Spatial Mapping and Suitability Analysis of Seagrass Meadows around Gaya Island Using Maximum Entropy (MaxEnt) Modelling - Siti Nur Fara Umairah Jali; Amanda Loris; Imelus Nius; Ashley Loduni; Wei Sheng Chong (Ocean Science Journal, 2026)

Sea Surface Temperature Variability in Izmir Bay, Aegean Sea: Marine Heat Waves, Cold Spells, and Fish Mass Mortality Events - Erdal Tokat (Ocean Science Journal, 2026)

psbA Metabarcoding Reveals Cryptic Diversity of Crustose Coralline Algae from Korea - Kyeong-Tae Lee; Myung Sook Kim (Ocean Science Journal, 2026)

Internal Architecture and Sedimentary Evolution of Heterolithic Tidal Ridges in the Central Yellow Sea - Yoo Jin Kwon; Sookwan Kim; Sang-Hoon Lee; Su-hwan Lee; Jongha Hwang; Seonghoon Moon; Tae Yeon Kim; Heung Soo Moon (Ocean Science Journal, 2026)

Tempo-Spatial Land Cover and Shoreline Dynamics of Sundarbans Mangrove Forest: A Geospatial Approach - Hasibul Hasan; Rifat-Ara Neera; Md. Mahin Uddin; Md Jobaer Alam; Mahmudul Hasan (Ocean Science Journal, 2026)

Vertical Distribution of Eggs and Larvae of Glyptocephalus Stelleri in the East Sea of Korea - Bo-Ram Lee; Hwan-Sung Ji; Hyo-Jae Yu; Jeong-Hoon Lee; Sukyung Kang (Ocean Science Journal, 2026)

A Validated Coupled Three-Dimensional Hydrodynamic and Wave Model for Water Levels and Wind Waves in the Western North Atlantic Ocean - Maria Venolia; Reza Marsooli; Jaime R. Calzada (Ocean Science Journal, 2026)
Accurate prediction of the coastal ocean requires models that capture dominant barotropic drivers, resolve baroclinic processes, and account for wind-waves. This study evaluates the performance of a high-resolution coupled three-dimensional hydrodynamic (SCHISM) and spectral wave (WWM III) model for simulating water levels and wave characteristics in the western North Atlantic Ocean. The model performance is evaluated for different wave parameterization methods, and the contribution of waves to water levels is quantified. Comparisons with in-situ measurements show that the coupled model reproduces tidal constituents, non-tidal components, and total water levels robustly along the U.S. East and Gulf of Mexico Coasts. Simulations using three different wave-physics parameterizations in the wave model show that each performs well for specific wave characteristics and locations; however, no single parameterization is optimal across the entire basin. Finally, the results show that including waves increases modeled water-level accuracy by about 3% on average across all study sites, though the improvement varies regionally. The greatest increases in accuracy, approximately 10% on average, occur at sites in the Gulf of Mexico.

Marine Debris Characteristics and Their Relationship with Reef Habitat Across Two Depth Levels in Taka Bonerate National Park, Indonesia - Citra Syananta; Ade Yamindago; Nur Kholis Wahib; Atsuhiko Isobe; Defri Yona (Ocean Science Journal, 2026)

Multi-view Glint Correction for UAV Multispectral Imagery in Benthic-Influenced Shallow Waters - Seungil Baek; Sooyoon Koh; Phillip Kim; Jong Hyuk Lee; Moonho Son; Won-Gi Min; Min-Su Woo; Wonkook Kim (Ocean Science Journal, 2026)

Numerical Modeling of Subduction Zone Thermal Structure with Firedrake and Gmsh - Minji Seong; Hyeon-Seob Kim; Kyeong-Min Lee; Jeonghyeop Kim; Byung-Dal So (Ocean Science Journal, 2026)

Typhoon Response and Recovery of Topography and Surface Sediments in the Macro-Tide Intertidal Flat of the Gochang Donghori, Korea - Woo Hun Ryang; Sol Ip Kang (Ocean Science Journal, 2026)

Unveiling the Mesopelagic Ichthyofauna in Korean Waters: Ecological Significance and the Need for Precautionary Management - Dongwha Sohn; Suam Kim; Youn-Ho Lee; Hwahyun Lee (Ocean Science Journal, 2026)

Decline of Acropora spp. in the Saudi Waters of the Arabian Gulf: Insights from Thirteen Years of Reef Surveys - Sudhanshu Dixit; Reynaldo T. Lindo; Rommel H. Maneja; Ace Vincent B. Flandez; Jinoy Gopalan; Thiyagarajan Duraisamy; Goutham Sambath; Yasir Y. Asiri; Mubarak S. Al-Jedani; Periyadan K. Krishnakumar; Karuppasamy P. Manikandan; Thadickal V. Joydas; et al. (Ocean Science Journal, 2026)

Energy Storage and Utilization in Wild Pacific Oysters (Crassostrea gigas) in an Annual Reproductive Cycle in Uihangri Tidal Flat on the West Coast of Korea, 4 Years After the Hebei Spirit Oil Spill (HSOS) Accident - Hyun-Ki Hong; Hee-Jung Lee; Hee-Do Jeung; Hyun-Sil Kang; Jeong-Hwa Kim; Nobuhisa Kajino; Kwang-Sik Choi (Ocean Science Journal, 2026)

Synoptic to Subseasonal Variability of Currents in the Southern Japan/East Sea - Hemantha W. Wijesekera; David W. Wang; William J. Teague; Kyung-Il Chang; Conrad A. Luecke; Ewa Jarosz; Sergio DeRada; Jae Hak Lee; Hong Sik Min; SungHyun Nam; Kyung Man Kim; Sung-Oh Lee (Ocean Science Journal, 2026)
Some aspects of synoptic to subseasonal variability of currents in the southern Japan/East Sea (JES) were investigated using high-resolution current measurements and reanalysis model products. Current measurements were made at multiple moorings containing acoustic Doppler current profilers (ADCPs) deployed during MJES (Mixing in the Japan/East Sea, 2021–2022) and LINKS (Linkages of Asian Marginal Seas, 1999–2000) programs. MJES measurements were collected over the southern slope of the Ulleung Basin (SSUB) and near the southeastern coast of Korea, and LINKS measurements were collected within the Korea-Tsushima Strait (KTS). Both LINKS and MJES observations revealed synoptic (2–7 days) to subseasonal (7–30 days) velocity fluctuations. Specifically, velocity fluctuations in the East Korea Warm Current on the southeastern Korean shelf from March to June 2022 reached magnitudes of 0.3 m s⁻ 1 , with broad periods ranging from 10 to 15 days. Local winds and currents were highly correlated here with a coherence of 0.95 at 12–13-day periods and a 2.7-day lag. Similar velocity fluctuations were observed at moored ADCPs on the SSUB and the northwestern corner of the KTS, but without any significant correlations between winds and currents. However, atmospheric surface-pressure distributions over the JES displayed 10–15 day oscillating along-basin pressure gradients of magnitudes $$\sim$$ 10 –5 mb m −1 . Our analysis suggests that wind and atmospheric pressure-gradient forcing can be important forcing mechanisms for generating the observed velocity fluctuations in the southern JES.

Distribution of Composition of Colloidal Organic Matter in the East Sea (Sea of Japan) Revealed by Fluorescence Spectroscopy - Jiyoung Lee; Jeonghyun Kim (Ocean Science Journal, 2026)

The Occurrence of Tetrodotoxin and Saxitoxin in the Xanthid Crab Zosimus aeneus from Vietnamese Coastal Waters - Khanh Hy Le Ho; Thi Thiet Doan; Bao Vy Phan; Xuan Ky Pham; Minh-Thu Phan; Thao My Nguyen Le; Thi Thu Thao Le; Kwang-Sik Choi; Dang Duc Nguyen; Ngoc Tung Nguyen; Viet Ha Dao (Ocean Science Journal, 2026)

Microplastic Uptake Potential by Marine Protists During the Summer: A Case Study in Busan Coastal Waters, South Korea - Jungmin Choi; Young-Ok Kim (Ocean Science Journal, 2026)

An Automated and Sample-Efficient Protocol for High-Precision Salinity Analysis using AutoSal 8400B - TaeKeun Rho; Sang Do Heo; Joonseong Park; Wooyoung Jeong; Purena Son (Ocean Science Journal, 2026)

Diel Dynamics of Bacterial and Picophytoplankton Growth, Grazing, and Viral Lysis at Different Depths in the Tropical South China Sea in Spring - Clara Natalie Annabel; Fuh-Kwo Shiah; Patrichka Wei-Yi Chen; Madeline Olivia; Tzong-Yueh Chen; An-Yi Tsai (Ocean Science Journal, 2026)

Mechanisms of Coral Bleaching and Biomarkers for Early Detection - Michelle Glory G Jonik; Mahadi Mohammad; Sazlina Salleh; Ching-Nen Nathan Chen; Nur Ain Amani Abdul Mubin; Nur Hidayah Abdullah (Ocean Science Journal, 2026)

Polyethylene and Polypropylene Degradation in the Echinodermata Digestive Organs - Alexander A. Karpenko; Vyacheslav S. Odintsov; Aleksandra A. Istomina (Ocean Science Journal, 2026)

Lagrangian Analysis of Source Water Variability in Korea Strait Inflow Across Seasonal and Decadal Timescales in an Eddying Climate Model - Hyeju An; Sang-Yeob Kim; Ho Jin Lee; Wonsun Park (Ocean Science Journal, 2026)

Long-term Monitoring of Meiofaunal Density and Community Composition on the Coast of Dokdo, East Sea, Korea - Teawook Kang; Dongsung Kim; Je-Hyeok Oh; A-Young Shin; Mu Gyeom Jeon; Won Gi Min (Ocean Science Journal, 2026)

Phylogeographic Structure and Haplotype Diversity of Seaweeds Ecklonia cava and Eisenia bicyclis Along the Korean Coast Using Mitochondrial DNA Markers - Jin-Won Lee; Jeong-Mi Do; Boseong Kim; Yu-Hee Seo; Myeong-Jun Gwon; KyoungSu Choi; Ho-Sung Yoon (Ocean Science Journal, 2026)

Status and Community Structure of Coral Reefs in the Southern Vietnam - Minh-Quang Thai; Van-Long Nguyen; Xuan-Dat Mai; Xuan-Ben Hoang; Si-Tuan Vo (Ocean Science Journal, 2026)

Biochemical Responses of Pacific Oysters (Crassostrea gigas) to Contrasting Oceanographic Environments: Implications of Hydrodynamics, Salinity, and Phytoplankton Communities - Kyung-Il Park; Soohwan Kim; Seung-Hyeon Kim; Jong-Deok Choi; Hye-Mi Lee; H. M. V. Udayantha; Yu Chen; S. D. N. K. Bathige (Ocean Science Journal, 2026)

Physiological Effects on Hematological Characteristics and Plasma Components of Olive Flounder, Paralichthys olivaceus Exposed to Spirulina, Spirulina maxima - Bijae Gong; Young-Bin Yu; A-Hyun Jo; Eunsol Hyun; Woon-Yong Choi; Gi-Young Kim; Hyunjung Lee; Sung-Pyo Hur; Cheol Young Choi; Kyuchang Chang; Jun-Hwan Kim (Ocean Science Journal, 2026)

Biochemical and Bioactive Potential of the Sea-urchin Stomopneustes variolaris from the Bay of Bengal - Hanif Biswas; Zakir Sultan; S. M. Abdur Rahman (Ocean Science Journal, 2026)

Annual net community production in the western North Pacific subtropical gyre estimated from Argo float observations - Doshik Hahm; Inhee Lee (Ocean Science Journal, 2026)

Erratum: Impacts of Fin-Fish Farming on the Organic Carbon Mineralization and Resultant Phosphorus Dynamics in Sediments of Hadong, Southern Coast of Korea - Sangbeom Baek; Jin-Sook Mok; Yerim Lee; Hyeonji Lee; Haneul Kim; Kee-Young Kwon; Jung-Ho Hyun (Ocean Science Journal, 2026)

Monitoring Coastal Water Quality Using Remote Sensing and Machine Learning - K. Ambika; P. Shanmugapriya; Abdulaziz G. Alghamdi; Hadeel Alsolai (Ocean Science Journal, 2026)

Enhancing Coastal Wave Forecasts Around the Korean Peninsula with Time-Series Decomposition and Spatio-Temporal Deep Learning - Donghwi Son; Jeseon Yoo; Hyoseob Noh (Ocean Science Journal, 2026)

Temporal Dynamics in Biochemical Composition, Energy Reserves and Condition Index of Blood Cockle, Tegillarca granosa (L., 1758) Natural Population from a Tropical Monsoon Coastal Habitat - Sumaiya Binte Ayesha; Maliha Khanom; Md.Sazzad Hossain; Sanjida Afrin Semme; Shah Rafia Tangin Mohona; Md.Jasim Uddin (Ocean Science Journal, 2026)

Long-Term Variability and Ecological Structure of Macrobenthic Polychaete Communities in Korean Coastal Waters: A 30-Year (1993–2022) Data-Based Assessment - Geon Kim; Kyeong Hun Lim; Jung Ho Lee; Sung Wan Park; Hyun Chool Shin (Ocean Science Journal, 2026)

Transcriptomic Analysis of Human Dermal Fibroblasts Exposed to Sargassum micracanthum Ethanol Extract Indicates Upregulation of Collagen-Related Genes - Hyeongwoo Choi; Tae-Hee Kim; Dong-Joo Park; Se-Chang Kim; Bonggi Lee; Hyun-Woo Kim; Won-Kyo Jung (Ocean Science Journal, 2026)

Underwater Noise, Marine Mammal Impacts, and Monitoring Strategies in the Arctic Ocean - Siddharth Khopkar; Miyoung Yeo; Hyunkyo Seo; Hyoung Sul La (Ocean Science Journal, 2026)

Scientific Implications of the Comprehensive Skeletal Discovery of the Extinct Dokdo Sea Lion (Zalophus japonicus) from Ulleungdo, Korea - Yoon Ji Lee; Myung Joon Kim; Ji Seong Kim; Seok Nam Kwak; Sang Heon Lee (Ocean Science Journal, 2026)

Marine Cold Spells in the Indonesian Seas Under Climate Change: Trends, Classification, and Drivers - Erlin Beliyana; Nining Sari Ningsih; Ikliema Hassya Kamila; Farrah Hanifah; Ayi Tarya (Ocean Science Journal, 2026)

The Dynamics of Nearshore Currents Under Extreme Wind Regime: A Case Study in Bangka Regency of the East Bangka Island Region, Indonesia - Johan Risandi; Brigita S. Mutiara; Terry L. Kepel; Dwi Hindarti; Faisal Hamzah; Furqon Alfahmi; Husen Rifai; Mira; Nani I. J. Undap; Mardi Wibowo; Mutiara R. Putri (Ocean Science Journal, 2026)

Amino Acid-Based Assessment of Bioavailability and Alteration of Organic Matter in the East Sea - Boyeon Lee; Jun-Oh Min; Chorom Shim; Sun-Yong Ha; Bo Kyung Kim; Jaeill Yoo; Kyung-Hoon Shin (Ocean Science Journal, 2026)

Erratum: Partial Nonlinear Iteration During Early Continental Rifting for Symmetric Surface Topography and Heat Flux - Jieun Chang; Byung-Dal So (Ocean Science Journal, 2026)

Sea Surface Salinity Variability in the Tropical Indian Ocean from Reanalysis Datasets - S. K. Sahoo; I. M. Momin; J. P. George (Ocean Science Journal, 2026)

Influence of Stratospheric Geoengineering on the Salinity Barrier Layer Seasonal Cycle in the Northeastern Gulf of Guinea - F. F. B. K. Ayissi; C. Y. Da-Allada; E. Baloïtcha; J. Agada; L. G. Mekonou-Tamko; S. Tilmes; E. Capo-Chichi (Ocean Science Journal, 2026)
Barrier layer (BL), by reinforcing ocean stratification, can maintain sea surface waters warming and limit nutrients supply into the euphotic layer, which is important to marine life. This study investigates the influence of stratospheric aerosol geoengineering (SAG) on the seasonal variability of the BL in the northeastern Gulf of Guinea (NEGG) and its causes based on data from the Geoengineering Large Ensemble project simulated under a high anthropogenic emission scenario and on observations. Results show that the model reproduces well the BL pattern according to observations in the northern Gulf of Guinea. BL is thicker in the NEGG, especially during boreal autumn, with barrier layer thickness (BLT) reaching a maximum value of 19 m in October. Under global warming compared to the current climate, the BLT increases slightly at the beginning of the year and strongly in boreal autumn by 14% with a maximum of + 4.5 m reached in November. The largest increase in BLT occurs in the NEGG, but the region of BL thickening also expands spatially toward the western Gulf of Guinea. The increase of BLT during boreal autumn is related to a 14% increase in river runoff and precipitation, with river runoff increasing by 17% and precipitation by 8%. Under SAG compared to the current climate, the BLT increases by 2% during boreal autumn in NEGG. This increase in BLT is relatively minor compared to global warming and is explained partly by a decrease in river runoff and precipitation of − 7%. Ocean dynamic processes through zonal advection and vertical mixing contribute to the little increase of BLT.

Short-Term Movement of MiniPAT-Tagged Coastal Fishes in the Yellow Sea: Case Studies on Korean Rockfish (Sebastes schlegelii) and Spotted Sea Bass (Lateolabrax spp.) - Young Uk Kim; Yun Jeong Seo; Won Young Lee; Sung-Yong Oh (Ocean Science Journal, 2026)

Deep Learning-Enabled Real-Time Monitoring of Coastal Water Pollution Using Sentinel-2 Remote Sensing Data - Eatedal Alabdulkreem; Turke Althobaiti; Mohammed Abaker; G. Murugesan; Hanadi Alkhudhayr; S. Srinivasan; V. Sampathkumar; V. Priya (Ocean Science Journal, 2026)

Modeling Future Coastal Morphodynamics Under Climate Forcing Using Ensemble-Based Machine Learning Approaches - Ghadah Aldehim; Randa Allafi; Abdulwhab Alkharashi; A. Sagai Francis Britto; J. Vijayalakshmi; A. Sumaiya Begum; M. C. Sashikkumar; V. Priya (Ocean Science Journal, 2026)

Methods and Instrumentation for In Situ Quantification and Sampling of Coastal and Deep-Sea Bioluminescent Organisms - Chatragadda Ramesh; Kanakam Anil (Ocean Science Journal, 2026)

An Indoor Mesocosm System for Cost-Effective Simulation of Multiple Ocean Stressors Affecting Marine Organisms - Sukyeon Lee; Jin Woo Kang; Im-Ho Choi; Juhyung Lee; Ju-Hyoung Kim (Ocean Science Journal, 2026)

Erratum: Basin-Scale Swarm of the Sea Butterfly Cavolinia Uncinata (Gastropoda: Pteropoda) in the Korea Strait: Linkage to the Tsushima Warm Current - Hyun Jun Yang; Yun Hee Kim; Hye Jin Seo; Seunghyun Son; Se Hyeon Jang (Ocean Science Journal, 2026)

Assessing the Reliability of ADCP-Derived Echo Intensity Under Variable Scattering Conditions: Roles of Sediment, Zooplankton, and Bubbles - Jun Young Seo; Sun Min Choi; Dong Hyeon Kim; Yong Hoon Kim; Jongseong Ryu; Ho Kyung Ha (Ocean Science Journal, 2026)

Characterization of Rogue Wave Occurrence During Typhoon Hinnamnor Using Directional Wave Spectra and High-Order Spectral Simulations - Faizal Ade Rahmahuddin Abdullah; Jeseon Yoo (Ocean Science Journal, 2026)
Rogue waves often occur unexpectedly during severe weather conditions, such as typhoons, where rapidly evolving sea states enhance nonlinear wave interactions. Typhoon Hinnamnor, one of the most intense storms in the Northwest Pacific during 2022, generated a sequence of extreme sea states that provide a valuable case for investigating rogue wave dynamics. Among them, two contrasting phases are analyzed: a wind-sea-dominated state before intensification and a swell-dominated state after re-intensification. Phase-resolving simulations are conducted using the Higher-Order Spectral (HOS) method, initialized with directional wave spectra from WAVEWATCH III (WW3) hindcast data. Key statistical parameters including wave skewness and excess kurtosis are examined to assess their roles in extreme crest formation. The HOS-simulated wave fields clearly capture the probability of highly nonlinear extreme crests, showing strong agreement with the Tayfun second- and third-order distribution models, while deviating significantly from the Rayleigh distribution base on linear theory. Results also reveal that rogue waves are more likely to occur in positively skewed sea states, emphasizing the importance of second order bound nonlinearities. In contrast, excess kurtosis remains near zero with a slight positive bias, indicating a limited role of third-order modulational processes. Probability density functions, cumulative distributions, and exceedance analyses further support the strong link between skewness and rogue wave probability. These findings underscore the critical role of evolving directional wave spectra in shaping nonlinear wave statistics and provide valuable insights for improving rogue wave prediction and maritime safety in storm-driven sea states.

Marine Macrobenthos Diversity of Chuuk Atoll in the Federated States of Micronesia, Western Tropical Pacific - Taihun Kim; Anna B. Jöst; Heung-Sik Park; Dong Sung Kim; Hyi-Seung Lee; Do-Hyung Kang (Ocean Science Journal, 2026)

Characteristics of Meiofaunal Communities in the Infralittoral-Circalittoral Transition Zone Compared to the Infralittoral Zone Around Dokdo, Korea - Mu Gyeom Jeon; Won Gi Min; Je-Hyeok Oh; A-Young Shin; Teawook Kang; Chulwoong Oh; Dongsung Kim (Ocean Science Journal, 2026)

Effects of Expanded Polystyrene Particles on the Diversity and Composition of the Gut Microbiome of the Coastal Isopod Ligia cinerascens - Youn-Ha Lee; Je-Won Yoo; Chaerin Park; Kwang-Min Choi; Jee-Hyun Jung; Young-Mi Lee (Ocean Science Journal, 2025)

Basin-Scale Swarm of the Sea Butterfly Cavolinia uncinata (Gastropoda: Pteropoda) in the Korea Strait: Linkage to the Tsushima Warm Current - Hyun Jun Yang; Yun Hee Kim; Hye Jin Seo; Seunghyun Son; Se Hyeon Jang (Ocean Science Journal, 2025)

Phylogenetic Diversity and Enzymatic Activities of Cultivable Actinomycetes Isolated from Marine Sediment at Ain Achir (Gulf of Annaba, Algeria) - Ilhem Meriane; Stuart McMillan; Andrew P. Desbois; Mahmoud Kitouni (Ocean Science Journal, 2025)
Algerian marine sediments are an underexplored and potentially rich source of microorganisms that may produce useful metabolites and enzymes. Here, we investigated the phylogenetic diversity and enzymatic activities of suspected Actinomycetia bacteria isolated from seabed sediment at Ain Achir, Gulf of Annaba, Algeria. Morphological, physiological and taxonomical properties were characterized and their potential to produce enzyme activities was studied. Phylogenetic analysis of partial 16S rRNA gene sequences assigned isolates into five main genera: Rhodococcus (21/35), Microbacterium (5/35), Streptomyces (3/35), Brevibacterium (2/35) and Agromyces (2/35). Screening for 14 enzymatic activities demonstrated their abilities to metabolize a wide range of substrates including DNA, L-asparagine, and L-glutamine (each degraded by all 35 isolates). Other substrates degraded by most isolates included uric acid and urea (both 33/35), starch (25/35) and tyrosine (24/35). Moreover, the number of enzymatic activities possessed by the isolates ranged from six (one isolate) to 10 (four isolates). This study is the first to investigate the phylogenetic diversity and enzymatic activities of actinomycetes isolated from sea sediment in the Gulf of Annaba and it confirms that actinomycetes from the marine environment are a valuable source of enzymes, with further investigation required to unlock their potential commercial applications.

Explainable machine learning for bathymetric mapping: adaptive normalization and feature engineering in complex seabed terrains - Ahmet Durap (Ocean Science Journal, 2025)

Source-to-Sink of the Korean Shelf Mud Deposits Since the Mid-Holocene - Bo Ram Lee; Dong Geun Yoo; Dhong Il Lim; Gil Young Kim; Seom Kyu Jung; Jin Hyung Cho (Ocean Science Journal, 2025)

Effects of Two Restoration Approaches on Temporal Dynamics of Macrobenthic Communities in Intertidal Flats - So Yun Jang; Sang Ock Ryu; Hyun Chool Shin; Chang Gun Lee; Ha Neul Oh; Sun Kwan Oh; Jeong Rok Lee; Young Sook Baek (Ocean Science Journal, 2025)

Marine Debris Assessment Post-Hurricane Using Remote Sensing and Machine Learning Techniques - S. Venkatraman; V. Mohan; Eatedal Alabdulkreem; Achraf Ben Miled; Khalid Nazim Abdul Sattar; Setu Garg (Ocean Science Journal, 2025)

Machine Learning Based Identification of River Plastic Litter in Coastal Region Using Sentinel-2 Data: An Automated Approach for Marine Pollution Monitoring and Management - M. Vadivel; Nada Alzaben; Malak Zayed Alamri; Menwa Alshammerid; S. V. N. Pammi; V. Priya (Ocean Science Journal, 2025)

First Assessment of Coccolithophore-Driven Carbonate Flux in the Ulleung Basin, East Sea (Sea of Japan) - Sung Min An; Dong Han Choi; Young-Il Kim; Young Suk Chang; Jae Hoon Noh (Ocean Science Journal, 2025)

Recent Acceleration of Tidal Amplification in the Vietnamese Mekong Delta: Drivers and Environmental Change Implications - Cong Thanh Nguyen; Van Xuan Tran; Nghia Hung Nguyen; Truong An Dang (Ocean Science Journal, 2025)

Interannual Variability in Acoustic Backscatter and Oceanographic Drivers in the Southwestern Indian Ocean - Fredrich Simanungkalit; Dongha Kang; Jihoon Jung; Joohyang Kim; Somang Song; Yeseul Kim; SungHyun Nam; Dong-Jin Kang; Myounghee Kang (Ocean Science Journal, 2025)

Performance Evaluation of a Portable Filter Skid for Zooplankton Sampling in Response to the Ballast Water Management Convention - Jaebeom Shin; Jeongmin Cho; Yunho Shin; Yujin Choi; Ryoungah Kim; Kyeonghun Kim (Ocean Science Journal, 2025)

Enhanced Microbial Respiration in the Open Melt Pond in the Arctic Ocean and its Implications for Carbon Cycles - Jun-Oh Min; Jung-Ho Hyun; Bomina Kim; Jinyoung Jung; Sang-Heon Lee; Sung-Ho Kang (Ocean Science Journal, 2025)

Measuring the Ecological Consequences of Coastal Uplift and Subsidence on Mangrove Crabs in the Andaman Islands, India - Mayur Fulmali; Anoop Raj Singh; Nehru Prabakaran (Ocean Science Journal, 2025)

Seasonal and Interannual Variability of Mixed-Layer Depth and Surface Chlorophyll-a in the Bay of Bengal: Insights into Physical-Biological Coupling - Siraj Uddin Md Babar Chowdhury; Md Minarul Hoque; Anik Karmakar; Nur Uddin Md Khaled Chowdhury; K. M. Azam Chowdhury; Tabassum Hossain Tahsin; Ashraful Moontahab (Ocean Science Journal, 2025)

First Report of Scrippsiella irregularis Attaran-Fariman & Bolch (Dinophyceae) from Korean Coastal Waters - Minseok Jeong; Da Bin Choi; Zhun Li; Kyong Ha Han; Jinik Hwang; Hyeon Ho Shin (Ocean Science Journal, 2025)

Spatial Variation of Energy Sourcing in Deep-Sea Vent Anemones from the Central Indian Ridge - Eun-Bi Kim; Yeon Jee Suh (Ocean Science Journal, 2025)

Partial Nonlinear Iteration During Early Continental Rifting for Symmetric Surface Topography and Heat Flux - Jieun Chang; Byung-Dal So (Ocean Science Journal, 2025)

Self-Regulation Pattern of Modern Microtidal Barrier Experiencing the Rising Sea Level in Southern Mediterranean Coasts - Maher Gzam; Avouca Mahamoud; Mustapha Hidouri; Laurent Dezileau (Ocean Science Journal, 2025)

Smooth Particle Hydrodynamics Modeling of Coastal Width Influence on Sediment Transport and Shoreline Morphodynamics - Rilwan Kayode Apalowo; Mohd Hafiz Zawawi; Aizat Abas; Nazirul Mubin Zahari; Zarina Itam (Ocean Science Journal, 2025)

Effects of Various Light-Emitting Diode Wavelengths on the Regulation and Control of Sexual Maturation in Abalone Haliotis discus hannai - Kun Woo Kim; Won Chae Jeong; Jin A. Kim; Ji Yong Choi; Jun-Hwan Kim; Cheol Young Choi (Ocean Science Journal, 2025)

Distributions of Dissolved Trace Metals in the Nakdong River Estuary: Influence of an Estuarine Barrage on Their Geochemical Behaviors - Ijin Lim; Jiwoo Kim; Jumi Kim; Sung-Uk An; Hyung-Mi Cho; Heejun Han; Hojong Seo; Taejin Kim (Ocean Science Journal, 2025)

Coastal Erosion and Accretion Trends in Gujarat and Odisha: A 4-Decade Shoreline Study - Neha Priyadarshini; Vikas Prasad (Ocean Science Journal, 2025)

Isotopic Constraints on Nitrate Cycling in the Yellow Sea: Seasonal and Regional Patterns - Seonghee Jeong; Junghyun Lee; Doshik Hahm; TaeKeun Rho; Purena Son; Hyung-Mi Cho; Guebuem Kim; Tongsup Lee (Ocean Science Journal, 2025)

Estimation of Extreme Wave and Wind Design Parameters and Impact of Storm Propagation Speed on Coastal Flood Hazard in the Center Coast of Algiers - Rachida Belhout; Khoudir Mezouar; Selma Chahtou; Youcef Khamallah (Ocean Science Journal, 2025)

Spatial Distribution and Key Environmental Factors of Benthic Polychaete Community in Korean Coast - Sung Wan Park; Hyun Chool Shin (Ocean Science Journal, 2025)

Newly Introduced GAMBI and OSTREO Indices for Epiphytic Dinoflagellate Communities - Hyung Seop Kim; Bora Jang; Mi Ryoung Oh; Yong Deok Ko; Keon Gang Jang; Jong Woo Park; Byoung-Ju Choi; Wonho Yih (Ocean Science Journal, 2025)

Effects of Different Wavelengths on Stress Responses in Disk Abalone Haliotis discus hannai Exposed to Changing Saline Environments - Rae Hyok Hwang; Jin A Kim; Ji Yong Choi; Jun-Hwan Kim; Cheol Young Choi (Ocean Science Journal, 2025)

Engineered Nanoparticles in the Marine Environment: A Future Risk for Seafood Security and Safety? - N. P. P. S. Nugawela; S. H. S. K. Gunarathna; A. S. Mahaliyana (Ocean Science Journal, 2025)

Distribution and Atmospheric Release of Methane Dissolved in Coastal Waters of the South Sea off Korea (Preliminary Results from the Goheung Coast) - Suyeon Ryu; DongJoo Joung (Ocean Science Journal, 2025)

High Condition Index in Subtidal Manila Clams Ruditapes philippinarum Despite High Level of Perkinsus olseni Infection on the South Coast of Korea - Thatchaneshkanth Subramaniam; Young-Ghan Cho; Hee Jung Choi; Mun-Gyeong Kwon; Kwang-Sik Choi (Ocean Science Journal, 2025)

Impacts of Fin-Fish Farming on the Organic Carbon Mineralization and Resultant Phosphorus Dynamics in Sediments of Hadong, Southern Coast of Korea - Sangbeom Baek; Jin-Sook Mok; Yerim Lee; Hyeonji Lee; Haneul Kim; Kee-Young Kwon; Jung-Ho Hyun (Ocean Science Journal, 2025)

Phylogeographic Distribution of Invasive Cordgrasses Spartina alterniflora and Spartina anglica Reveals Multiple Introductions to Korean Coasts - Buhari Lawan Muhammad; Jang-Seu Ki (Ocean Science Journal, 2025)

Surface Drifters and Ocean Dynamics: A Review of Technological Advancements and Scientific Contributions - Dong-Kyu Lee; Nikolai Maximenko (Ocean Science Journal, 2025)

Unbiased Estimation of the Maximum Wave Height-to-Significant Wave Height Ratio Using Wave Monitoring Data - Hong Yeon Cho; Gi Seop Lee; Weon-Mu Jeong; Kyong Ho Ryu; Yeon S. Chang (Ocean Science Journal, 2025)

CO2 Partial Pressure and Air-Sea CO2 Flux in the Bach Dang Estuary (Hai Phong City, Vietnam) - Cao Thi Thu Trang; Pham Thi Kha; Le Van Nam; Dinh Hai Ngoc; Do Tien Long; Nguyen Thi Anh Huong; Pham Thi Ngoc Mai; Nguyen Van Minh; Pham Van Quang; Nguyen Thi Thu Ha (Ocean Science Journal, 2025)

A Survey of Deep Learning Approaches for the Monitoring and Classification of Seagrass - Uzma Nawaz; Mufti Anees-ur-Rahaman; Zubair Saeed (Ocean Science Journal, 2025)
Seagrass meadows are essential to the health of coastal ecosystems. They support carbon storage, provide habitats for marine species, and help stabilize coastlines. Monitoring underwater seagrass is vital for understanding the conditions of the ecosystem. Researchers have been interested in identifying and classifying underwater seagrasses. However, traditional monitoring methods can be labor-intensive and costly, especially in complex underwater environments. Deep learning approaches have made significant progress in digital image processing, particularly in object recognition and classification, and are among the most popular computer vision tools. The collection of digital images for monitoring underwater habitats, such as seagrass meadows, has increased significantly as recent progress in imaging technology has made it easier to collect high-resolution data. The increase in imagery data has in turn created a demand for automated detection and classification using deep neural network-based techniques. This study reviews the current deep-learning techniques used for monitoring and classification of the seagrass. It discusses the key methodologies, datasets, and progress in this area. This study not only examines the well-known challenges such as limited availability of data but provides a novel, structured taxonomy of deep learning techniques tailored for the monitoring of seagrass, highlighting their unique advantages and limitations within diverse marine environments. By synthesizing findings across various data sources and model architectures, we offer critical insights into the selection of context-aware algorithms and identify key research gaps, an essential step for advancing the reliability and applicability of AI-driven seagrass conservation efforts.

Current State of Ocean Acidification in Surface Waters of the Western Arctic Ocean from 2020 to 2022 - Dongseon Kim; Sosul Cho; Eun-Jin Yang; Kyoung-Ho Cho; Jinyoung Jung (Ocean Science Journal, 2025)

Decadal Shifts in Macrobenthic Communities and Feeding Types in the Rocky Subtidal Zone of Gageodo, Southwestern Korea - Hyun-Jung Kim; Chung Il Lee; Su Jin Lee; Choul-Hee Hwang; Young Yoon Kim; InSeo Hwang; Soo-Yeon Cho; HoJoon Choi; Joo Myun Park (Ocean Science Journal, 2025)

Predicting Peruvian Anchovy School Density with GAMLSS and BAMLSS Using Morphological Descriptors Extracted from Echograms - Oswaldo Miguel Flores Huaman; Marceliano Buenaventura Segura Zamudio; German Pablo Chacón Nieto; Carlos Jorge Paulino Rojas (Ocean Science Journal, 2025)

Time-Resolved Fluorescence Immunochromatography Sensor for Detecting Okadaic Acid in Shellfish - Zhi Zhang; Yaofan Lu; Fuyuan Ma; Chenhao Zhao; Jiayu Li; Biao Huang; Yuan Qin (Ocean Science Journal, 2025)

P-limited Prokaryotic Heterotrophic Production and Metabolic Balance Between Prokaryotic Carbon Demand and Phytoplankton Primary Production in Summer in the Central Yellow Sea - Bomina Kim; Yong-Jae Baek; Heejun Han; Hyeonji Lee; Seok-Hyun Youn; Jung-Ho Hyun (Ocean Science Journal, 2025)

Changes in the Specific Gravity of Small Yellow Croaker (Larimichthys polyactis) During Early Life History - Hyung-Jin Ahn; In-Uk Hwang; Seung-Jun Lee; Kyung-Nam Han (Ocean Science Journal, 2025)

Erratum: Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2025)

A Long-Term Survey on the Shoreline Changes of Gulf of Oman Coasts (Makran) - Danial Ghaderi; Maryam Rahbani (Ocean Science Journal, 2025)

Spatial and Temporal Variation of Synechococcus Abundance and Diversity in the Yellow Sea - Jongseok Won; Myungjin Hyun; Wonseok Yang; Howon Lee; Yeonjung Lee; Seok Lee; Kongtae Ra; Hee Cheol Yang; Jae Hoon Noh; Dong Han Choi (Ocean Science Journal, 2025)

137Cs Distribution Coefficients in Seawater, Sedimentation Rates, and Remobilization in Sediment Cores from Masan Bay and Suyeong Bay, Korea - Hyeong Kyu Kwon; Jaehong Park; Young-Il Kim; Guebuem Kim (Ocean Science Journal, 2025)
We measured 137 Cs in seawater, particulate matter, and sediment cores from two coastal bays (Masan Bay and Suyeong Bay) in Korea in August 2016 and July 2017 to examine its deposition in water and remobilization in the sediments. The 137 Cs activities in the bay seawaters were similar to those in the remote ocean seawaters, suggesting that there are no extra 137 Cs inputs from land. We reconstructed the deposition history of 137 Cs using the measured distribution coefficient ( K d ) values in the bay, the known history of 137 Cs activities in the remote ocean seawaters, and sediment ages based on the 210 Pb method. The measured inventory of 137 Cs in the sediment cores retained about 89–94% of the reconstructed 137 Cs inventory in the same depths, but the measured distribution patterns were very different from the reconstructed profiles. The measured distributions of 137 Cs were quite uniform and penetrated more deeply, with the peaks at a shallow oxic layer and around 1963, indicating significant post-depositional remobilization and redistribution due to changes in porewater chemistry with depth. The sedimentation rates (0.53–0.70 cm yr −1 ) derived from 137 Cs in the two bays agree well with those (0.51–0.68 cm yr −1 ) derived from 210 Pb. Thus, our results suggest that 137 Cs can be used as an independent geochronological tracer in coastal sediments, but careful consideration is necessary for the remobilization of 137 Cs in sediment cores.

Impacts of Along-Strait Winds on Sea Level, Sea Surface Temperature, and Current in the Jeju Strait During Summer 2022 - Chang-Woong Shin; Hong Sik Min; Seok Lee; Kyung-Hee Oh; Yong Sun Kim; Hyoun-Woo Kang; Byoung-Ju Choi (Ocean Science Journal, 2025)
The along-strait wind in the Jeju Strait (JS) significantly impacts the sea level, surface temperature, and currents on its northern and southern coasts. During the summer of 2022, the winds in the JS were characterized by strong easterly winds that occurred before the approach of several typhoons. A strong correlation of 0.61 was found between the along-strait wind and the difference in sea level anomaly between the strait’s south and north coasts. A more robust correlation of 0.71 was estimated between the along-strait wind and the difference in sea surface temperature anomaly. When the positive (eastward) wind blows along the strait, it causes upwelling along the north coast, resulting in cold anomalies there and warm anomalies along the south coast, and vice versa. In addition, a positive correlation ( r = 0.39–0.50) was estimated between the along-strait wind and along-strait surface current, with a negative correlation ( r = −0.68 to −0.44) for the cross-strait current in most observation stations of the JS, except near the coast of Jeju Island. The positive along-strait wind causes the sea level to fall on the north coast and strengthens the eastward surface current. In contrast, the negative (westward) along-strait wind has the opposite effect, causing the sea level to rise near Wando, then slowing down or reversing the eastward surface current. Overall, these findings show that Ekman dynamics can explain wind-induced coastal upwelling and downwelling on both coasts of the JS, providing valuable insights into the environmental conditions surrounding marine organisms in this coastal region.

Mapping the Dynamics of Particulate Organic Carbon: Satellite Observations of Coastal to Shelf Variability in the Northeastern Gulf of Mexico - Hafez Ahmad; Shakila Islam Jhara (Ocean Science Journal, 2025)

Transcriptome-Based Prediction of the Toxicity of the Marine Biotoxin Okadaic Acid in Human Vascular Endothelial Cells - Jong Hee Kim; Jeong-In Park; Yewon Kim; Mira Park; Jang Kyun Kim; Young-Seok Han; Youn-Jung Kim (Ocean Science Journal, 2025)

Fluctuations and Benthic Flux of Inorganic Nutrients Associated with Tidal Cycles and Its Implications to the Outwelling Process in Garolim Bay, Yellow Sea - Sung-Uk An; Bomina Kim; Sung-Han Kim; Jin-Sook Mok; Jung-Ho Hyun (Ocean Science Journal, 2025)

Diversity and Bioactivities of Ulleung Island-Derived Marine Actinomycetes - Jeonghee Lee; Hyeongsub Shin; Ho Sung Kim; Jeong Woo Park; Ganiyu Akinniyi; Soojin Kang; Ki Hwan Moon; Inho Yang (Ocean Science Journal, 2025)
Actinomycetes are key producers of bioactive secondary metabolites. In this study, sediment samples were collected using a grab sampler from the coast of Ulleung Island and inoculated on various agar media by stamping to isolate Actinomycetes. As a result, 69 Actinomycete strains were isolated and laboratory-cultured from the sediment samples. The isolates were assigned to the genera Streptomyces (44 strains), Nocardia (6 strains), Rhodococcus (6 strains), Mycobacterium (6 strains), Micromonospora (3 strains), Nocardioides (2 strains), Marmoricola (1 strain), and Oerskovia (1 strain) based on 16S rRNA gene sequence analysis. The antibacterial activity and potential toxicity of the culture broth extracts were tested for all isolates. Extracts from some strains exhibited strong antibacterial activity against Acinetobacter baumannii 04 and methicillin-resistant Staphylococcus aureus . Additionally, some extracts were toxic to brine shrimp. This study confirms that marine Actinomycetes from Ulleung Island encompass unique and diverse taxonomic groups and are a good source of bioactive natural products.

Review on Hyperspectral Remote Sensing of Tidal Zones - Seungil Baek; Wonkook Kim (Ocean Science Journal, 2025)

Changes in Melatonin and Dopamine Secretion During Ovarian Development in Japanese Eel - Jun-Hwan Byun; Ji-Yeon Hyeon; Sung-Pyo Hur (Ocean Science Journal, 2025)

Volumetric Change Assessment and Mapping of Coastal Landform Between 2000 and 2011 Using Remote Sensing and Machine Learning Techniques - Indumathi C.P; Nada Alzaben; Mashael Maashi; Amal M. Nouri (Ocean Science Journal, 2025)

Simulation Characteristics of Ocean Predictability Experiment for Marine environment (OPEM): A Western North Pacific Regional Ocean Prediction System - Hyunkeun Jin; Young Ho Kim; Young-Gyu Park; Inseong Chang; You-Soon Chang; Hyukmin Park; Gyundo Pak (Ocean Science Journal, 2024)

Detection of Tetrodotoxin in the Xanthid Crab Atergatis floridus (Linnaeus, 1767) Collected from Jeju Island off the South Coast of Korea, Using Competitive Enzyme-Linked Immunosorbent Assay (cELISA) - Nobuhisa Kajino; Jong-Seop Shin; Hyun-Ki Hong; Thatchaneshkanth Subramaniam; Jung Hui Chae; Tae Hun Noh; Hyang Sook Chun; Kwang-Sik Choi (Ocean Science Journal, 2024)

Recent Multifaceted Studies on the Physical, Chemical, Geological, and Biological Processes in the Yellow and East China Seas and Implications to Global Environmental Changes - Kyung-Ae Park; Young Ho Kim (Ocean Science Journal, 2024)

Long-Term Changes in the Characteristics of the Yellow Sea Cold Water Mass in Spring and Autumn from 1996 to 2022 - Kyung-Hee Oh; Seok Lee (Ocean Science Journal, 2024)

Impacts of Typhoon Bavi on Prokaryotic Communities in the Yellow Sea - Wonseok Yang; Myung Jin Hyun; Jae Hoon Noh; Yeonjung Lee; JongSeok Won; Howon Lee; Kongtae Ra; Dong Han Choi (Ocean Science Journal, 2024)

Short-Term Variations in the Chemical Properties and Microbial Diversity of Intertidal Sediments Using Oyster Shells in a Field Study - Maheshkumar Prakash Patil; Hee-Eun Woo; Ilwon Jeong; Sung Eun Park; Jong-Oh Kim; Kyunghoi Kim (Ocean Science Journal, 2024)

A Kinematic Approach for Rip Current Identification from ADCP Observation Data at Haeundae Beach, Korea - Inkweon Bang; KyungMan Kim; Jeong-bon Gu; Sung-min Shin; Jong Beom Kim; Boonsoon Kang (Ocean Science Journal, 2024)
In May 2023, direct observations of rip currents were conducted at Haeundae Beach, Korea, over a two-day period at six different stations using upward-facing Acoustic Doppler Current Profilers (ADCPs). The depth-averaged cross-shore velocity data were low-pass filtered with a 30-s cutoff period to eliminate wave-related motions. By applying 15-min boxcar averages, correlation analyses were performed to examine the relationship between three types of flow (cross-shore, onshore, and offshore) and three environmental factors (tide, wave, and wind). The analysis revealed that only one (R2-3) of the six stations had a high likelihood of rip current occurrence. Rip currents were defined as regions of offshore flow within the low-pass filtered time series of cross-shore velocities. For each identified rip current, three key kinematic features—maximum speed, duration, and distance—were estimated. Using specific thresholds for these features, hazardous rip currents were determined. Station R2-3 was the only station where hazardous rip currents were observed, which is consistent with the findings of the correlation analysis. Additionally, swells with a 15-s period were detected exclusively at R2-3 during the period of the hazardous rip currents, suggesting their significant role in the development of the observed rip currents. Furthermore, both Rip Index from the Rip Current Monitoring and Warning System and the CCTV Score from the Rip Current Checklist exceeded threshold values during this period, reinforcing the reliability of the method used. The potential influence of bound infragravity waves on the duration and variability of these rip currents was discussed. The rip currents observed at Haeundae Beach could be categorized as the "focused" type.

Analysis of Sea Surface Temperature Variations off Wando During Summer Using Multiple Linear Regression - Sora Ahn; Byoung-Ju Choi; Jong-Kyu Kim (Ocean Science Journal, 2024)

Enhancing Backscatter Data Processing Through Sound Speed and Salinity Proxies - Moonsoo Lim; Joo Bong Jeong; Bo-Yeon Yi; Yonghee Park; Sunhee Hwang; Jeongwon Kang (Ocean Science Journal, 2024)

Effectiveness of Emergent Coastal Vegetation as a Defense System to Mitigate Debris Load on a Structure During Extreme Events - Aditya Gupta; Manasa R. Behera (Ocean Science Journal, 2024)

40-Year Journey of Shoreline Changes Along the Benin Coast Using Satellite Data Through the CASSIE Tool - Frédéric Bonou; Raïssa Christelle Madiesseu Metem; Luis Pedro Almeida; Bapentire Donatus Angnuureng; Zacharie Sohou (Ocean Science Journal, 2024)

An Optimized Method for the Simultaneous Analysis of 16 Lipophilic Marine Toxins Using LC–MS/MS with Solid-Phase Extraction Cleanup in Seafood Matrices - Sang Yoo Lee; Jong Bin Park; So Young Woo; Su Been Park; Hyun-Ki Hong; Hyang Sook Chun (Ocean Science Journal, 2024)

Sediment Organic Carbon Oxidation and Benthic Nutrient Flux in the Continental Shelf of the Southern Yellow Sea - Ju-Wook Baek; Hyun-Jeong Jeong; Jae Seong Lee; Yeonjung Lee; Hyun-Min Baek; Dong Han Choi; Jung-Ho Hyun; Hyunjin Yoon; Kee-Young Kwon; Sung-Han Kim (Ocean Science Journal, 2024)

Sea Water Turbidity Variability and Relation to Tides and Environmental Factors in the Korean Coastal Region of the Yellow Sea - Su-Ran Kim; Tae-Sung Kim; Kyung-Ae Park; Jae-Jin Park; Moon-Jin Lee; Do-Seong Byun (Ocean Science Journal, 2024)

Assimilation of Surface Geostrophic Currents in the East Sea Using the Ensemble Kalman Filter - Jae-Sung Choi; Byoung-Ju Choi; Kyungman Kwon; Gwang-Ho Seo (Ocean Science Journal, 2024)
The conventional ocean data assimilation process typically involves assimilating hydrographic data, such as temperature and salinity measurements, obtained from both satellites and in-situ observations. This study introduces a novel approach to enhance ocean circulation modeling by assimilating surface geostrophic currents derived from satellite altimetry data using the ensemble Kalman filter. To match the time scales for the variability in the observed surface geostrophic currents and the model currents, the current velocities from the model were low-pass filtered. The optimal cut-off period for the low-pass filter was determined to be 31 days in the East Sea. Eight sensitivity experiments were then conducted to examine the effects of observation error and low-pass filtering during the assimilation of surface geostrophic current data. Assimilation experiments with surface geostrophic current data improved surface currents but had minor negative impacts on the temperature and salinity when compared with assimilation experiments without surface geostrophic current data. Notably, the experiment with an observation error of 10 cm/s for the geostrophic current outperformed the other experiments. Surface geostrophic current assimilation improved the sea surface temperature during winter and effectively modified surface current patterns during autumn in the East Sea. Assimilating satellite-derived surface geostrophic currents in the ocean circulation model thus enhanced the accuracy of surface circulation simulation. This improvement in ocean analysis data offers significant benefits for understanding ocean climate change and for developing marine management strategies.

Automated System for Identifying Marine Floating Plastics to Enhance Sustainability in Coastal Environments Through Sentinel-2 Imagery and Machine Learning Models - S. Venkatraman; S. Sabarunisha Begum; K. Nithya; M. Sujatha; T. Jayasankar; N. B. Prakash; S. Srinivasan; S. Vivek (Ocean Science Journal, 2024)

Detection and Quantification of Tetrodotoxin in Marine Mud Snails, Nassarius sinarum from a Tidal Flat on the West Coast of Korea - Nobuhisa Kajino; Bong Ki Park; Hyun-Ki Hong; Jong-Seop Shin; Jeong-Hwa Kim; Jonghyub Park; Jihyun Lee; Kwang-Sik Choi (Ocean Science Journal, 2024)

Impacts of Anthropogenic Structures on Coastal Morphodynamics: A Case Study of Sand Spit Evolution in the Ujeon Tidal Flat, South Korea - Huigyeong Ryu; Hoi-Soo Jung; Joo-Hyung Ryu; Jun-Ho Lee (Ocean Science Journal, 2024)

Dynamics of Carbon Export and Lower Trophic Ecosystems: A Comparative Model Study in the Yellow Sea and Dokdo Waters - Young Shin Kwon; Hyoun-Woo Kang; Dong Han Choi; Ok Hee Seo (Ocean Science Journal, 2024)

Transport of Water Masses Through a Constricted Channel with a Sill: Possible Application to Indonesian Through-Flow - Tjipto Prastowo; Muhammad Nurul Fahmi; Arie Realita (Ocean Science Journal, 2024)

Observation of the West Korea Coastal Current in the Eastern Yellow Sea During Summer - Jae Yeob Kim; Byoung-Ju Choi; Sang-Ho Lee; Oujin Jeong (Ocean Science Journal, 2024)

Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2024)

Enhanced Chromatographic Separation for Quantitative Accuracy of Palytoxin - Young-Sang Kim; Nari Seo; Hye Won Kim; Jae Young Yu; Myung Jin Oh; Hyun Joo An; You-Jin Jeon (Ocean Science Journal, 2024)

Influence of Region-Specific Marine Environments on Phytoplankton and Bacterial Communities in the Korean Coastal Waters in Winter 2021 - Young Kyun Lim; Seongjin Hong; Chung Hyeon Lee; Mungi Kim; Seung Ho Baek (Ocean Science Journal, 2024)

Experimental Estimation of Horizontal Velocity and Vertical Structure of Floating Anticyclones Based on the Quasi-geostrophic Approximation - Cristian D. De la torre-Martínez; Raúl C. Cruz-Gómez; César O. Monzón (Ocean Science Journal, 2024)

Contribution to the Diversity of Zoanthids (Anthozoa: Hexacorallia) in the Northern Persian Gulf and Gulf of Oman - Mahsa Panahi Bazzaz; Pargol Ghavam Mostafavi; Ali Mashinchian Moradi (Ocean Science Journal, 2024)

Tissue-Specific Distribution of Tetrodotoxin (TTX) and Its Analogues in the Blue-Lined Octopus Hapalochlaena fasciata Hoyle 1886 Collected from Jeju Island, Korea using LC-MS/MS - Nobuhisa Kajino; Bong Ki Park; Hyun-Ki Hong; Hyoun Joong Kim; Jong-Seop Shin; Taeho Kim; Jihyun Lee; Kwang-Sik Choi (Ocean Science Journal, 2024)

Sea-air CO2 Flux in the South Yellow Sea Based on Seasonal Underway Observations - Dongseon Kim; Sosul Cho; Dong Han Choi (Ocean Science Journal, 2024)

Applications of Nuclear Magnetic Resonance Spectroscopy to Characterization of Marine Toxins - Hyo-Yeon Yu; Mi Gang Kim; Jin Young Kim; Yun Hwan Kim; Hyo Jin Cho; Hyeona Lim; Hyang Sook Chun; Sangdoo Ahn (Ocean Science Journal, 2024)

The Ecological Changes of Macrozoobenthos to the Sand Excavation Activities in the Southern Continental Shelf of the Korea Strait - Jin-Young Seo; Bonggil Hyun; Kyoungsoon Shin; Jin-Woo Choi (Ocean Science Journal, 2024)

Safety Management of Marine Biotoxins in South Korea: Analytical Methods, Occurrence, and Risk Assessment - Seongjin Hong; Hyun-Ki Hong; Kwang-Sik Choi (Ocean Science Journal, 2024)

Enhancing the Detection of Cyclic Imines in Marine Mollusks Using Advanced LC/MRM-MS - Nari Seo; Hye Won Kim; Jae Young Yu; Myung Jin Oh; Young Sang Kim; You Jin Jeon; Hyun Joo An (Ocean Science Journal, 2024)

Wave Climate, Sediment Transport and Shoreline Evolution in the West Littoral of Algeria - Mohammed Djili; Khoudir Mezouar; Noureddine Benaissa (Ocean Science Journal, 2024)

Predicting Underwater Photosynthetically Active Radiation (PAR) Using Random Forests in the São Sebastião Channel, Brazil - Herminio Foloni-Neto; Áurea M. Ciotti (Ocean Science Journal, 2024)

Erratum: Detection of Cyclic Imines (CIs) Toxins in Whole Body of Shellfishes: First Monitoring Report of CIs in South Korea Shellfishes - Young-Sang Kim; D. P. Nagahawatta; M. J. M. S. Kurera; H. H. A. C. K. Jayawardhana; N. M. Liyanage; D. S. Dissanayake; R. P. G. S. K. Amarasiri; Chan-Young Kim; Jun-Geon Je; Sang Gil Lee; Hee Young Jo; Hong Ju Kim; et al. (Ocean Science Journal, 2024)

Resilience-Based Assessment of Shallow Water Patchy Reefs in Palk Bay of South East Coast of India - Koushik Sadhukhan; Sudhanshu Dixit; Shunmugaraj Thimmu Reddiar; Rukmini Shekar; Ramesh Chatragadda; M. V. Raman Murthy (Ocean Science Journal, 2024)

Sea Turtles are at Risk: Unraveling the Major Threats and Conservation Challenges Encountered by Sea Turtles in Southern Sri Lanka - E. P. D. N. Thilakarathne; W. A. S. W. Lakmini; K. P. U. T. Egodauyana; Tharindu Bandara; A. B. K. M. Srimali; N. W. Ramawickrama; M. U. S. Maldeniya; A. C. W. W. M. C. L. K. Coswatte (Ocean Science Journal, 2024)

Optimal Proxy Indices for Annual Marine Heatwave Characteristics Using Monthly Sea Surface Temperature - Gyundo Pak (Ocean Science Journal, 2024)

Research on a Numerical Simulation Model of Marine Drifting Debris: A Case Study of Penghu Waters - Shyang-Chyuan Fang (Ocean Science Journal, 2024)

Diversity and Distribution Patterns of Biofouling Macrobenthos Based on the Ship Navigation Type - Si Jin Gwak; Sang Lyeol Kim; Hyung Gon Lee; Ok Hwan Yu (Ocean Science Journal, 2024)

Monitoring the Mangrove Colonization on the Uplifted Reef Beds in the North Andaman Island, India - Anoop Raj Singh; Vedagiri Thirumurugan; Nehru Prabakaran (Ocean Science Journal, 2024)

Detection of Cyclic Imines (CIs) Toxins in Whole Body of Shellfishes: First Monitoring Report of CIs in South Korea Shellfishes - Young-Sang Kim; D. P. Nagahawatta; M. J. M. S. Kurera; H. H. A. C. K. Jayawardhana; N. M. Liyanage; D. S. Dissanayake; R. P. G. S. K. Amarasiri; Chan-Young Kim; Jun-Geon Je; Sang Gil Lee; Hee Young Jo; Hong Ju Kim; et al. (Ocean Science Journal, 2024)
Cyclic imines (CIs) produced by microalgal species that accumulate in the food chains of marine organisms are novel biotoxins that do not belong to the classic group of marine biotoxins. In the past, CIs were found only in limited areas; however, in recent years, rapid changes in marine ecosystems have led to widespread CIs and increased exposure to toxic risks. In this study, we analyzed seven CI toxins, GYM-A, SPX (13-desmethyl spirolide C, 13, 19-dideMe spirolide C, 20-methyl spirolide G), and PnTX-E, F, and G, using LC/MRM-MS. Shellfish samples were purchased from a domestic Korean fish market (67 samples in 2021 and 216 samples in 2022). The entire body of the shellfish was ground and extracted with 50% methanol, followed by lipophilic-specific SPE. Only GYM-A, PnTX-G, and 13-desmethyl spirolide C were detected in all analyzed samples. The maximum concentrations of GYM-A is maximum 179 ppt (ng/kg) in Crassostrea nippona (March 2022), PnTX-G is maximum 7 ppt in Anadara broughtonii (April 2022), 13-desmethyl SPX C is maximum 58 ppt in Crassostrea nippona (April 2022). The southern coast exhibited the highest frequency of detection of these toxins, which was attributed to elevated sea-surface temperatures, aligned with conducive conditions for toxin-producing phytoplankton. According to the monitoring results, there were no significant CI toxins in the shellfish; however, it is important to monitor CI toxin accumulation in shellfish because of their high risk of toxicity.

Coral Communities Distribution in the Context of Site’s Reef Formation Type in Wakatobi National Park, Indonesia - Karizma Fahlevy; Budi Prabowo; Nurul Wahidah Q. Manik; Paul G. Carvalho; Austin T. Humphries; Beginer Subhan; Hawis Madduppa (Ocean Science Journal, 2024)

Analysis of Unmatched Fishing Activities Between VIIRS and Field Data (AIS and V-Pass) Around Korean Peninsula - Boram Lee; Yoon-Kyung Lee; Sang-Wan Kim (Ocean Science Journal, 2024)

Assessment of Maritime Vessel Detection and Tracking Using Integrated SAR Imagery and AIS/V-Pass Data - Yoon-Kyung Lee; Hahn Chul Jung; Keunyong Kim; Yeongjae Jang; Joo-Hyung Ryu; Sang-Wan Kim (Ocean Science Journal, 2024)

Origin of Subaqueous Dunes on a Flat-topped Seamount, Dokdo in the East (Japan) Sea, Korea - Soo-Jin Kim; Jang-Jun Bahk; Chang Hwan Kim; Young Kwan Sohn; Chan Hong Park (Ocean Science Journal, 2024)

Annual Reproductive Phenology and Condition Index of Blood Cockle Tegillarca granosa (L., 1758) Collected from the West Coast of Moheshkhali Island, Cox’s Bazar, Bangladesh - M. Jasim Uddin; Afroza Yesmin Aleya; Nusrat Zahan; Chaity Paul; Selina Yeasmine (Ocean Science Journal, 2024)

Assessing the Impact of Habitat Fragmentation on the Distribution of Juvenile and Larval Sillago Species in the Ka Long Estuary Located in Northern Vietnam - Anh Ngoc Thi Do (Ocean Science Journal, 2024)

Chronic Effects of Waterborne Silver on the Physiology and Reproduction of the Manila Clam Ruditapes philippinarum - Xiang-Lan Yu; Hyun-Ki Hong; Kwang-Sik Choi; Jihyuk Kim; Byeong-Gweon Lee (Ocean Science Journal, 2024)

Do Sea Surface Winds and Currents in the Equatorial Pacific Ocean Derive the Extreme El Niños? - Seongsuk Lee; Yu Yi; Yun Gon Lee (Ocean Science Journal, 2024)
El Niño is the largest natural climate variability event on an interannual time scale occurring in the equatorial Pacific Ocean, and is linked to global climate change. The north equatorial countercurrent (NECC) is considered a significant feature of the tropical Pacific current system due to its location and eastward flow direction. The NECC has been suggested as a current that transports the warmer western Pacific waters to the eastern Pacific to trigger the El Niño event in the equatorial Pacific. We investigated how the movements of zonal wind stress (ZWS) and ocean surface currents (OSC) contribute to the sea surface temperature (SST) changes during the El Niño period. During moderate to severe Central Pacific El Niño events, the continuous flow of the NECC extending from the El Niño monitoring region into the eastern Pacific is rarely observed. In addition, a significant increase in ocean heat content compared to the 27-year climatological normal has been identified at temperatures above 28 °C. Therefore, we propose a hypothesis that the additional heat is supplied from the subsurface source and the warm pool is expanded by the subsurface equatorial countercurrent, known as the Equatorial Undercurrent, rather than by the surface currents. The heated water is expected to contribute to the evolution of El Niño by upwelling to the surface along the equator in a north–south symmetric feature.

High Spatial Variability in Under-Ice Export Fluxes over the Chukchi Plateau in the Pacific Arctic Region - Catherine Lalande; Jong-Kuk Moon; Jinyoung Jung; Eun Jin Yang (Ocean Science Journal, 2024)

Erratum: Trends of Satellite-Derived Thermal Fronts in the Southeast and Southwest of Australia Between 1993 and 2019 - Kai Yang; Andrew M. Fischer; Pallavi Govekar (Ocean Science Journal, 2024)

Dinoflagellate Cyst Assemblage, Abundance and Distribution in Three Estuaries in Bone Bay, South Sulawesi, Indonesia - Nita Rukminasari; Sapto Andriyono; Andi Aliyah Hidayani (Ocean Science Journal, 2024)

Preliminary Estimation of Protist Predation Potential on Picoplankton in Summer of the Yellow Sea - Young-Ok Kim; Mutsuo Ichinomiya; Jungmin Choi; Dong Han Choi; Wonseok Yang; Kyung-Hee Oh; Kongtae Ra; Howon Lee (Ocean Science Journal, 2024)

Significant Reduction of Photosynthesis in the Harmful Dinoflagellate Margalefidinium polykrikoides by Co-culturing with the Marine Green Alga Tetraselmis suecica - Han-Sol Kim; Buhari Lawan Muhammad; Jang-Seu Ki (Ocean Science Journal, 2024)

Feasibility of Ship Detection and Tracking Using GOCI-II Images - Yeongjae Jang; Keunyong Kim; Won-Kyung Baek; Jae-Hyun Ahn; Joo-Hyung Ryu (Ocean Science Journal, 2024)

Essential Elements in Muscle Tissue of Rhizoprionodon acutus and Sphyrna lewini from West Java Waters - Suratno Suratno; Satriyo K. Wahono; Dwi Siswanta; Nurul H. Aprilita (Ocean Science Journal, 2024)

Trends of Satellite-Derived Thermal Fronts in the Southeast and Southwest of Australia Between 1993 and 2019 - Kai Yang; Andrew M. Fischer; Pallavi Govekar (Ocean Science Journal, 2024)
Oceanic fronts play a significant role in marine ecosystems by enhancing vertical exchange, promoting the aggregation of plankton, and drawdown of organic carbon. Anthropogenic emission of carbon dioxide and other greenhouse gases in the twentieth century has driven global warming, leading to rising ocean temperatures. Specific regions warming faster than the global average—known as ‘ocean warming hotspots’—have been identified, impacting geophysical and biogeochemical dynamics of local ecosystems. Here, we aim to characterize the variability of sea surface temperature (SST) fronts in the southeast and southwest Australia hotspots. Using a histogram frontal detection method, we derived fronts from AVHRR-only and Multi-sensor 6-day SST composites on a 0.02 × 0.02 grid between January 1993 and December 2019. Our results indicate that frontal frequency and frontal density have increased in both regions in the past three decades, by around 0.2–0.3%. In addition, both regions exhibit higher frequency and density of fronts in austral winter and fewer in austral summer. Our calculations show that changes in frontal frequency/density show some relationship to El Niño-Southern Oscillation and Indian Ocean Dipole. Changes in frontal activity could strongly impact local ocean biogeochemistry and marine ecosystems. A better understanding changing fronts in hotspots will help predict and manage future changes in regional oceans to warming.

Distribution of REY-Rich Mud in Deep-Sea Sediments from the Magellan Seamount Trail Zone in the Northwestern Pacific - Jongmin Lee; Mun Gi Kim; Kiseong Hyeong (Ocean Science Journal, 2024)

Temporal and Spatial Distribution of Invasive Ctenophore Mnemiopsis leidyi in the Southern Part of the Caspian Sea from 2019 to 2020 - Reza Rahnama Haratbarr; Jafar Azizpour; Ahmad Manbohi; Kazem Darvish Bastami; Ali Hamzehpour; Ali Mehdinia; Mehrshad Taheri (Ocean Science Journal, 2024)

Physiological Impacts of CO2-Induced Acidification and UVR on Invasive Alga Caulerpa racemosa - Gamze Yildiz (Ocean Science Journal, 2024)

A Study on Ship Detection and Classification Using KOMPSAT Optical and SAR Images - Kwang-Jae Lee; Seung-Jae Lee; Jae-Young Chang (Ocean Science Journal, 2024)

Erratum: Path Prediction for Fishing Boats Using Attention-Based Bidirectional Gated Recurrent Unit - Sang-Lok Yoo; Kyounghoon Lee; Won-Kyung Baek; Kwang-Il Kim (Ocean Science Journal, 2024)

Monitoring Maritime Ship Characteristics Using Satellite Remote Sensing Data from Different Sensors - Won-Kyung Baek; Euihyun Kim; Ho-Kun Jeon; Kwang-Jae Lee; Sang-Wan Kim; Yoon-Kyung Lee; Joo-Hyung Ryu (Ocean Science Journal, 2024)

Evaluation of Ecosystem Services Provided by Pacific Oyster, Crassostrea gigas, Farms in Hansan Bay, Korea - Jongyoon Baek; Seonggil Go; Jungho Nam; Kwang-Sik Choi; Sukgeun Jung (Ocean Science Journal, 2024)

Substrate Characteristics Determine the Distribution and Abundance of Reef and Reef-Associated Fish: A Comprehensive Study in Protected and Non-protected Coral Ecosystems of Sri Lanka - M. S. V. H. Priyashadi; E. M. A. P. Edirimanna; Sachithra Amarin Hettiarachchi; K. H. M. Ashoka Deepananda (Ocean Science Journal, 2024)

Utilizing Room-Temperature Ionic Liquids in the Analysis of Volatile Hazardous and Noxious Substances in Marine Sediments - Hyeonju Jung; Mingu Kang; Junhyeong Park; Na Yeong Kim; Gi Beum Kim (Ocean Science Journal, 2024)

Analysis of the Effects of Minimum Capture Size Limits on Changes in the Biomass and Fishing Profits of Sandfish, Arctoscopus japonicus, in Korean Waters - Sung Il Lee; Do-Hoon Kim; Se Hyun Song; Chang Ik Zhang (Ocean Science Journal, 2024)

Path Prediction for Fishing Boats Using Attention-Based Bidirectional Gated Recurrent Unit - Sang Lok Yoo; Kyounghoon Lee; Won Kyung Baek; Kwang Il Kim (Ocean Science Journal, 2024)

The Annual Reproductive Cycle and Reproductive Effort of the Pacific Oyster Crassostrea gigas from a Tidal Flat in Incheon Bay on the West Coast of Korea - Hee-Jung Lee; Hye-Mi Lee; Hyun-Ki Hong; Young Baek Hur; Kwang-Sik Choi (Ocean Science Journal, 2024)

Spatio-Temporal Variation in Perkinsus olseni Infection Intensity in Manila Clam Ruditapes philippinarum in Anmyeondo and Cheonsu Bay Tidal Flats on the West Coast of Korea - Thatchaneshkanth Subramaniam; Young-Ghan Cho; Hye-Mi Lee; Jeong-Hwa Kim; Jong-Seop Shin; Mun-Gyeong Kwon; Gwang-Il Jang; Kwang-Sik Choi (Ocean Science Journal, 2024)

Characteristics of Plastic Debris Ingested by Sea Turtles: A Comprehensive Review - Yelim Moon; Won Joon Shim; Sang Hee Hong (Ocean Science Journal, 2023)
Sea turtles, an ecologically vital marine species, face the mounting threat of plastic ingestion. To devise effective mitigation strategies, a nuanced understanding of the characteristics of ingested plastics is essential. Previous reviews have predominantly concentrated on the frequency of occurrence (%FO) and quantity of ingested plastics. In this study, we present an update to the literature on %FO and quantity of ingested plastics and also introduce a novel review of the morphology, color, and polymer composition of ingested plastics. This analysis draws upon 110 scholarly articles on plastic ingestion by sea turtles. Additionally, we explore geographical variations in both the quantity and characteristics of ingested plastics. Most of the analyzed studies were conducted in the Americas and Europe. We found that approximately 54% of examined sea turtles had ingested plastic debris. Loggerhead sea turtles ingested more foams than green sea turtles (Wilcoxon rank-sum test, p < 0.05). By contrast, green sea turtles exhibited a higher ingestion on films (Wilcoxon rank-sum test, p > 0.05). Our study also underscored the paucity of data regarding the original usage of ingested plastics. White and transparent plastics were most commonly ingested. Additionally, polymers with a lower density than seawater, such as polyethylene, polypropylene, and their copolymers, were frequently found. We strongly advocate for future studies to furnish more comprehensive data regarding the ingested plastics, including quantities, morphological and chemical properties, and origins. Such detailed information is indispensable for shaping well-informed and effective strategies to combat plastic ingestion in marine life.

Distribution and Abundance of Intertidal Sponge (Porifera) Communities in Coral Reefs of Singapore - Shu Feng Lim; Lik Tong Tan; Beverly Pi Lee Goh (Ocean Science Journal, 2023)
Given the important functional roles of sponges in the coral reef community, few studies have looked at sponge community assemblages in Singapore. This study was conducted to assess the sponge diversity, species richness, and species abundance of intertidal sponge communities in Singapore’s coral reefs, including Pulau Hantu, P. Subar Laut, Tanjong Rimau, and Labrador Park. Belt transects measuring 10 m by 1 m were established to survey the sponge communities at these reef sites. Based on sponge morphology, a total of 28 morphospecies were identified, belonging to eight different sponge orders, namely Chondrillida, Clionaida, Dictyoceratida, Haplosclerida, Poecilosclerida, Suberitida, Tetractinellida, and Verongiida. Univariate statistical analyses revealed that sponge diversity, species richness, and abundance at P. Hantu site 2 were significantly higher than that in Labrador Park. In addition, multivariate statistical analyses showed that in terms of community structure, there were three distinct clusters found at P. Hantu site 2, Labrador Park, and P. Subar Laut. The formation of these distinct clusters was sponge species specific and shaped by environmental factors and anthropogenic stresses. Preliminary sponge data presented in this study contribute to the regional biogeography of sponges and could serve as baseline data for future studies, including ecological research and biomonitoring of marine invertebrates, and support marine conservation efforts in Singapore.

Movability Number as the Parameter of Sediment Incipient Motion: A Mathematical Approach - Aamer Majid Bhat; Manzoor Ahmad Ahanger; Pranab Kumar Mohapatra (Ocean Science Journal, 2023)

A Comprehensive Investigation of Coastal and Shelf Sediment Sources in the South Sea of Korea: A Marginal Sea of the Northwestern Pacific - Dhongil Lim; Yeong-Gil Cho; Dohyun Jeong; Jihun Kim; Zhaokai Xu; Taesoo Chang (Ocean Science Journal, 2023)

Development and Benchmarking of the Shallow Shelf Approximation Ice Sheet Dynamics Module - Yi-Jeong Baek; Su-Jeong Lim; Byung-Dal So (Ocean Science Journal, 2023)

Assessing the Potential Marine Environmental Impacts of Heavy Metal Leaching from Ship Cleaning Residues - Je Hyeok Kang; Hyeonju Jung; Na Yeong Kim; Moonkoo Kim; Gi Beum Kim (Ocean Science Journal, 2023)

Exploring Rearing Water Temperature Conditions for Inducing Body Growth without Water Temperature Stress in Red-Spotted Grouper (Epinephelus akaara) - Byeong-Hoon Kim; Sung-Pyo Hur; Song-Hee Choi; Young-Don Lee; Chi-Hoon Lee (Ocean Science Journal, 2023)

Phase Shift in Vertical Distribution of Macroalgal Assemblages on Udo Islet, Jeju, Korea, After a Decade of Revisiting - Jeong Chan Kang; Hyung Woo Lee; Young Wook Ko; Myung Sook Kim (Ocean Science Journal, 2023)

Trace-Metal-Clean Sampling System: Application to Ice-Breaking Research Vessel Araon - Jiwoo Kim; Hunsub Sim; Ijin Lim; Taejin Kim; Jinyoung Jung; Kyoung-Ho Cho; Tae-Wan Kim; Jisoo Park; Eun Jin Yang; Xiaoyu Chen; Hojong Seo (Ocean Science Journal, 2023)

Spatial Patterns of the Primorye Current in the Northwestern East/Japan Sea on Satellite Images and Standard Sections - Aleksandr A. Nikitin; Irina L. Tsypysheva; Yury I. Zuenko (Ocean Science Journal, 2023)

Short-Term Exposure to Combined Condition of Low Salinity and pH Affects ROS-Mediated Stress in Disk Abalone (Haliotis discus hannai) - Min Ju Kim; Gyung-Suk Kil; Young-Su Park; Cheol Young Choi (Ocean Science Journal, 2023)

Spatial Variation Ecological Quality Assessment of Live and Dead Molluscan Assemblages in the Aegean Sea - Herdem Aslan; Panayotis Ovalis (Ocean Science Journal, 2023)

Estimation of Size-Dependent Mortality of Chub Mackerel (Scomber japonicus) Based on Their Fecundity - Seonggil Go; Sukgeun Jung (Ocean Science Journal, 2023)

Non-conservative Characteristics of Seawater Calcium Ion in Offshore Aquaculture Areas: A Case Study in the Muping Marine Ranch, Yantai, China - Zhe Zhang; Hai-Zhen Bian; Yu-Bin Hu (Ocean Science Journal, 2023)

Use of Autonomous Reef Monitoring Structures to Monitor Changes in the Marine Environment in Jeju, South Korea: A Brief Review - Hyun-Sung Yang; Taihun Kim; Kyeong-Tae Lee; Taeho Kim; David M. Baker; Do-Hyung Kang (Ocean Science Journal, 2023)

Current Status of Coral Reef Fish Abundances at Pulau Bidong and Nearby Islands, South China Sea Using Stereo-Diver Operated Video System - Aminudin Muhammad Afiq-Firdaus; Che Din Mohd Safuan; Suhaidi Shafie; Lila Iznita Izhar; Ezmahamrul Afreen Awalludin; Muhammad Faiz Ahmad; Nur Arbaeen Mohd Johari; Zainudin Bachok (Ocean Science Journal, 2023)

Branched GDGT in the Hupo Trough (Southwestern East Sea) as a Record of the Terrestrial Climate Change in East Asia Since the Last Glacial Maximum - Yu-Hyeon Park; Boo-Keun Khim (Ocean Science Journal, 2023)

In Vivo Culture Study of Free-Living Marine Nematodes (Bathylaimus sp., Oncholaimus sp., Oncholaimellus sp.) Inhabiting West Coast Mallipo, Korea - Ayoung Shin; Dongsung Kim; Teawook Kang; Je Hyeok Oh; Chul-Woong Oh (Ocean Science Journal, 2023)

Seasonal Variability of Marine Fish Diversity in Relation to Water Quality of East Midnapore Coast of West Bengal, India - Deep Sankar Chini; Niladri Mondal; Avijit Kar; Ingrid Bunholi; Sourav Singh; Pratik Ghosh; Prasanta Patra; Shampa Patra; Bidhan Chandra Patra (Ocean Science Journal, 2023)

Sedimentary Records of the Dramatic Environmental Changes in the Lingdingyang Bay of the Pearl River Estuary in Southern China - Weizhu Zeng; Zhaoyong Zheng; Cuiping Zhang; Peng Zhou (Ocean Science Journal, 2023)

Microbial Diversity of Deep-sea Sediments from Three Newly Discovered Hydrothermal Vent Fields in the Central Indian Ridge - Teddy Namirimu; Mi-Jeong Park; Yun Jae Kim; Dhongil Lim; Jung-Hyun Lee; Ayoung Shin; Dongsung Kim; Kae Kyoung Kwon (Ocean Science Journal, 2023)

A Data-Driven Binary-Regression Framework for Rapid Screening of Marine Fuel Oil - Andrew Loh; Un Hyuk Yim (Ocean Science Journal, 2023)

Biometrical Variation of Posidonia oceanica with Different Bottom Types Along the Entire Turkish Mediterranean Coast - Erhan Mutlu; Güler Sıla Duman; Doğukan Karaca; Yaşar Özvarol; Ahmet Şahin (Ocean Science Journal, 2023)

Fluid Mud Dynamics and Its Correlation to Hydrodynamics in Jiaojiang River Estuary, China - Li Li; Jiachen Wang; Yiqun Zheng; Yanming Yao; Weibing Guan (Ocean Science Journal, 2023)

Influence of Nutrient Gradient on Phytoplankton Size Structure, Primary Production and Carbon Transfer Pathway in a Highly Productive Area (SE Mediterranean) - Oumayma Chkili; Marouan Meddeb; Kaouther Mejri Kousri; Sondes Melliti Ben Garali; Nouha Makhlouf Belkhahia; Marc Tedetti; Marc Pagano; Amel Belaaj Zouari; Malika Belhassen; Nathalie Niquil; Asma Sakka Hlaili (Ocean Science Journal, 2023)

A Biological Indication of Vertical Mixing of the Yellow Sea Bottom Cold Water - Young Ok Kim; Jungmin Choi; Dong Han Choi; Kyung-Hee Oh (Ocean Science Journal, 2023)

Chemical Speciation of Dissolved Copper in the Nakdong River Estuary and Its Relationship with Humic-Like Fluorescent Dissolved Organic Matter - Hunsub Sim; Ijin Lim; Jumi Kim; Jiwoo Kim; Jong-Sik Ryu; Jun-Ho Lee; Hyung-Mi Cho; Heejun Han; Hojong Seo; Taejin Kim (Ocean Science Journal, 2023)

Effects of Hydrodynamic Disturbance on Vegetation Development in Coastal Salt Marshes: A Model Study in Jiangsu, China - Zhipeng Chen; Feng Luo; Jingwei Zeng; Jiancheng Dai; Guanghuai Zhou; Ruijie Li (Ocean Science Journal, 2023)

Sea Surface Temperature and Phytoplankton Abundance as Crucial Proxies for Green Noctiluca Bloom Monitoring in the Northeastern Arabian Sea: A Case Study - Nittala S. Sarma; Sanjiba Kumar Baliarsingh; Aneesh Anandrao Lotliker; Sudarsana Rao Pandi; Alakes Samanta; Suchismita Srichandan (Ocean Science Journal, 2023)

Estimating Bed Shear Stress Distribution over Bottom of a Channel on the Moving Vessel - Dong Hyeon Kim; Jin Hwan Hwang (Ocean Science Journal, 2023)

Sea Urchin Removal and Effectiveness Evaluation from the Long-Term Monitoring Data in Dokdo, Korea - Su-Young Jeong; Sungtae Kim; Chae-Lin Lee; Gyusang Kang; Jungsoo Kim; Chang-Soo Kim; Seokjin Yoon; Kangseok Hwang; Jae-Won Yoo (Ocean Science Journal, 2023)

Gulf of Urabá (Caribbean Colombia), a Tropical Estuary: A Review with Some General Lessons About How it Works - Sebastián Contreras-Fernández; Lennin Florez-Leiva; María Camila Bernal-Sánchez; Wilberto Pacheco-Paternina; Shalenys Bedoya-Valestt; Lorenzo Portillo-Cogollo (Ocean Science Journal, 2022)

Meiofauna and Nematode Community Composition in Maxwell Bay, King George Island, Antarctica - Teawook Kang; Kyu-Cheul Yoo; Dongsung Kim (Ocean Science Journal, 2022)

Numerical Study of Influencing Factors on Tidal Wave Propagation in the Persian Gulf - S. Mahya Hoseini; Mohsen Soltanpour (Ocean Science Journal, 2022)

Sub- and Marine Mediterranean Basin Antimicrobial Resistance and Environmental Concerns: A Case Study of Tunisia - Bilel Hassen; Monia El Bour (Ocean Science Journal, 2022)

Influence of the Cape Angle and Flow Speed on Eddy Formation and Detachment: Experimental Results and Comparison with North Brazil Current Eddies - Raúl C. Cruz-Gómez; Julio Salcedo-Castro (Ocean Science Journal, 2022)

Erratum to: Spatio-Temporal Variation of the M2 Tidal Current from Field Observations in the Jeju Strait - Kyu‑Min Song; Dawoon Jung; Kyung-Hee Oh; Chang-Woong Shin; Young-Heon Jo; Byoung-Ju Choi; Jae-Il Kwon; Seok Lee (Ocean Science Journal, 2022)

Reproductive and Growth Parameters of the Razor Clam, Cultellus maximus (Gmelin, 1791), in Southern Vietnam - Quan T. Lai; Vu Anh Tuan; Dinh Kim Dieu; Alexander B. Orfinger; Ngo Minh Ly; Nguyen Thanh Ha; Trinh Truong Giang (Ocean Science Journal, 2022)

Estimation of Potential Habitats for Three Species of Bivalves Using the Habitat Variables in Gomso Bay Tidal Flat, Korea - Seung Ryul Zeon; Jun-Ho Koo; Jong-Woo Park; Hee-Do Jeung; Yong Hyeon Choi; Yoonsik Cho (Ocean Science Journal, 2022)

Comparing Environmental DNA Metabarcoding and Underwater Visual Census to Monitor Korean Coastal Fish Community - Yong-Deuk Lee; Gang-Min Lee; Jong-Yul Park; Woo-Seok Gwak (Ocean Science Journal, 2022)

Spatio-Temporal Variation of the M2 Tidal Current from Field Observations in the Jeju Strait - Kyu‑Min Song; Dawoon Jung; Kyung-Hee Oh; Chang-Woong Shin; Young-Heon Jo; Byoung-Ju Choi; Jae-Il Kwon; Seok Lee (Ocean Science Journal, 2022)

Study of Shoreline Changes Through Digital Shoreline Analysis System and Wave Modeling: Case of the Sandy Coast of Bou-Ismail Bay, Algeria - Said Kaddour; Yacine Hemdane; Nasser Kessali; Khalid Belabdi; Miloud Sallaye (Ocean Science Journal, 2022)

Estimation of Seasonal Representation of the Sea Water Temperature Profile Using Machine Learning and Its Effect on the Prediction of Underwater Acoustic Detection Performance - Nayoung Park; Young-Gyu Kim; Kyeong Ok Kim; Su-Uk Son; JongJin Park; Young Ho Kim (Ocean Science Journal, 2022)

Effects of Light, Salinity and Temperature on Germination Characteristics of Surfgrass, Phyllospadix japonicus and P. iwatensis Seeds - Jung-Im Park; Jae Hoon Kim; Hwi-June Song; Gu Yeon Kim (Ocean Science Journal, 2022)

Monsoon-Driven Geomorphological Changes Along the West Coast of Sri Lanka: A Combined Approach Utilizing ‘CoastSat’ and Google Earth Engine - Gunasinghage Prasadh Gunasinghe; Nalin Prasanna Ratnayake; Amila Sandaruwan Ratnayake; G. V. I. Samaradivakara; Nimila Praneeth Dushyantha; Ravindra Jayaratne; Kodithuwakka Arachchige Dinusha; Akalanka Silva (Ocean Science Journal, 2022)

Multi-proxy Stratigraphy and Paleoceanographic Variations in Sediment from the Korea Plateau, East Sea (Japan Sea), Over the Last 500 kyr - Sangmin Hyun; Jin-Kyung Kim; Jeongwon Kang; Gil Young Kim (Ocean Science Journal, 2022)

Seasonal Growth Dynamics of Posidonia oceanica in a Pristine Mediterranean Gulf - Erhan Mutlu; Cansu Olguner; Mehmet Gökoğlu; Yaşar Özvarol (Ocean Science Journal, 2022)

Current Structure and Volume Transport in the Jeju Strait Observed for a Year with Multiple ADCP Moorings - Chang-Woong Shin; Hong Sik Min; Seok Lee; Hyoun-Woo Kang; Bonhwa Ku; Dong Guk Kim; Joonseong Park; Soonyeol Kwon; Byoung-Ju Choi (Ocean Science Journal, 2022)

Abandoned, Lost and Discarded Fishing Gear from the Fishing Sector of Kerala, India - Damaris Benny Daniel; Saly N. Thomas (Ocean Science Journal, 2022)

Dissolved Pb Concentrations and Stable Pb Isotope Ratios in the Ulleung Basin, East/Japan Sea - Seonghu Choi; Man-Sik Choi; Dongjin Joe; Sojung Park; Jinwoo Kim; Kongtae Ra; Intae Kim; Kyung-Tae Kim; Kyoung-Seok Lee; Jean-Sun Lim (Ocean Science Journal, 2022)

The First Recorded Occurrences and the Distribution of Physalia physalis (Hydrozoa: Physaliidae) in Algerian Waters - Samir Bachouche; Tarek Ghribi; Samir Rouidi; Mohamed Etsouri; Yasmine Belkacem; Rabah Selmani; Mostapha Djellali; Raouf Hadj Aissa; Samir Grimes (Ocean Science Journal, 2022)

Evolution and Sedimentation Mechanisms of Estuarine Beach in the Nakdong River Estuary, Korea: Natural and Human Impact - Joo Bong Jeong; Hoi-Soo Jung; Jun-Ho Lee; Kyung Kyu Park; Seok Yun Kim; Han Jun Woo (Ocean Science Journal, 2022)

Progress in the Industry-University-Institute Cooperative Use of Research Vessels - Jae Hak Lee (Ocean Science Journal, 2022)

New Opportunities in Global Ocean Research for Academia and Industry - Sang-Mook Lee (Ocean Science Journal, 2022)
Since 2017, requesting ship time has become possible for university researchers and businesses on research vessels. They include Isabu and Onnuri of the Korea Institute of Ocean Science and Technology (KIOST) and the icebreaking research vessel Araon of the Korea Polar Research Institute (KOPRI). There was no regulation barring the chartering of the significant national scientific infrastructure in the first place, but the exorbitant cost of ship time had made their usage virtually impossible. Shared Use Committee (SUC) was set up to handle applications and coordinate the cruises. A modest amount of research funds is also granted. Currently, the KIOST vessels conduct surveys in the Pacific and the central Indian Ocean annually. The KOPRI vessel routinely operates around Antarctica during the austral summer and in the Arctic seas during the boreal summer. Other government-supported institutions are likely to follow this shared used example. Here I provide a brief historical background leading to the shared use of research and information for potential applicants. The description is given from the perspective of geological oceanography, and thus some accounts may differ in other fields of study. A case study is given where a team of international university scientists successfully conducted a joint experiment to investigate the upper mantle structure by deploying ocean bottom instruments and recovering them one year later in the Pacific using Korean research vessels. Finally, some long and short-term recommendations are made to improve the system further.

Suppressed Upwelling Events in the Seychelles–Chagos Thermocline Ridge of the Southwestern Tropical Indian Ocean - Eunsun Lee; Chanmi Kim; Hanna Na (Ocean Science Journal, 2022)
A prominent subsurface upwelling over the Seychelles–Chagos Thermocline Ridge (SCTR) in the southwestern tropical Indian Ocean is suppressed when downwelling Rossby waves propagate from the eastern Indian Ocean during the positive phase of the Indian Ocean Dipole (IOD) or El Niño periods. Recent studies have suggested that the upwelling can be further suppressed during the co-occurrence years of positive IOD and El Niño, associated with the strong easterly wind anomalies in the eastern Indian Ocean. This study examines the temporal variations in the SCTR upwelling strength during 1968–2017, identifies strong upwelling suppression events, and analyzes their characteristics by focusing on the role of both remote and local wind forcing, not limited to the remote influence linked to the IOD and the El Niño Southern Oscillation. A total of nine events were identified for the 50-year period, with seven of them occurring 3–6 months after the co-occurring peaks of positive IOD and El Niño in the eastern Indian Ocean. However, only IOD exhibited a positive phase before the 2011–2012 suppression event associated with the downwelling-favorable anticlockwise local wind anomalies in the SCTR. Moreover, the 1978–1979 suppression event was primarily caused by the strong anticlockwise wind anomalies in the SCTR, without any significant influence of the positive IOD or El Niño. The results suggest that the role of local winds, as well as the remote forcing, are significant in the upwelling suppression over the SCTR, which would contribute to understanding the potential predictability of the upwelling variations.

Influence of Sea Surface Fluctuation on Internal Waves’ Vertical Structures in a Two-Layer Model - Dongling Zhang; Yufei Zhang; Xu Lu; Ming Zhang (Ocean Science Journal, 2022)

Unusual Mass Appearance of Salpa fusiformis (Thaliacea: Salpida) in Early Spring at a Nuclear Power Plant at Mid-western Boundary of the East Sea - Wonduk Yoon; Byoung-Ju Choi; Hyunsu Yoo; Byeongho Kim; Youngwook Bok; Jinho Chae (Ocean Science Journal, 2022)

Status, Biodiversity, and Ecosystem Services of Seagrass Habitats Within the Coral Triangle in the Western Pacific Ocean - Abdulla- Al-Asif; Abu Hena Mustafa Kamal; Hadi Hamli; Mohd Hanafi Idris; Geoffery James Gerusu; Johan Ismail; Md Khurshid Alam Bhuiyan; Muyassar H. Abualreesh; Najiah Musa; Mohd Effendy Abd Wahid; Manoranjan Mishra (Ocean Science Journal, 2022)

Application of a Length-Based Stock Assessment Model for the Chub Mackerel (Scomber japonicus) in Korean Waters - Jinwoo Gim; Saang-Yoon Hyun (Ocean Science Journal, 2022)

Effect of Different pCO2 Concentrations in Seawater on Meiofauna: Abundance of Communities in Sediment and Survival Rate of Harpacticoid Copepods - Je Hyeok Oh; Teawook Kang; Ayoung Shin; Taewon Kim; Ok Hwan Yu; Wonchoel Lee; Dongsung Kim (Ocean Science Journal, 2022)

Optimized Metavirome Analysis of Marine DNA Virus Communities for Taxonomic Profiling - Kang Eun Kim; Seung Won Jung; Joon Sang Park; Hyun-Jung Kim; Cholyoung Lee; Sun-Yong Ha; Taek-Kyun Lee (Ocean Science Journal, 2022)

Decadal Variability of Satellite-Derived Air–Sea CO2 Flux in Southwestern Part of the Bay of Bengal - Ramalingam Shanthi; Durairaj Poornima; Thirunavukarasu Thangaradjou; Ayyappan Saravanakumar; Saroj B. Choudhury; Rajdeep Roy (Ocean Science Journal, 2022)

Microstructure of Antarctic Krill (Euphausia suberba) Cuticle - Yuanhuai Peng; Wei Ji; Hongwu Ji (Ocean Science Journal, 2022)

Temporal Variations in the Antifouling Activity of Extract of the Soft Coral Sarcophyton trocheliophorum Collected from the Red Sea - Sathianeson Satheesh; Mohammad Abulaziz Ba-Akdah (Ocean Science Journal, 2022)

Calibration of the XRF-Estimated CaCO3 Content in the Western Tropical Pacific Deep-Sea Sediments - Il Taek Lee; Tae Wook Ko; Kyung Eun Lee; Si Woong Bae; Gyu Chan Hwang; Ryoung Ah Kim (Ocean Science Journal, 2022)

Evaluation of Sea Surface Temperature-Dependent Whitecap Coverage Parameterizations Using In Situ Data - Min Liu; Bailin Yang (Ocean Science Journal, 2022)

Bioaccumulation of Trace Metals in Sabellaria alveolata (Annelida: Polychaeta) and Their Controlling Factors Along the Essaouira Protected Coastal Area (Atlantic Coast of Morocco) - Nor-eddine Chouikh; Patrick Gillet; Mohamed Cheggour; Abdelmalek Maarouf; Youssef El Hachimi; Abdelaziz Mounir; Hassan Alahyane; Abdelfattah Mouabad (Ocean Science Journal, 2022)

Enhancement of Sea Surface Chlorophyll a Concentration by Interaction of Winds and Currents in a Cyclonic Eddy in the Japan/East Sea - Dong-Kyu Lee; Gi-Hoon Hong; Dong-Beom Yamg; Young-Il Kim; Min Seung-Hwan (Ocean Science Journal, 2022)

Origin of the Holocene Sediments in the Ninetyeast Ridge of the Equatorial Indian Ocean - Inah Seo; Boo-Keun Khim; Hyen Goo Cho; Youngsook Huh; Jongmin Lee; Kiseong Hyeong (Ocean Science Journal, 2022)

Seasonal Fluctuations in the Abundance of Marine Tardigrades (Heterotardigrada: Echiniscoides sigismundi, Styraconyx haploceros) Inhabiting Fistulobalanus albicostatus, an Intertidal Barnacle on the West Coast of Korea - Yu Na Choi; Hyung Seop Kim; Soo-Gun Jo (Ocean Science Journal, 2022)

Deep-Water Circulation over the Last Two Glacial Cycles Reconstructed from Authigenic Neodymium Isotopes in the Equatorial Indian Ocean (Core HI1808-GPC04) - Sunhwa Bang; Youngsook Huh; Boo-Keun Khim; Hiroyuki Takata; Minoru Ikehara; Kiseong Hyeong; Inah Seo; HyenGoo Cho (Ocean Science Journal, 2022)
We reconstructed the past deep-water character of the equatorial Indian Ocean using the isotope ratio of neodymium ( ε Nd ) in the Fe–Mn coating of mixed-species foraminifera. When compared with previous ε Nd records at the same site (ODP 758) and at another site to the west (SK 129), the three datasets were consistent and showed glacial-interglacial variations, even though the other two records were extracted from different media (cleaned foraminifera and bulk sediment leach). This confirms that while the foraminiferal coating is the preferred medium for reconstructing past bottom water ε Nd records, for carbonate-dominated lithologies, weak acid extraction of bulk sediment is also a viable option offering high-resolution capabilities. When the lithology includes volcanic particles or high organics, the extraction protocol may need to be adjusted to guard against detrital contamination or a slight correction may need to be applied. During glacials, the deep waters bathing the equatorial Indian Ocean had a larger AABW component and during interglacials a larger NADW component. Our HI1808-GPC04 record supplements the ODP 758 record in the interval with prominent AABW signal (MIS 6/5 transition and MIS 7) and reveals regional effects in some non-radiogenic intervals. The smaller differences between the HI1808-GPC04/ODP 758 and SK 129 records seem to reflect regional Nd input from river systems and non-radiogenic Nd from the boundaries.

Distribution of Freely Dissolved Polycyclic Aromatic Hydrocarbons in the Yellow Sea: Application of Improved Passive Sampling Technique - Yu Lee Jang; Haejin Jeong; Na Yeong Kim; Gi Beum Kim (Ocean Science Journal, 2022)

Seaweed Community and Succession on a Trapezoidal-Shaped Artificial Reef - Seung Wook Jung; Chang Geun Choi (Ocean Science Journal, 2022)

Indicator Framework for Monitoring Ecosystem Integrity of Coral Reefs in the Western Caribbean - Diana Margarita Carrillo-García; Melanie Kolb (Ocean Science Journal, 2022)

Estimation of Seagrass Biomass by In Situ Measurement and Remote Sensing Technology on Small Islands, Indonesia - Nurjannah Nurdin; Khairul Amri; Supriadi Mashoreng; Teruhisa Komatsu (Ocean Science Journal, 2022)

Spatiotemporal Response of Currents and Mixing to the Interaction of Tides and River Runoff in a Mesotidal Estuary - Faruq Khadami; Kiyosi Kawanisi; Mohamad Basel Al Sawaf; Gillang Noor Nugrahaning Gusti; Cong Xiao (Ocean Science Journal, 2022)

Osmotic Regulation Strategy in Three Marine, Estuarial and Freshwater Crab Species (Portunus armatus, Macrophthalmus dentipes and Eriocheir hupensis) - Khadijeh Khalifi; Negin Salamat; Abdolali Movahedinia (Ocean Science Journal, 2022)

A Comprehensive Study on Fish Species Composition, Diversity, Migration, Threatened Status, Economic Value and Endemism in the Co Chien River, Ben Tre Province (Mekong Delta), Vietnam - Xuan-Dong Nguyen; Ngo Xuan Quang; Thanh Luu Pham; Bijeesh Kozhikkodan Veettil (Ocean Science Journal, 2022)

Variation in Fish Abundance in Different Habitats of a Tropical Lagoon with an Attempt to Model the Effects of Physico-Chemical Parameters on Their Abundance - Sulakkana Wanshapaly Rathnayake; Sithara Rasanjali Sirimanna; Chamari Thathsaramala Dissanayake (Ocean Science Journal, 2022)

Impact of Different Wind Representations on Resonant Ocean Near-inertial Motions in the Gulf of Mexico - Chuan-Yuan Hsu; Jongsun Kim; Ping Chang; Steven F. DiMarco (Ocean Science Journal, 2022)

Centrifuge Tube Trap: A Direct-Sampling Mini Plankton Light Trap for Under 3USD - Seong Lee Neoh (Ocean Science Journal, 2022)

Use of Pb Isotopes to Track the Sources of Sediment Metals in Youngil Bay, Korea and Offshore - Yunho Song; Man Sik Choi; In Kwon Um; Seonghu Choi; Dongjin Cho; Sojeong Park; Minseok Choi (Ocean Science Journal, 2022)

Potential of a Tintinnid Species, Tintinnidium primitivum, as a Biological Indicator in the Yellow Sea Bottom Cold Water - Young Ok Kim; Jungmin Choi; Kyung-Hee Oh; Dong Han Choi; Jae Hoon Noh; Wonseok Yang; Myung Jin Hyun (Ocean Science Journal, 2022)

Mortality and Physiological Responses with Regard to the Surf Clam, Mactra quadrangularis, Exposed to Chlorine - Seon-Sik Lee; Hyung-Jin Ahn; In-Uk Hwang; Eun Kim; Kyung-Nam Han (Ocean Science Journal, 2021)

Changes of the Macrobenthos Community with Non-native Mangrove Rehabilitation (Kandelia obovata) and Salt Marsh Invasion (Spartina alterniflora) in Ximen Island, Zhejiang, China - Qiuxuan Wang; Li Song; Susana Agusti; Carlos Duarte; George Christakos; Jiaping Wu (Ocean Science Journal, 2021)

Age Estimation and Growth Performance of the Blackthroat Seaperch, Doederleinia berycoides (Hilgendorf, 1879), in Korean Waters - Makidul Islam Khan; Jung Hwa Choi (Ocean Science Journal, 2021)

Optimization of Bottom Friction Coefficient Using Inverse Modeling in the Persian Gulf - Zahra Ranji; Mohsen Soltanpour (Ocean Science Journal, 2021)

Report on the Annual Gametogenesis and Tissue Biochemical Composition in the Gray mussel, Crenomytilus grayanus (Dunker 1853) in the Subtidal Rocky Bottom on the East Coast of Korea - Thatchaneshkanth Subramaniam; Hee-Jung Lee; Hee-Do Jeung; Hyun-Sil Kang; Chul-Won Kim; Hyung-Seop Kim; Young-Ghan Cho; Kwang-Sik Choi (Ocean Science Journal, 2021)

Seasonal Changes in Gonad Index, Biochemical Composition and Heavy Metal Determination of Sea Urchin Paracentrotus lividus Gonads from the South Coast of Morocco - Hanan Ouchene; Abir Chahouri; Najat Hafidi; Hassan Elouizgani; Jamila Hermas (Ocean Science Journal, 2021)

Age and Growth of Southern Bluefin Tuna, Thunnus maccoyii, Based on Otolith Microstructure - Jeong Eun Ku; Sung Il Lee; Doo Nam Kim (Ocean Science Journal, 2021)
Age and growth of southern bluefin tuna (SBT, Thunnus maccoyii ) were estimated based on otoliths collected by Korean tuna longline vessels in the Atlantic and Indian Oceans from 2015 to 2019. A total of 739 specimens were used to estimate age and growth of SBT, with sizes ranging from 66 to 181 cm in fork length. It was confirmed that the otolith is a suitable aging characteristic for determining SBT age, and otolith annuli can be used as an annual ring. The relationship between fork length (FL) and total weight ( W ) was W = 7.7e − 05FL 2.722 ( R 2 = 0.874). The von Bertalanffy’s growth parameters estimated from the non-linear method using length-at-age data were L ∞ = 170.0 cm, K = 0.200/year, t 0 = − 1.615 years, with 95% confidence intervals between 166 and 175 cm for L ∞ , 0.17–0.23/year for K , and − 2.27 to − 1.09 years for t 0 from bootstrapping. The Kimura’s likelihood ratio test results of the models under assumptions of common and different parameters between female and male concluded that the growth of SBT has no difference between genders.

Rapid and Accurate Method for Determining 234Th in Seawater: Fe Co-precipitation, UTEVA Extraction, and Micro-precipitation - Junhyeong Seo; Hojong Seo; Jeomshik Hwang; Guebuem Kim (Ocean Science Journal, 2021)

Relative Importance of Microplastics as Vectors of Hydrophobic Organic Chemicals to Marine Fish and Seabirds - Su-Young Bang; Yeonjeong Ha; Jung-Hwan Kwon (Ocean Science Journal, 2021)

Assessing Metal Content in Halophila stipulacea Seagrass as an Indicator of Metal Pollution in the Northern Gulf of Aqaba, Red Sea - Tariq Al-Najjar; Mohammad Wahsha; Mwaffaq Al-Khushman; Maroof Khalaf; Kyle Hardage; Wissam Hayek; Khalid Abu Khadra; Adina Paytan (Ocean Science Journal, 2021)

Distribution and Sources of Carbon, Nitrogen and Their Isotopic Compositions in Tropical Estuarine Sediments of Mtoni, Tanzania - Matobola Joel Mihale; Clavery Tungaraza; Willy Baeyens; Natacha Brion (Ocean Science Journal, 2021)

Contrasting Genetic Structures Among Populations of Two Hexagrammid Fish Species in the Northwestern Pacific - Woo-Seok Gwak; Animesh Roy; Kouji Nakayama (Ocean Science Journal, 2021)

Comment on Gazi et al. (2020): Detecting Coral Reef Degradation on St. Martin’s Island, Bangladesh? - Tomas Tomascik; Mohammed Shah Nawaz Chowdhury; Tom Bell (Ocean Science Journal, 2021)

Comparison of Early Succession and Scleractinian Recruitment Between Artificial Live Rocks and Terracotta Tiles - Yusof Muhammad Hamizan; Shahbudin Saad; Mohd Azrul Naim; Mohd Fikri Akmal Khodzori; Muhammad Faiz Mohd Hanapiah (Ocean Science Journal, 2021)

Numerical Modeling of Tropical Cyclone-Induced Storm Surge in the Gulf of Oman Using a Storm Surge–Wave–Tide Coupled Model - Amir Siahsarani; Ali Karami Khaniki; Abbas-Ali Aliakbari Bidokhti; Majid Azadi (Ocean Science Journal, 2021)

Negative Impacts of Perkinsus olseni Infection in Manila Clam Ruditapes philippinarum Observed from Tidal Flats in Anmyeondo Island on the West Coast of Korea During Post-Spawning Period - Hye-Mi Lee; Kyung-Il Park; Hyun-Sung Yang; Kwang-Sik Choi (Ocean Science Journal, 2021)

Comparison of Intestine Microbiota Between Wild and Farmed Korean Rockfish, Sebastes schlegelii - Jihyun Yu; Min Joo Kang; Yun Jae Kim; Mi-Jeong Park; Jae Kyu Lim; Choong Hwan Noh; Sung Gyun Kang; Hyun Sook Lee; Jung-Hyun Lee; Kae Kyoung Kwon (Ocean Science Journal, 2021)

Metal Concentrations in the Coastal Fauna of the Caspian Sea - Alireza Mirzajani; Amir Hossein Hamidian; Jalal Hassan (Ocean Science Journal, 2021)

The Annual Gametogenesis of the Mussel, Mytilus unguiculatus (coruscus) (Valenciennes, 1858), Occurring in the Shallow Subtidal of Ulleungdo Island in Korea - Hyun-Sung Yang; Sung-Jin Yoon; Do-Hyung Kang (Ocean Science Journal, 2021)

Genetic Diversity and Population Genetic Structure of Korean Black Scraper Thamnaconus modestus in Korea and Japan Based on the mtDNA Marker - Woo-Seok Gwak; Animesh Roy (Ocean Science Journal, 2021)

Determination of Similarity Cutoff Value for the Classification of Macrobenthic Communities in the Korean Coast - Jae-Won Yoo; Chae-Lin Lee; Sungtae Kim; Su-Young Jeong; Chang-Gun Lee; Byoung-Seol Koh; Sang-Ock Ryu (Ocean Science Journal, 2021)

Erratum to: Circadian Rhythm Disturbances Due to Exposure to Acidified Conditions and Different Photoperiods in Juvenile Olive Flounder (Paralichthys olivaceus) - Dae-Won Lee; Jin Ah Song; Heung-Sik Park; Cheol Young Choi (Ocean Science Journal, 2021)

Effect of the Wave on Sediment Suspension and the Morphological Pattern of Ripple Formation - Subhadeep Sarkar; Vikas Kumar Das; Krishnendu Barman; Koustuv Debnath (Ocean Science Journal, 2021)

Biometric Relationship of Tegillarca granosa (Bivalvia: Arcidae) from the Northern Region of the Strait of Malacca - Munawar Khalil; Riri Ezraneti; Rachmawati Rusydi; Zulfigar Yasin; Shau Hwai Tan (Ocean Science Journal, 2021)

Circadian Rhythm Disturbances Due to Exposure to Acidified Conditions and Different Photoperiods in Juvenile Olive Flounder (Paralichthys olivaceus) - Dae-Won Lee; Jin Ah Song; Heung-Sik Park; Cheol Young Choi (Ocean Science Journal, 2021)

Water Temperature and Microplastic Concentration Influenced Microplastic Ingestion and Retention Rates in Sea Cucumber (Holothuria cinerascens Brandt, 1835) - Oladimeji Ayo Iwalaye; Ganas Kandasamy Moodley; Deborah Vivienne Robertson-Andersson (Ocean Science Journal, 2021)

A Review: Marine Bio-logging of Animal Behaviour and Ocean Environments - Hyunjae Chung; Jongchan Lee; Won Young Lee (Ocean Science Journal, 2021)

Fluorescent Dissolved Organic Matter (FDOM) in the East Sea (Japan Sea): Distributions, Sources, and Sinks - Heejun Han; Hyung-Mi Cho; Hyeong Kyu Kwon; Guebuem Kim (Ocean Science Journal, 2021)

Long-Term Changes in Fish Assemblage Structure in the Korea Strait from 1986 to 2010 in Relation with Climate Change - Kyunghwan Lee; Seonggil Go; Sukgeun Jung (Ocean Science Journal, 2021)

Korea Institute of Ocean Science and Technology Earth System Model and Its Simulation Characteristics - Gyundo Pak; Yign Noh; Myong-In Lee; Sang-Wook Yeh; Daehyun Kim; Sang-Yeob Kim; Joon-Lee Lee; Ho Jin Lee; Seung-Hwon Hyun; Kwang-Yeon Lee; Jae-Hak Lee; Young-Gyu Park; et al. (Ocean Science Journal, 2021)

Concentration of Trace Metals and Biochemical Alterations in Various Species of Fishes along the West Coast of India - Nageswar Rao Molla; Angad Gaud; Anirudh Ram; Siddaiah Vidavalur; Rakesh Payipattu Sudhakaran; Raja Pitchaikkaran (Ocean Science Journal, 2021)

Effects of Concentrated Freshwater Discharge on Hydrography and Mesozooplankton Community in a Dammed Estuary - Na An; Young-Hee Kim; Sang-Woo Lee; Keun-Hyung Choi (Ocean Science Journal, 2021)

Genetic Structure and Diversity of the Moon Jellyfish Aurelia coerulea Polyp Population in Jaran Bay, Korea, Revealed by Mitochondrial COI and 16S rRNA Genes - Yoseph Seo; Buhari Lawan Muhammad; Jinho Chae; Jang-Seu Ki (Ocean Science Journal, 2021)

Application of Column Chromatography for Accurate Determination of the Carbon Isotopic Compositions of n-alkanes in Diverse Environmental Samples - Dong-Hun Lee; Jung-Hyun Kim; Kyung-Hoon Shin (Ocean Science Journal, 2021)

Resource Utilization of Three Copepods Along Salinity Gradient in the Seomjin River Estuary, Revealed by Stable Isotope Analysis - Dong-Hoon Im; Hae-Lip Suh (Ocean Science Journal, 2021)

Effects of Green Light on the Stress Response of Olive Flounder Paralichthys olivaceus under Clove Oil Anesthesia - Cheol Young Choi; Jin Ah Song; Young-Su Park (Ocean Science Journal, 2021)

Marine-Derived Fungi in Korea - Yong Min Kwon; Seung Sub Bae; Grace Choi; Ji Yeon Lim; Yoon-Hee Jung; Dawoon Chung (Ocean Science Journal, 2021)

Spring Distribution of Ciliate Plankton in the Southeastern Yellow Sea in 2019 - Young Ok Kim; Jungmin Choi; Hyung-Ku Kang; Jae Hoon Noh; Dong Han Choi; Kyung-Hee Oh (Ocean Science Journal, 2021)

Unusual Association of Skipjack Tunas Katsuwonus pelamis and a Longline Vessel - Gonzalo Mucientes; Nair Vilas-Arrondo (Ocean Science Journal, 2021)

Microscopic Research on the Olfactory Organ of the Blue Spotted Mudskipper Boleophthalmus pectinirostris, Compared to a Related Sympatric Mudskipper - Hyun Tae Kim; Jong Young Park (Ocean Science Journal, 2020)

Diversity and Assemblage Structure of Marine Fish Species Collected by Set Net in Korean Peninsula During 2009–2013 - Jung-Hwa Ryu; Jin-Koo Kim (Ocean Science Journal, 2020)

Salinity Biases and the Variability of the Atlantic Meridional Overturning Circulation in GFDL-CM3 - Fernanda D. A. O. Matos; Janini Pereira; Marcus Dengler (Ocean Science Journal, 2020)

Trends in Tidal Levels and Mean Sea Level in the Gulf of Thailand - Nitinun Pongsiri; Rhysa McNeil; Somporn Chuai-Aree (Ocean Science Journal, 2020)

Are Juvenile Manila Clam Ruditapes philippinarum Free from Perkinsus olseni Infection in Korean Waters? - Hye-Mi Lee; Young-Ghan Cho; Hee-Do Jeung; Min-Seok Jang; Jee Youn Hwang; Kwang-Sik Choi (Ocean Science Journal, 2020)

Preliminary Study of Catalase Enzyme Activity and Protein Concentrations in the Mediterranean and African Mussels, Mytilus galloprovincialis and Perna perna, Cohabiting on the Same Natural Coastal Site (Figuier, Boumerdes, Algeria) - Kourdali Sidali; Bounakous Nabila; Meknachi Abdellah; Zenati Bilal; Inal Ahmed (Ocean Science Journal, 2020)

Comparisons of Net Heat Flux Data Sets Over the Western North Pacific - Gyundo Pak; Jae-Hyoung Park; Seok-Joon Lee; Young-Gyu Park; You-Soon Chang (Ocean Science Journal, 2020)

Transgressive Shelf Sands around the Korean Peninsula: A Brief Review - Hee Jun Lee; Chung Kyun Jeon; Hak Soo Lim (Ocean Science Journal, 2020)

Subtidal Marine Algal Community and Endangered Species in Dokdo and Ulleungdo, Two Oceanic Islands in the East Sea of Korea - Seung Wook Jung; Yoon Sik Oh; Hyun Soo Rho; Chang Geun Choi (Ocean Science Journal, 2020)

Characteristics and Ecosystem Changes of Marine Algal Communities in Wangdol-cho on the East Coast of Korea - Seung Wook Jung; Hyun Soo Rho; Chang Geun Choi (Ocean Science Journal, 2020)

Study on the Distribution of Surface Chlorophyll-a and Subsurface Chlorophyll Maximum in the Southeastern Yellow Sea According to the Typhoon Paths and Water Masses - Pung-Guk Jang; Jung-Hoon Kang; Kyoungsoon Shin (Ocean Science Journal, 2020)

Verification of the Backscattering Strength Based on the Swimming Behavior of Antarctic Krill - Inwoo Han; Wooseok Oh; Hyoung Sul La; Seok-Gwan Choi; Sukyung Kang; Euna Yoon; Kyounghoon Lee (Ocean Science Journal, 2020)

Ocean Responses to Typhoon Soulik (1819) around Korea - KiRyong Kang; Hyeong Jun Jo; YoonJae Kim (Ocean Science Journal, 2020)

Detection of Coral Reefs Degradation using Geospatial Techniques around Saint Martin’s Island, Bay of Bengal - Md. Yousuf Gazi; Tahrim Jannat Mowsumi; Md. Kawser Ahmed (Ocean Science Journal, 2020)

Molecular Detection for Two Abalone Shell-boring Species Polydora haswelli and P. hoplura (Polychaeta, Spionidae) from Korea using 18S rDNA and cox1 Markers - Soon Jeong Lee; Mun-Gyeong Kwon; Sang-Rae Lee (Ocean Science Journal, 2020)

The Summer/Fall Variability of the Southern East/Japan Sea in the ENSO Period - Woo Geun Cheon (Ocean Science Journal, 2020)

Cadmium Accumulation and mRNA Expression Associated with Detoxification in Various Organs of Black Seabream (Acanthopagrus schlegelii) Exposed to Cadmium-contaminated Diet - Won-Jun Yeo; Hyung-Jin Ahn; In-Uk Hwang; Keon-ho Lee; Kyung-Nam Han (Ocean Science Journal, 2020)

The Accumulation of Al, As, Li, Mg, Mn, S, Si, Ti, and V in the Mussel Mytilus galloprovincialis from the Moroccan Mediterranean Coastal Areas: Trends Pertaining to Seasons and Levels - Ghizlane Azizi; Mostafa Layachi; Mustapha Akodad; Mourad Baghour; Mohammad Ghalit; Elkhadir Gharibi; Hamza Ngadi; Abdelmajid Moumen (Ocean Science Journal, 2020)

Change of Foraging and Hiding Behaviors in the Pacific Abalone Haliotis discus hannai in Response to Elevated Seawater Temperature - Tae Won Kim; Jung-Ah Lee; Chae-Young Yoo (Ocean Science Journal, 2020)

Oil Spill Four-Class Classification Using UAVSAR Polarimetric Data - Behnam Hassani; Mahmod Reza Sahebi; Reza Mohammadi Asiyabi (Ocean Science Journal, 2020)

Submesoscale Flows Associated with Convergent Strain in an Anticyclonic Eddy of the Kuroshio Extension: A High-resolution Numerical Study - Shihao Luo; Zhiyou Jing; Yiquan Qi (Ocean Science Journal, 2020)

Observations and Measurements of Planktonic Bioluminescence off the South Coast and Puttalam Lagoon of Sri Lanka - Hewa Bhashithage Udeshika Gangani M Wimalasiri; Sinhalage Udaya Priyantha Jinadasa; Dadigamuwage Chamari Tathsaramala Dissanayake; Hemantha W. Wijesekara; Alan D. Weidemann (Ocean Science Journal, 2020)

Wave Data Assimilation to Modify Wind Forcing Using an Ensemble Kalman Filter - Jinah Kim; Jeseon Yoo; Kideok Do (Ocean Science Journal, 2020)

Relationship between Age and Oxygen along Line W in the Northwest Atlantic Ocean - Jordan L. Thomas; Darryn W. Waugh; Anand Gnanadesikan (Ocean Science Journal, 2020)

Acoustic Characteristic of Sailfin Sandfish (Arctoscopus japonicus) in Dokdo, Republic of Korea - Myounghee Kang; Rina Fajaryanti; Sangchul Yoon; Bokyu Hwang (Ocean Science Journal, 2020)

Deepening of Future Aleutian Low in Ensemble Global Warming Simulations with the Kiel Climate Model - Hwan Young Choi; Ho Jin Lee; Sang-Yeob Kim; Wonsun Park (Ocean Science Journal, 2020)

Icefish Adaptations to Climate Change on the South Georgia Island Shelf (Sub-Antarctic) - Ryszard Traczyk; Victor Benno Meyer-Rochow; Robert M. Hughes (Ocean Science Journal, 2020)

Long-term Changes of Disinfection Byproducts in Treatment of Simulated Ballast Water - Pung-Guk Jang; Hyung-Gon Cha (Ocean Science Journal, 2020)

Morphological and Anatomical Differences among Three Seagrass Species in a High-energy Coastal Area Typically Dominated by Surfgrass in a Rocky Coastal Area of Shandong Peninsula, China - Wen-Tao Li; Jia Song; Chongfeng Zhong; Xin Hou; Ran Cheng; Pei-dong Zhang (Ocean Science Journal, 2020)

Application of the DPSIR Framework to Coastal and Marine Fisheries Management in Kenya - Mumini Dzoga; Danny Mulala Simatele; Cosmas Munga; Shadrack Yonge (Ocean Science Journal, 2020)

Morphological Variation of the Sea Silverside Odontesthes regia in Regions with Dissimilar Upwelling Intensity along the Humboldt Current System - Diego Deville; Gustavo Sanchez; Sergio Barahona; Carmen Yamashiro; Daniel Oré-Chávez; Roger Quiroz Bazán; Tetsuya Umino (Ocean Science Journal, 2020)

An Application of the Bayesian Hierarchical Approach to Refining the Information on Main Life History Parameters for Small Yellow Croaker, Larimichthys polyactis, off the Coast of China - Lixin Zhu; Zhenlin Liang; Changzi Ge; Chunli Liu (Ocean Science Journal, 2020)

Comparison of Turbulent Flows and Suspended Sediment Particle Motions Simulated around a Submerged Breakwater Using RANS and LES - Yeon S. Chang; Jong Dae Do; Weon Mu Jeong; Sang Kwon Hyun; Won-Dae Baek; Jae Ho Choi; Jae-Youll Jin (Ocean Science Journal, 2020)

Changes in Fish Assemblages after Dike Construction in the Saemangeum Area - Jeong-Hui Kim; Sang-Hyeon Park; Seung-Ho Baek; Min-Ho Jang; Ju-Duk Yoon (Ocean Science Journal, 2020)

Validation of Reference Genes for Quantitative Gene Expression Studies in Octopus minor - Ilson Whang; Hyun-Sil Kang; Yucheol Kim (Ocean Science Journal, 2020)

Equatorial Indian Ocean Response during Extreme Indian Summer Monsoon Years Using Reliable CMIP5 Models - Alfred Johny; Kalidahasan Vasanthakumari Ramesh (Ocean Science Journal, 2020)

Impact of Temperature, Low pH and NH4+ Enrichment on Ecophysiological Responses of a Green Tide Species Ulva australis Areschoug - Cicilia S. B. Kambey; Jin Woo Kang; Ik Kyo Chung (Ocean Science Journal, 2020)

Total Microbial Activity and Sulfur Cycling Microbe Changes in Response to the Development of Hypoxia in a Shallow Estuary - Yunjung Park; Jaeho Cha; Bongkeun Song; Yan Huang; Seoyoung Kim; Suhyun Kim; Eunhye Jo; Samantha Fortin; Soonmo An (Ocean Science Journal, 2020)

A Temperature-Dependent Growth Equation for Larval Chub Mackerel (Scomber japonicus) - Seonggil Go; Kyunghwan Lee; Sukgeun Jung (Ocean Science Journal, 2020)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)

Spatiotemporal Distribution of Dissolved Heavy Metals in Gyeonggi Bay, Korea - Sojung Park; Mansik Choi; Dongjun Jang; Dongjin Joe; Kyunggue Park; Hyojin Lee; Junsik Woo; Taeha Kim; Jongkyu Park (Ocean Science Journal, 2020)

Distribution and Sources of Dissolved and Particulate Heavy Metals (Mn, Co, Ni, Cu, Zn, Cd, Pb) in Masan Bay, Korea - Sojung Park; Mansik Choi; Dongjun Jang; Dongjin Joe; Kyunggue Park (Ocean Science Journal, 2020)

Assessing Cryptic Invasion State: Fine-Scale Genetic Analysis of Ciona savignyi Population in Putative Native Habitat of the Korean Coast - Chang Ho Yi; Won Kim (Ocean Science Journal, 2020)

Wrapround Multiple Reflectors over the Seafloor in the Gas Hydrate Area: A Possible Indicator of Methane Plume - Yuto Sakakibara; Jun Matsushima (Ocean Science Journal, 2019)

Estimation of the Effect of Flushing Time on Oyster Aquaculture Potential in Jaran Bay - Jin Ho Kim; Sokjin Hong; Won-Chan Lee; Hyung Chul Kim; Ki-Hyuk Eom; Woo-Sung Jung; Dong-Myung Kim (Ocean Science Journal, 2019)

Assessment of Tidal Stream Energy Resources Using a Numerical Model in Southwestern Sea of Korea - Jun-Seok Park; Chol-Young Lee; Jin-Soon Park; Hyun-Woo Choi; Dong-Hui Ko; Jung-Lyul Lee (Ocean Science Journal, 2019)

A Review on Marine N2 Fixation: Mechanism, Evolution of Methodologies, Rates, and Future Concerns - P. S. Bhavya; Jun-Oh Min; Min-Seob Kim; Hyo Keun Jang; Kwanwoo Kim; Jae Joong Kang; Jae Hyung Lee; Dabin Lee; Naeun Jo; Myung Joon Kim; Yejin Kim; Junbeom Lee; et al. (Ocean Science Journal, 2019)

Downwelling Events in a Coastal Mussel Farming Area, NW Thessaloniki’s Gulf (NW Aegean Sea) - Yiannis Savvidis; Alexander Antoniou; Amalia Moriki; Vasilis-Orestis Stoilas (Ocean Science Journal, 2019)

On Robust Multi-Year Tidal Prediction Using T_TIDE - Do-Seong Byun; Deirdre Erin Hart (Ocean Science Journal, 2019)

Investigating the Effects of Different LED Wavelengths on Aggregation and Swimming Behavior of Chub Mackerel (Scomber japonicus) - Donggil Lee; Wooseok Oh; Byeong-Mo Gim; Jung Suk Lee; Euna Yoon; Kyounghoon Lee (Ocean Science Journal, 2019)

Interactive Effects of Ultraviolet Radiation and Dissolved Organic Carbon on Phytoplankton Growth and Photosynthesis in Sanya Bay, Northern South China Sea - Jianzu Liao; Jie Xu; Xiangcheng Yuan; Yuxian Liang; Yajuan Guo; Weihua Zhou; Hui Huang; Sheng Liu; Aimin Long (Ocean Science Journal, 2019)

Patterns of Gene Expression Variation across Body Parts of the Hydrothermal Vent Shrimp Nautilocaris saintlaurentae - Ryeo-Ok Kim; Eun-Ji Won; Hyun Mi Kang; Se-Jong Ju; Se-Joo Kim (Ocean Science Journal, 2019)

Seasonal Variability of Polycyclic Aromatic Hydrocarbons (PAHs) in a Coastal Marine Area in the Northwestern Region of the Sea of Japan/East Sea (Possiet Bay) - Yuliya Koudryashova; Tatiana Chizhova; Pavel Tishchenko; Kazuichi Hayakawa (Ocean Science Journal, 2019)

Characterization and Transcriptional Response of Ecdysone Receptor Gene in the Mud Crab Macrophthalmus japonicus: Effects of Osmotic Stress and Endocrine Disrupting Chemicals - Kiyun Park; Won-Seok Kim; Ihn-Sil Kwak (Ocean Science Journal, 2019)

R/V Isabu-Based First Ultraclean Seawater Sampling for Ocean Trace Elements in Korea - Suk Hyun Kim; Kongtae Ra; Kyung-Tae Kim; Hyeryeong Jeong; Jihyun Lee; Dong-Jin Kang; Taekeun Rho; Intae Kim (Ocean Science Journal, 2019)

Harmful Dinoflagellate Prorocentrum donghaiense Lu is Widely Distributed Along the East China Sea and Korean Coastal Area - Hyeon Ho Shin; Zhun Li; Min Ho Seo; Ho Young Soh; Weol Ae Lim; Jong Woo Park (Ocean Science Journal, 2019)

Current Status of Marine Pollution and Mitigation Strategies in Arid Region: A Detailed Review - Prerana Chitrakar; Mahad Said Baawain; Ahmad Sana; Abdullah Al-Mamun (Ocean Science Journal, 2019)

Estimate of Coastal Water Depth Based on Aerial Photographs Using a Low-Altitude Remote Sensing System - Jong-Seok Lee; Ji-Yeon Baek; Dawoon Jung; Jae-Seol Shim; Hak-Soo Lim; Young-Heon Jo (Ocean Science Journal, 2019)

Abundance and Taxonomic Diversity of Bacteria Inhabiting the Sediment-Water Interface in a Marine Harbor Channel - Piotr Perliński; Zbigniew J. Mudryk; Marta Zdanowicz (Ocean Science Journal, 2019)
The abundance of bacteria inhabiting the sediment-water interface and their taxonomic composition were determined with the fluorescence in situ hybridization (FISH) method in a marine harbor channel in Ustka. Among bacteria inhabiting the studied layer Gammaproteobacteria (1.4 cells 10 8 ·dm −3 ) and Cytophaga - Flavobacterium (1.1 cells 10 8 ·dm −3 ) dominated. Vibrio and Pseudomonas represented only a small fraction of the total cell counts. All taxonomic groups of studied bacteria show significant positive correlation between their abundance. The total bacterial number varied from 3.3 to 23.5 cells 10 8 ·dm −3 and their biomass oscillated from 39.4 to 282.4 μg C·dm −3 . This parameter differed along horizontal profiles, while there were no significant differences in the abundance of the studied taxonomic groups among the study sites of the channel in Ustka. The total number of bacteria as well as the abundance of bacterial phylogenetic groups were subject to seasonal fluctuation in the studied water basin.

Investigation of the Concentration of Metals in Two Economically Important Fish Species from the Caspian Sea and Assessment of Potential Risk to Human Health - Eisa Solgi; Hossein Alipour; Farshid Majnooni (Ocean Science Journal, 2019)

Density Estimates of Moon Jellyfish (Aurelia coerulea) in the Yeongsan Estuary using Nets and Hydroacoustics - Eun-A Yoon; Kyounghoon Lee; Jinho Chae; Wonduk Yoon; Changhoon Han; Hyeeun Lee; Pyungkwan Kim; Wooseok Oh (Ocean Science Journal, 2019)

Molecular and Morphometric Variations in the Sea Raven, Hemitripterus villosus from Korea, with its Implication on Fisheries Management - Seo-Ha Jang; Jang-Won Lee; Jin-Koo Kim (Ocean Science Journal, 2019)

Molecular Identification and Expression Analysis of Carbonic Anhydrase VII in Pufferfish (Takifugu rubripes) - Kanij Rukshana Sumi; Soo Cheol Kim; Jewel Howlader; Md Rajib Sharker; Kap Seong Choi; Sang Ki Choi; Jong-In Park; Ill-Sup Nou; Kang Hee Kho (Ocean Science Journal, 2019)

Temperature-Dependent Bifurcated Seasonal Shift of Phytoplankton Community Composition in the Coastal Water off Southwestern Korea - Yoonja Kang; Hee-Yoon Kang; Dongyoung Kim; Young-Jae Lee; Tae-Ik Kim; Chang-Keun Kang (Ocean Science Journal, 2019)

The First Molecular Evidence of Korean Zalophus japonicus (Otariidae: Sea Lions) from the Archaeological Site of Dokdo Island, Korea - Sang-Rae Lee; Yun-Bae Kim; Tongsup Lee (Ocean Science Journal, 2019)

Biomarker-based Seawater Temperatures of Winter Sinking Particles and Core-top Sediment in the Ulleung Basin of the East Sea - Yu-Hyeon Park; Hyung Jeek Kim; Ju Won Son; Chan Min Yoo; Boo-Keun Khim (Ocean Science Journal, 2019)

Diversity and Abundance of Scleractinian Corals in the East Coast of Peninsular Malaysia: A Case Study of Redang and Tioman Islands - Khodzori Fikri Akmal; Saad Shahbudin; Mohd Hanapiah Muhammad Faiz; Yusof Muhammad Hamizan (Ocean Science Journal, 2019)

Summer Variations of Macrobenthic Community Structures in Gwangyang Bay, Korea - Jin-Young Seo; Young Ok Kim; Jin-Woo Choi (Ocean Science Journal, 2019)

Succession of the Nanoplankton Community during a Brown Tide in a Scallop Culture Area in China - Ling Qiao; Jie Yu; Ying Li; Haobing Guo; Yu Zhen; Lingling Zhang; Tiezhu Mi; Fuchong Zhang; Zhenmin Bao (Ocean Science Journal, 2019)

On the Effects of Acid Pre-treatment on the Elemental and Isotopic Composition of Lightly- and Heavily-calcified Marine Invertebrates - Georgios Kazanidis; Solveig Bourgeois; Ursula F. M. Witte (Ocean Science Journal, 2019)

Population Genetic Structure of Liza affinis (Eastern Keelback Mullet), Reveals High Gene Flow Inferred from Microsatellite Analysis - Lu Liu; Xiumei Zhang; Dianrong Sun; Tianxiang Gao; Na Song (Ocean Science Journal, 2019)

Modelling the Particulate Backscattering Coefficients of Turbid and Productive Coastal Waters - V. Gomathisankaraprasad Harharasudhan; Palanisamy Shanmugam (Ocean Science Journal, 2019)

De novo Assembly and Annotation of the Blood Transcriptome of the Southern Elephant Seal Mirounga leonina from the South Shetland Islands, Antarctica - Bo-Mi Kim; Do-Hwan Ahn; Seunghyun Kang; Jihye Jeong; Euna Jo; Jeong-Hoon Kim; Jae-Sung Rhee; Hyun Park (Ocean Science Journal, 2019)

Effects of UV Radiation on Oxidative Stress in Yellowtail Clownfish Amphiprion clarkii - Han Seok Ryu; Cheol Young Choi; Jin Ah Song; Gyung-Suk Kil (Ocean Science Journal, 2019)

Classification of the Global Tidal Types Based on Auto-correlation Analysis - Sung-Hwa Lee; You-Soon Chang (Ocean Science Journal, 2019)

Distribution of Mesozooplankton during Spring and Autumn across the Frontal Zone of South Sea, Korea - Minju Kim; Jung-Hoon Kang; Garam Kim; Hyung-Ku Kang; Jae Hoon Noh (Ocean Science Journal, 2019)

The Characteristics and Distribution of Eukaryotic Phytoplankton Community in Liaodong Bay, China - Lun Song; Jing Wu; Jing Du; Nan Li; GuangJun Song; Kun Wang; Ming Sun; Peng Wang (Ocean Science Journal, 2019)

Seasonal Variations in Primary Productivity and Biomass of Phytoplankton in Geoje-Hansan Bay on the Southern Coast of Korea - Dongyoung Kim; Young-Jae Lee; Hee Yoon Kang; Kee-Young Kwon; Won-Chan Lee; Jung Hyun Kwak (Ocean Science Journal, 2019)

Gender Differences in Foraging Behavior of the Euphausiid Euphausia pacifica in the East Sea (Japan Sea) in Spring - Dong-Hoon Im; Seung-Kyu Kim; Hae-Lip Suh (Ocean Science Journal, 2019)

Coastal Ecosystem Health Assessment in Korea: Busan Case Study - Young Ok Kim; Won Joon Shim; Seung Ho Baek; Jin-Woo Choi; Dongseon Kim; Hyun-Woo Choi (Ocean Science Journal, 2019)

Stenophagy as a Pathway for the Occurrence of Unique Coral Fatty Acid Biomarkers in Higher Branches of the Marine Tree of Life: The Nudibranch Armina maculata Case - Rui Rosa; Catarina Santos; Ana Lopes; Miguel Baptista; Eduardo Sampaio; Inês C. Rosa; Tiago Repolho (Ocean Science Journal, 2019)

Late Holocene Shallow Marine Sand Sheet in the Haeundae Coast, Korea - Young Sook Baek; Hee Jun Lee; Su Hwan Lee; Dong-Hyeok Shin (Ocean Science Journal, 2019)

Practical Resilience Index for Coral Reef Assessment - Imam Bachtiar; Suharsono; Ario Damar; Neviaty P. Zamani (Ocean Science Journal, 2019)

Intraseasonal-to-Interannual Variability of the Upper-Layer Zonal Currents in the Tropical Northwest Pacific Ocean - Fuad Azminuddin; Dongchull Jeon; Chang-Woong Shin (Ocean Science Journal, 2019)

Importance of a Coastal Artificial Lake in Methylmercury Production: A Case Study of Lake Changpo, Korea - Sampa Rani Kundu; Eunhee Kim; Seunghee Han; Byeong-Gweon Lee (Ocean Science Journal, 2019)

Physiological Responses of Cultured Seaweed Pyropia yezoensis to Phosphorous Limitation in the Nakdong River Estuary, Korea - Sangil Kim; Sang Chol Yoon; Man Ho Yoo; Kyung Woo Park; Sang Rul Park; Seok-Hyun Youn (Ocean Science Journal, 2019)

A Review on the Macromolecular Compositions of Phytoplankton and the Implications for Aquatic Biogeochemistry - P. S. Bhavya; Bo Kyung Kim; Naeun Jo; Kwanwoo Kim; Jae Joong Kang; Jae Hyung Lee; Dabin Lee; Jang Han Lee; HuiTae Joo; So Hyun Ahn; Yewon Kim; Jun-Oh Min; et al. (Ocean Science Journal, 2019)

M2 Tidal Current Estimation from One-day Observation Data off the Western and Southern Coasts of Korea - Seok Lee; Kyung-Hee Oh; Sung-Tae Jang; Hak Yoel You; Joonsung Park; Kyu-Min Song (Ocean Science Journal, 2019)

Isolation, Morphological Characteristics and Proteomic Profile Analysis of Thermo-tolerant Pyropia yezoensis Mutant in Response to High-temperature Stress - Hak-Jyung Lee; Eun-Jeong Park; Jong-il Choi (Ocean Science Journal, 2019)

Determining Water Depths for Monitoring Coastal Water Quality Using Multiple Functional Traits of Periphytic Protozoa in Marine Ecosystems - Congcong Guo; Xiaoyun Bai; Mamun Abdullah Al; Mohammad Nurul Azim Sikder; Henglong Xu (Ocean Science Journal, 2019)

Lagrangian Approach for a New Separation Index of the East Korea Warm Current - Gyundo Pak; Young Ho Kim; Young-Gyu Park (Ocean Science Journal, 2019)

Effects of Temperature and Salinity on the Egg Development and Larval Settlement of Ciona robusta (Ascidiacea, Phlebobranchia, Cionidae) - Min Kyung Kim; Dong Hyun Kim; Ju-un Park; Dong Hwan Kim; Tae Joong Yoon; Dong Gun Kim; Yoon Lee; Sook Shin (Ocean Science Journal, 2019)

Genetic Structure and Haplotype Pattern of Marine Planktonic Ostracod (Porroecia spinirostris) from South China Sea Based on Mitochondrial COI Gene - Lei Xu; Hong Li; Lianggen Wang; Feiyan Du (Ocean Science Journal, 2019)

Day-Night and Gastrointestinal Changes in Winter Feeding Intensity and Prey Composition of Apogon lineatus Inhabiting the Southeastern Waters of Korea - Joo Myun Park; Hae Kun Jung; Chung Il Lee; Sung-Hoi Huh (Ocean Science Journal, 2019)

Chelonodontops bengalensis (Tetraodontiformes: Tetraodontidae): A New Species of Puffer Fish from the Northern Bay of Bengal Based on Morphology and DNA Barcode - Kazi Ahsan Habib; Amit Kumer Neogi; Jina Oh; Youn-Ho Lee; Choong-Gon Kim (Ocean Science Journal, 2019)

Physiological Characteristics and Related Biochemical Parameters of Snow Algae from King George Island, Antarctica - Bo Kyung Kim; HyoungMin Joo; Boyeon Lee; Dong-Hun Lee; In-Young Ahn; Sun-Yong Ha (Ocean Science Journal, 2018)

Desorption of Hydrophobic Organic Chemicals from Fragment-Type Microplastics - Hwang Lee; Da-Eun Byun; Ju Min Kim; Jung-Hwan Kwon (Ocean Science Journal, 2018)

Decoupling of Macromolecular Compositions of Particulate Organic Matters between the Water Columns and the Sediment in Geoje-Hansan Bay, South Korea - Hyung Chul Kim; Jae Hyung Lee; Won-Chan Lee; Sokjin Hong; Jae Joong Kang; Dabin Lee; Naeun Jo; P. S. Bhavya (Ocean Science Journal, 2018)

Fishery-induced Inter-annual Changes in the Mean Trophic Level, the Northern Sea of Oman off the Iranian Coast, 2002–2011 - Sakineh Mashjoor; Fatemeh Heidary Jamebozorgi; Ehsan Kamrani (Ocean Science Journal, 2018)

Occurrence of Anisakid Nematodes in Walleye Pollock (Gadus chalcogrammus) Caught off the East Sea of Korea: Their Molecular Identification and Biological Implication - Septianto Wikan Nurhidayat; U-Hwa Nam; Jeong-Ho Kim (Ocean Science Journal, 2018)

Metallothionein cDNA Cloning and Metallothionein Expression in Sea Cucumber (Apostichopus japonicus, Slenka) from the WeiHai Coast of China - Xinfang Lv; Wenhao Deng; Pei Yu; Zhaoyang Hua (Ocean Science Journal, 2018)

Seasonal Shift in Community Structure of Periphytic Ciliates in Estuarine Waters in the Northern Bay of Bengal, Bangladesh - Mamun Abdullah Al; Rahman Muhammed Forruq; Aysha Akhtar; Md. Wahidul Alam; Mohammad Nurul Azim Sikder; Alan Warren; Henglong Xu (Ocean Science Journal, 2018)

Monthly Geographical Distribution of Nemopilema nomurai (Scyphozoa: Rhizosotomeae) in the Bohai and North Yellow Seas: a Preliminary Study using Ships of Opportunity - Wonduk Yoon; Kiyeon Hahn; Jing Dong; Jinho Chae (Ocean Science Journal, 2018)

Optimization of Chemical Oxygen Demand Determination in Seawater Samples Using the Alkaline Potassium Permanganate Method - TaeKeun Rho; Sang-Hwa Choi; Eun Soo Kim; Na Yeon Kang; Sung Rok Cho; Sung Hyun Khang; Dong-Jin Kang (Ocean Science Journal, 2018)

Characterization of Frequency and Aggregation of the Antarctic Krill (Euphausia superba) Using Acoustics - Seok-Gwan Choi; Eun-A Yoon; Doo-Hae An; Sangdeuk Chung; Jaebong Lee; Kyounghoon Lee (Ocean Science Journal, 2018)

Physiological Responses of the Mediterranean Subtidal Alga Peyssonnelia squamaria to Elevated CO2 - Gamze Yıldız (Ocean Science Journal, 2018)

Genome Wide Computational Identification of Tuna (Thunnus orientalis) MicroRNAs and Their Targets - Sangita Chowdhury Paul; Ashutosh Sharma; Richa Mehta; Sujay Paul (Ocean Science Journal, 2018)

Re-evaluation of Morphological Diagnostic Characteristics of Hexapleomera Dudich, 1931 (Crustacea: Tanaidacea), with Description of a New Species - Jin Hee Wi; Chang-Keun Kang; In Tae Lee; Hyeon Gyeong Jeong (Ocean Science Journal, 2018)

Evaluation of the Effect of Marine Ranching Activities on the Tongyeong Marine Ecosystem - Sung Il Lee; Chang Ik Zhang (Ocean Science Journal, 2018)

Application of a Conceptual Ecological Model to Predict the Effects of Sand Mining around Chilsan Island Group in the West Coast of Korea - Jae-Won Yoo; Chan-Woo Lee; Yong-Woo Lee; Chang-Soo Kim; Chang-Gun Lee; Keun-Hyung Choi; Seung Won Jung; Sung-Joo Jin; Kyu-Hee Son (Ocean Science Journal, 2018)

A Length-based Analysis of Recruitment Variability in the Korean Pollock Population under Data-limited Conditions - Kyuhan Kim; Saang-Yoon Hyun (Ocean Science Journal, 2018)

Experiments on Surface Waves Interacting with Flexible Aquatic Vegetation - Luca Cavallaro; Antonino Viviano; Giovanni Paratore; Enrico Foti (Ocean Science Journal, 2018)

Neotectonics of the Eastern Korean Margin Inferred from Back-arc Rifting Structure - Han-Joon Kim; Hyeong-Tae Jou; Gwang Hoon Lee (Ocean Science Journal, 2018)

Studies on the Application of Steady State Assumption in 1DV Model for the Estimation of Settling Velocity of Suspended Sediments in a Shallow Estuary - K. L. Priya (Ocean Science Journal, 2018)

Stipe Length as an Indicator of Reproductive Maturity in the Kelp Ecklonia cava - Sangil Kim; Suk Hyun Youn; Hyun-Ju Oh; Sun Kyeong Choi; Yun Hee Kang; Tae-Hoon Kim; Hyuk Je Lee; Kwang-Sik Choi; Sang Rul Park (Ocean Science Journal, 2018)

Acidification at the Surface in the East Sea: A Coupled Climate-carbon Cycle Model Study - Young-Gyu Park; Kyung-Hee Seol; Kyung-On Boo; Johan Lee; Chunho Cho; Young-Hwa Byun; Seongbong Seo (Ocean Science Journal, 2018)

Wave-induced Maintenance of Suspended Sediment Concentration during Slack in a Tidal Channel on a Sheltered Macro-tidal Flat, Gangwha Island, Korea - Guan-hong Lee; KiRyong Kang (Ocean Science Journal, 2018)

Recent Primary Production and Small Phytoplankton Contribution in the Yellow Sea during the Summer in 2016 - Hyo Keun Jang; Jae Jung Kang; Jae Hyung Lee; Myungjoon Kim; So Hyun Ahn; Jin-Yong Jeong; Mi Sun Yun; In-Seong Han; Sang Heon Lee (Ocean Science Journal, 2018)

Polyp Removal of a Bloom Forming Jellyfish, Aurelia coerulea, in Korean Waters and Its Value Evaluation - Wonduk Yoon; Jinho Chae; Byoung-Seol Koh; Changhoon Han (Ocean Science Journal, 2018)

The Interactive Effects of Elevated CO2 and Ammonium Enrichment on the Physiological Performances of Saccharina japonica (Laminariales, Phaeophyta) - Jin Woo Kang; Ik Kyo Chung (Ocean Science Journal, 2018)

Improved Chlorophyll-a Algorithm for the Satellite Ocean Color Data in the Northern Bering Sea and Southern Chukchi Sea - Sang Heon Lee; Jongseong Ryu; Jung-woo Park; Dabin Lee; Jae-Il Kwon; Jingping Zhao; SeungHyun Son (Ocean Science Journal, 2018)

Preface for the Special Volume on Exploration and Environmental Considerations of Deep Seabed Mineral Resources - Kiseong Hyeong; Se-Jong Ju; David Billett; Ashley Rowden (Ocean Science Journal, 2018)

Mining at 2,500 Fathoms under the Sea: Thoughts on an Emerging Regulatory Framework - Chris G. Brown (Ocean Science Journal, 2018)

Fine-scale Microbial Communities Associated with Manganese Nodules in Deep-sea Sediment of the Korea Deep Ocean Study Area in the Northeast Equatorial Pacific - Hyeyoun Cho; Kyeong-Hong Kim; Seung Kyu Son; Jung-Ho Hyun (Ocean Science Journal, 2018)

The Role of Bimodal Magmatism in Seafloor Massive Sulfide (SMS) Ore-forming Systems at the Middle Okinawa Trough, Japan - Toru Yamasaki (Ocean Science Journal, 2018)

3D Focused Inversion of Near-bottom Magnetic Data from Autonomous Underwater Vehicle in Rough Seas - Zhou Fei; Tao Chunhui; Wu Tao; Zeng Zhaofa; Liu Cai (Ocean Science Journal, 2018)

Resource Assessment of Polymetallic Nodules Using Acoustic Backscatter Intensity Data from the Korean Exploration Area, Northeastern Equatorial Pacific - Chan Min Yoo; Jongmin Joo; Sang Hoon Lee; Youngtak Ko; Sang-Bum Chi; Hyung Jeek Kim; Inah Seo; Kiseong Hyeong (Ocean Science Journal, 2018)

Distribution and Variability of the Meiobenthic Assemblages near the Korean Polymetallic Nodule Claim Area of the Clarion-Clipperton Fracture Zone (Subequatorial NE Pacific) - Won-Gi Min; Dongsung Kim; Hyun Soo Rho; Sang Bum Chi; Seung-Kyu Son (Ocean Science Journal, 2018)

Sinking Particle Flux in the Subtropical Oligotrophic Northwestern Pacific from a Short-term Sediment Trap Experiment - Hyung Jeek Kim; Jonguk Kim; Dongseon Kim; Michael T. Chandler; Seung Kyu Son (Ocean Science Journal, 2018)

Characterization of Deep-sea Macrofauna in the Korean Exploration Claim Area in the Clarion-Clipperton Fracture Zone, Northeastern Pacific Ocean - Ok Hwan Yu; Hyung-Gon Lee; Dongsung Kim; Jin Hee Wi; Kyeong Hong Kim; Chan Min Yoo (Ocean Science Journal, 2018)

Variability in Particle Mixing Rates in Sediments with Polymetallic Nodules in the Equatorial Eastern Pacific as Determined from Measurements of Excess 210Pb - Kiseong Hyeong; Inah Seo; Hyun-Bok Lee; Chan Min Yoo; Sang-Bum Chi; In Kwon Um (Ocean Science Journal, 2018)

Rock Magnetic Approaches Used on Deep-sea Sediments in the Northeastern Equatorial Pacific - Cheong Kee Park; Gun Chang Lee (Ocean Science Journal, 2018)

A Baseline Assessment of Coral Reef in Malacca Straits, Malaysia - Che Din Mohd Safuan; Azizi Ali; Zuraini Zainol; Ahmad Ali; Mohd Fadzil Mohd Akhir; Aidy M. Muslim; Zainudin Bachok (Ocean Science Journal, 2018)

The Effects of Ocean Acidification on Feeding and Contest Behaviour by the Beadlet Anemone Actinia equina - Tess Olivia Bamber; Angus Charles Jackson; Robert Philip Mansfield (Ocean Science Journal, 2018)

Progress in the Study of Coastal Storm Deposits - Haixian Xiong; Guangqing Huang; Shuqing Fu; Peng Qian (Ocean Science Journal, 2018)

Tide-related Changes in mRNA Abundance of Aromatases and Estrogen Receptors in the Ovary and Brain of the Threespot Wrasse Halichoeres trimaculatus - Dae-Ju Oh; Sung-Pyo Hur; Selma Bouchekioua; Yuki Takeuchi; Shingo Udagawa; Neelakanteswar Aluru; Yong-Ju Park; Ji-Gweon Park; Se-Jae Kim; Thomas W. Moon; Mathilakath M. Vijayan; Akihiro Takemura (Ocean Science Journal, 2018)

4DVAR Data Assimilation with the Regional Ocean Modeling System (ROMS): Impact on the Water Mass Distributions in the Yellow Sea - Joon-Ho Lee; Taekyun Kim; Ig-Chan Pang; Jae-Hong Moon (Ocean Science Journal, 2018)

Population Genetic Structure of Rock Bream (Oplegnathus fasciatus Temminck & Schlegel, 1884) Revealed by mtDNA COI Sequence in Korea and China - Hyun Suk Park; Choong-Gon Kim; Sung Kim; Yong-Joo Park; Hee-Jung Choi; Zhizhong Xiao; Jun Li; Yongshuang Xiao; Youn-Ho Lee (Ocean Science Journal, 2018)

Comparison of Measurements from Pressure-recording Inverted Echo Sounders and Satellite Altimetry in the North Equatorial Current Region of the Western Pacific - Chanhyung Jeon; Jae-Hun Park; Dong Guk Kim; Eung Kim; Dongchull Jeon (Ocean Science Journal, 2018)

Grazing Impact of the Copepod Calanus sinicus on Phytoplankton in the Northern East China Sea in Late Spring - Garam Kim; Hyung-Ku Kang (Ocean Science Journal, 2018)

Seasonal Variation of Submesoscale Flow Features in a Mesoscale Eddy-dominant Region in the East Sea - Yeon S. Chang; Byoung-Ju Choi; Young-Gyu Park (Ocean Science Journal, 2018)

An OSSE Study for Deep Argo Array using the GFDL Ensemble Coupled Data Assimilation System - You-Soon Chang; Shaoqing Zhang; Anthony Rosati; Gabriel A. Vecchi; Xiaosong Yang (Ocean Science Journal, 2018)

First Investigation of Microbial Community Composition in the Bridge (Gadeok Channel) between the Jinhae-Masan Bay and the South Sea of Korea - Jiyoung Lee; Jae-Hyun Lim; Junhyung Park; Seok-Hyun Youn; Hyun-Ju Oh; Ju-Hyoung Kim; Myung Kyum Kim; Hyeyoun Cho; Joo-Eun Yoon; Soyeon Kim; Kesavan Markkandan; Ki-Tae Park; et al. (Ocean Science Journal, 2018)

Eukaryotic Plankton Species Diversity in the Western Channel of the Korea Strait using 18S rDNA Sequences and its Implications for Water Masses - Sang-Rae Lee; Eun Hye Song; Tongsup Lee (Ocean Science Journal, 2018)

δ13C and δ15N Values of Sediment-trap Particles in the Japan and Yamato Basins and Comparison with the Core-top Values in the East/Japan Sea - Boo-Keun Khim; Shigeyoshi Otosaka; Kyung-Ae Park; Shinichiro Noriki (Ocean Science Journal, 2018)

Effect of Mudflat Trampling on Activity of Intertidal Crabs - Tae Won Kim; Sanha Kim; Jung-Ah Lee (Ocean Science Journal, 2018)

Effects of Thermal Stress on the mRNA Expression of SOD, HSP90, and HSP70 in the Spotted Sea Bass (Lateolabrax maculatus) - Moon-Kyeong Shin; Ho-Ra Park; Won-Jun Yeo; Kyung-Nam Han (Ocean Science Journal, 2018)

In-situ Measured Carbon and Nitrogen Uptake Rates of Melt Pond Algae in the Western Arctic Ocean, 2014 - Ho Jung Song; Kwanwoo Kim; Jae Hyung Lee; So Hyun Ahn; Houng-Min Joo; Jin Young Jeong; Eun Jin Yang; Sung-Ho Kang; Mi Sun Yun; Sang Heon Lee (Ocean Science Journal, 2018)

Genus-specific PCR Primers Targeting Intracellular Parasite Euduboscquella (Dinoflagellata: Syndinea) - Jae-Ho Jung; Jung Min Choi; Young-Ok Kim (Ocean Science Journal, 2018)

Provenance of Fine-grained Sediments in the Inner Shelf of the Korea Strait (South Sea), Korea - In kwon Um; Man Sik Choi; Sung Ho Bae; Yunho Song; Gee Soo Kong (Ocean Science Journal, 2018)

Development and Application of an Acoustic System for Harmful Algal Blooms (HABs, Red Tide) Detection using an Ultrasonic Digital Sensor - Hansoo Kim; Donhyug Kang; Seung Won Jung (Ocean Science Journal, 2018)

An Ephemeral Dinoflagellate Bloom during Summer Season in Nearshore Water of Puri, East Coast of India - Sanjiba Kumar Baliarsingh; Rashmin Dwivedi; Aneesh A. Lotliker; Reeta Jayashankar; Biraja Kumar Sahu; Suchismita Srichandan; Alakes Samanta; Chandanlal Parida; Tummala Srinivasakumar; Kali Charan Sahu (Ocean Science Journal, 2018)

Feeding Relationships among Six Seagrass-associated Fishes in the Northeastern Gwangyang Bay, Southern Korea - Joo Myun Park; Seok Nam Kwak; In-Seong Han (Ocean Science Journal, 2018)

Seabed Gradient Controlling Onshore Transport Rates of Surf Sand during Beach Retreat by Sea Level Rise - Hee Jun Lee; Hi-Il Yi (Ocean Science Journal, 2018)

Target-strength Measurements of Sandfish Arctoscopus japonicus - Eun-A Yoon; Kyounghoon Lee; Wooseok Oh; Junghwa Choi; Kangseok Hwang; Myounghee Kang (Ocean Science Journal, 2018)

Interannual Variation of Surface Circulation in the Japan/East Sea due to External Forcings and Intrinsic Variability - Byoung-Ju Choi; Seong Hun Cho; Hee Seok Jung; Sang-Ho Lee; Do-Seong Byun; Kyungman Kwon (Ocean Science Journal, 2018)

Behavior and Frequency Analysis of Aurelia aurita by Using in situ Target Strength at a Port in Southwestern Korea - Eun-A Yoon; Doo-Jin Hwang; Jinho Chae; Won Duk Yoon; Kyounghoon Lee (Ocean Science Journal, 2018)

Sources and distribution of allochthonous organic matter in surface sediment from the Seomjin River to the southern inner shelf of Korea - Adegoke Olugboyega Badejo; Sangmin Hyun; Wonnyon Kim; Se-Jong Ju; Bareum Song (Ocean Science Journal, 2017)

Phylogenetic, histological and age determination for investigation of non-native tropical black-lip pearl oyster, Pinctada margaritifera, settled in jeju, Korea - Chulhong Oh; Jin-Kyoung Kim; Young-Baek Son; Se-Jong Ju; Hee-Do Jeung; Hyun-Sung Yang; Kwang-Sik Choi; Gilles Le Moullac; Do-Hyung Kang (Ocean Science Journal, 2017)

Behavioral patterns and in-situ target strength of the hairtail (Trichiurus lepturus) via coupling of scientific echosounder and acoustic camera data - Kangseok Hwang; Eun-A Yoon; Sukyung Kang; Hyungkee Cha; Kyounghoon Lee (Ocean Science Journal, 2017)

A new species of the genus Ammonicera (Prosobranchia, Omalogyridae) in a coralline algae community from Jeju Island, off the south coast of Korea - Tsukasa Waki; Emilio Rolán; Ronald G. Noseworthy; Hyun-Sil Kang; Kwang-Sik Choi (Ocean Science Journal, 2017)

Environmental variability and chum salmon production at the northwestern Pacific Ocean - Suam Kim; Sukyung Kang; Ju Kyoung Kim; Minkyoung Bang (Ocean Science Journal, 2017)

Effect of different wavelengths of light on the antioxidant and immunity status of juvenile rock bream, Oplegnathus fasciatus, exposed to thermal stress - Jong Ryeol Choe; Yoon Sub Shin; Ji Yong Choi; Tae Hwan Kim; Min-Min Jung; Cheol Young Choi (Ocean Science Journal, 2017)

Stratification and salt-wedge in the Seomjin river estuary under the idealized tidal influence - Jin Hwan Hwang; Dongmin Jang; Yong Hoon Kim (Ocean Science Journal, 2017)

Spawning characteristics of Clupea pallasii in the coastal waters off Gyeongnam, Korea, during spawning season - Yong-Deuk Lee; Jung Hwa Choi; Seong Yong Moon; Sun Kil Lee; Woo-Seok Gwak (Ocean Science Journal, 2017)

Concentrations of heavy metals in marine wild fishes captured from the southern sea of Korea and associated health risk assessments - Dong-Woon Hwang; Seong-Soo Kim; Seong-Gil Kim; Dong-Sun Kim; Tae-Hoon Kim (Ocean Science Journal, 2017)

Environmental gradients regulate the spatio-temporal variability of phytoplankton assemblages in the Can Gio Mangrove Biosphere Reserve, Vietnam - Thanh-Luu Pham (Ocean Science Journal, 2017)

Effects of temperature and salinity on the asexual reproduction of Nemopilema nomurai (Scyphozoa: Rhizostomeae) - Hye Eun Lee; Chang Hoon Han; ByeongHo Kim; Won Duk Yoon (Ocean Science Journal, 2017)

Sediment reworking by a polychaete, Perinereis aibuhitensis, in the intertidal sediments of the Gomso Bay, Korea - Bon Joo Koo; Jaehwan Seo (Ocean Science Journal, 2017)

Annual gametogenesis and reproductive effort of the limpet Cellana grata (Gould, 1859) (Gastropoda: Nacellidae) in a rocky intertidal beach at Ulleungdo Island off the east coast of Korea - Hyun-Sung Yang; Do-Hyung Kang; Heung-Sik Park; Kwang-Sik Choi (Ocean Science Journal, 2017)

Erratum to: Concentrations of heavy metals in marine wild fishes captured from the Southern Sea of Korea and associated health risk assessments - Dong-Woon Hwang; Seong-Soo Kim; Seong-Gil Kim; Dong-Sun Kim; Tae-Hoon Kim (Ocean Science Journal, 2017)

Phytoplankton and bacterial community structures and their interaction during red-tide phenomena - Mona Mohamed Ismail; Hassan Abd Allah Ibrahim (Ocean Science Journal, 2017)

Surface circulation and vertical structure of current off the Keum River estuary, Korea in later spring 2008 - Sang-Ho Lee; Moon-Jin Kim; Chang-Soo Kim; Byoung-Ju Choi; Hong-Bae Moon (Ocean Science Journal, 2017)

Monitoring of 45 pesticides in Lebanese surface water using Polar Organic Chemical Integrative Sampler (POCIS) - Al Ashi Aisha; Wael Hneine; Samia Mokh; Marie-Hélène Devier; Hélèn Budzinski; Farouk Jaber (Ocean Science Journal, 2017)

Temporal variation of intertidal seagrass in southern China (2008–2014) - Guanglong Qiu; Frederick T. Short; Hangqing Fan; Guohua Liu (Ocean Science Journal, 2017)

Seasonal variations in the community structures of macrobenthic fauna and their health status in an estuarine bay, Gwangyang Bay in Korea - Jin-Young Seo; Soon-Mo An; Dhong-il Lim; Jin-Woo Choi (Ocean Science Journal, 2017)

The reproductive cycle of the humbug damselfish Dascyllus aruanus according to the changes in lunar phase in Micronesia - Ji Yong Choi; Na Na Kim; Dae-Won Lee; Young-Ung Choi; Cheol Young Choi (Ocean Science Journal, 2017)

Tissue-specific changes in OGG1 and SOD mRNA expression caused by NaOCl exposure in black seabream (Acanthopagrus schlegelii) - Ho-Ra Park; Yong Kim; Won-Jun Yeo; Ji-Hye Kim; Kyung-Nam Han (Ocean Science Journal, 2017)

Large temporal changes in contributions of groundwater-borne nutrients to coastal waters off a volcanic island - Hyung-Mi Cho; Guebuem Kim (Ocean Science Journal, 2017)

A rapid assessment survey of invasive species of macrobenthic invertebrates in Korean waters - Chul Park; Sung-Tae Kim; Jae-Sang Hong; Keun-Hyung Choi (Ocean Science Journal, 2017)

Morphological identification of Alexandrium species (Dinophyceae) from Jinhae-Masan Bay, Korea - Eun Song Kim; Zhun Li; Seok Jin Oh; Yang Ho Yoon; Hyeon Ho Shin (Ocean Science Journal, 2017)

Fossil diatom assemblages as paleoecological indicators of paleo-water environmental change in the Ulleung Basin, East Sea, Republic of Korea - Suk Min Yun; Taehee Lee; Seung Won Jung; Joon Sang Park; Jin Hwan Lee (Ocean Science Journal, 2017)

Characterization of the coccoid cyanobacterium Myxosarcina sp. KIOST-1 isolated from mangrove forest in Chuuk State, Federated States of Micronesia - Ji Hyung Kim; JunMo Lee; Md-Abu Affan; Dae-Won Lee; Do-Hyung Kang (Ocean Science Journal, 2017)

Recent increase in surface fCO2 in the western subtropical North Pacific - Dongseon Kim; Yujeong Choi; Tae-Wook Kim; Geun-Ha Park (Ocean Science Journal, 2017)

Estimation of net ecosystem metabolism of seagrass meadows in the coastal waters of the East Sea and Black Sea using the noninvasive eddy covariance technique - Jae Seong Lee; Dong-Jin Kang; Elitsa Hineva; Violeta Slabakova; Valentina Todorova; Jiyoung Park; Jin-Hyung Cho (Ocean Science Journal, 2017)

Removal rate and releases of polybrominated diphenyl ethers in two wastewater treatment plants, Korea - Hyo Jin Lee; Gi Beum Kim (Ocean Science Journal, 2017)

Growth and reproduction of the Japanese mantis shrimp, Oratosquilla oratoria (De Haan 1844) in the coastal area of Tongyeong, Korea - SeongEun Kim; HanJu Kim; HoJin Bae; Hyeong-Gi Kim; Chul-Woong Oh (Ocean Science Journal, 2017)

Winter thermal inversion and Trichodesmium dominance in north-western Bay of Bengal - Biraja Kumar Sahu; Sanjiba Kumar Baliarsingh; Aneesh A. Lotliker; Chandanlal Parida; Suchismita Srichandan; Kali Charan Sahu (Ocean Science Journal, 2017)

The correlation between bioaccumulation and pattern of stress-related genes expression of black sea bream (Acanthopagrus schlegeli) by cadmium exposure - Yong Kim; Ho-Ra Park; Won-Jun Yeo; Ji-Hye Kim; Kyung-Nam Han (Ocean Science Journal, 2017)

First record of Sinocorophium homoceratum (Yu, 1938) (Crustacea, Amphipoda, Corophiidae) from Korea - Ara Ko; Kwan Ha Park; Soo-Gun Jo (Ocean Science Journal, 2017)

Application of the coral health chart to determine bleaching status of Acropora downingi in a subtropical coral reef - Mahshid Oladi; Mohammad Reza Shokri; Hassan Rajabi-Maham (Ocean Science Journal, 2017)

A simple method of correction for profile-length water-column height variations in high-resolution, shallow-water seismic data - Hyeonju Kim; Gwang Hoon Lee; Bo Yeon Yi; Youngho Yoon; Kyong-O Kim; Han-Joon Kim; Sang Hoon Lee (Ocean Science Journal, 2017)

Tracing the origin of Pb using stable Pb isotopes in surface sediments along the Korean Yellow Sea coast - Jong-Kyu Park; Man-Sik Choi; Yunho Song; Dhong-Il Lim (Ocean Science Journal, 2017)

Estimation of spawning area of Pisodonophis sangjuensis Ji and Kim, 2011 (Pisces: Ophichthidae) based on leptocephali size and distribution - Hwan-Sung Ji; Kangseok Hwang; Jung Hwa Choi; Hyung-Kee Cha; Jin-Koo Kim (Ocean Science Journal, 2017)

Zostera marina seed burial can be enhanced by Manila clam Ruditapes philippinarum: A microcosm study - Chang-Jun Li; Wen-Tao Li; Jianying Liu; Xiumei Zhang; Peidong Zhang (Ocean Science Journal, 2017)

The spatial and seasonal variation of trace metals in coastal seawater and soft tissue of Chthamalus montagui around the northwest coast of Portugal - Pedro A. Reis; Maria Antónia Salgado; Vitor Vasconcelos (Ocean Science Journal, 2017)

Oceanic response to Typhoon Nari (2007) in the East China Sea - Kyung-Hee Oh; Seok Lee; Sok-Kuh Kang; Kyu-Min Song (Ocean Science Journal, 2017)

Biomonitoring of trace metals using transplanted mussels, Mytilus galloprovincialis, in coastal areas around Ulsan and Onsan Bays, Korea - Chan-Kook Kim; Man Sik Choi (Ocean Science Journal, 2017)

Adaptation responses of individuals to environmental changes in the ciliate Euplotes crassus - Se-Joo Kim; Jin-Hyoung Kim; Se-Jong Ju (Ocean Science Journal, 2017)

Impact of estuary barrage construction on fish assemblages in the lower part of a river and the role of fishways as a passage - Ju-Duk Yoon; Jeong-Hui Kim; Sang-Hyeon Park; Eve Kim; Min-Ho Jang (Ocean Science Journal, 2017)

New polymorphic microsatellite markers derived from hemocyte cDNA library of Manila clam Ruditapes philippinarum challenged by the protozoan parasite Perkinsus olseni - Hyun-Sil Kang; Hyun-Ki Hong; Kyung-Il Park; Moonjae Cho; Seok-Hyun Youn; Kwang-Sik Choi (Ocean Science Journal, 2017)

Erratum to: Effects of environmental and biological conditions on the recruitment and growth of the Manila Clam Ruditapes philippinarum on the West Coast of Korea - Sang Lyeol Kim; Soon Hyun Kwon; Hyung-Gon Lee; Ok Hwan Yu (Ocean Science Journal, 2017)

A modeling study of the characteristics and mechanism of the westward coastal current during summer in the northwestern South China Sea - Yang Ding; Xianwen Bao; Zhigang Yao; Cong Zhang; Kai Wan; Min Bao; Ruixiang Li; Maochong Shi (Ocean Science Journal, 2017)

Reproductive biology of blood cockle Anadara granosa (Bivalvia: Arcidae) in the northern region of the Strait of Malacca - Munawar Khalil; Zulfigar Yasin; Tan Shau Hwai (Ocean Science Journal, 2017)

Long-term changes in rocky intertidal macrobenthos during the five years after the Hebei Spirit oil spill, Taean, Korea - Yun-Hwan Jung; Henug-Sik Park; Kon-Tak Yoon; Hyung-June Kim; Won-Joon Shim (Ocean Science Journal, 2017)

Seasonal and interannual variation in mesozooplankton community structure off Tongyeong, southeastern coast of Korea, from 2011 to 2014 - Garam Kim; Hyung-Ku Kang; Jung-Goo Myoung (Ocean Science Journal, 2017)

Spatio-temporal variability in sea surface temperatures for the Yellow Sea based on MODIS dataset - Chunli Liu; Qiwei Sun; Qianguo Xing; Zhenlin Liang; Yue Deng; Lixin Zhu (Ocean Science Journal, 2017)

Fugacity analysis of polycyclic aromatic hydrocarbons between microplastics and seawater - Hwang Lee; Sein Chang; Seung-Kyu Kim; Jung-Hwan Kwon (Ocean Science Journal, 2017)

Potential for heavy metal (copper and zinc) removal from contaminated marine sediments using microalgae and light emitting diodes - Hyeong Kyu Kwon; Jin Young Jeon; Seok Jin Oh (Ocean Science Journal, 2017)

Effects of environmental and biological conditions on the recruitment and growth of the Manila clam Ruditapes philippinarum on the west coast of Korea - Sang Lyeol Kim; Soon Hyun Kwon; Hyung-Gon Lee; Ok Hwan Yu (Ocean Science Journal, 2017)

Acoustic monitoring using bamboo set net in the Southern Sea of Korea - Hyungbeen Lee; Kyounghoon Lee; Hyoung Sul La; Yongsu Yang; Pyungkwan Kim (Ocean Science Journal, 2017)

Characteristics of drift pumice from New Caledonia beaches - Kirsten Ngaire Nicholson; Ariel Stewart (Ocean Science Journal, 2016)

Modeling the largest inflow of Changjiang freshwater into the Yellow Sea in 2012 with particle-tracking experiment - Ji-Seok Hong; Jae-Hong Moon; Joon-Ho Lee; Ig-Chan Pang (Ocean Science Journal, 2016)

Climate-change driven range shifts of anchovy biomass projected by bio-physical coupling individual based model in the marginal seas of East Asia - Sukgeun Jung; Ig-Chan Pang; Joon-ho Lee; Kyunghwan Lee (Ocean Science Journal, 2016)

The identity of ‘Berkeleya scopulorum’ from Northeast Asia: Report on Climaconeis mabikii sp. nov. from temperate marine waters with notes on biogeography of the genus - Jinsoon Park; Jin Hwan Lee; Jong Seong Khim (Ocean Science Journal, 2016)

Carbon and nitrogen dynamics of the intertidal seagrass, Zostera japonica, on the southern coast of the Korean peninsula - Jong-Hyeob Kim; Seung Hyeon Kim; Young Kyun Kim; Kun-Seop Lee (Ocean Science Journal, 2016)

Effects of temperature on growth, photophysiology, Rubisco gene expression in Prorocentrum donghaiense and Karenia mikimotoi - Anglu Shen; Zengling Ma; Keji Jiang; Daoji Li (Ocean Science Journal, 2016)

Metagenomic characterization of viral communities in Goseong Bay, Korea - Jinik Hwang; So Yun Park; Mirye Park; Sukchan Lee; Yeonhwa Jo; Won Kyong Cho; Taek-Kyun Lee (Ocean Science Journal, 2016)

Haeundae Beach in Korea: Seasonal-to-decadal wave statistics and impulsive beach responses to typhoons - Hee Jun Lee; Jong-Dae Do; Sun Sin Kim; Won-Kyung Park; Kicheon Jun (Ocean Science Journal, 2016)

A review of the effects of particle types on oil-suspended particulate matter aggregate formation - Andrew Loh; Un Hyuk Yim (Ocean Science Journal, 2016)

Age determination and growth rate of Mactra chinensis (Bivalvia: Mactridae) by external rings and chondrophore growth bands - Jung Yeon Kim; Jong Hun Na; Chul-Woong Oh (Ocean Science Journal, 2016)

Growth dynamics of the deep-water Asian eelgrass, Zostera asiatica, in the eastern coastal waters of Korea - Jung-Im Park; Jong-Hyeob Kim; Su Hyun Park (Ocean Science Journal, 2016)

Morphology and phylogeny of Triadinium polyedricum (Pouchet) Dodge (Dinophyceae) from Korean coastal waters - Hyeon Ho Shin; Zhun Li; Eun Song Kim; Joo Yeon Youn; Seul Gi Jeon; Seok Jin Oh; Weol-Ae Lim (Ocean Science Journal, 2016)

Latitudinal change in benthic foraminiferal fauna by ITCZ movement along the ~131°W transect in the equatorial Pacific Ocean - Hiroyuki Takata; Chan Min Yoo; Hyung Jeek Kim; Boo-Keun Khim (Ocean Science Journal, 2016)

A new record of pasiphaeid shrimp of the genus Pasiphaea (Crustacea: Decapoda: Caridea) in Korean waters - Jung Nyun Kim; Jung Hwa Choi; Hyun-su Jo (Ocean Science Journal, 2016)

Molecular phylogeny of the genus Chondracanthus (Rhodophyta), focusing on the resurrection of C. okamurae and the description of C. cincinnus sp. nov. - Mi Yeon Yang; Myung Sook Kim (Ocean Science Journal, 2016)

Delimiting the species Neosiphonia yendoi (Rhodomelaceae, Rhodophyta) based on COI and rbcL genetic variation in Korea and Japan - Byeongseok Kim; Mi Yeon Yang; Myung Sook Kim (Ocean Science Journal, 2016)

Retrospective analysis of diversity and species composition of marine macroalgae of Hainan Island (China) - Eduard A. Titlyanov; Tamara V. Titlyanova; Bangmei Xia; Inka Bartsch (Ocean Science Journal, 2016)

Responses of meiofauna and nematode communities to crude oil contamination in a laboratory microcosm experiment - Teawook Kang; Je Hyeok Oh; Jae-Sang Hong; Dongsung Kim (Ocean Science Journal, 2016)

Temporal changes in the geographic distribution of two clam species Meretrix lusoria and M. petechialis along the coast of Japan and South Korea - Shin’ichi Sato; Yoshitaka Kaneko; Hiroshi Torii; Jae-Sang Hong (Ocean Science Journal, 2016)

Distribution of chaetognaths (Aphragmophora: Sagittidae) in Korean waters - Bo Ram Lee; Hyun Woo Kim; Wongyu Park (Ocean Science Journal, 2016)

Long-term variations in macrobenthic community diversity (species number) in the Chokchon macrotidal flat, Incheon, Korea - Jae-Won Yoo; Hyun-Jung Lee; Jae-Sang Hong (Ocean Science Journal, 2016)

Effect-directed analysis: Current status and future challenges - Seongjin Hong; John P. Giesy; Jung-Suk Lee; Jong-Hyeon Lee; Jong Seong Khim (Ocean Science Journal, 2016)

Special issue of the Second Asian Marine Biology Symposium — Toward the Blue Sea, Asian Seas in a changing world - Jae-Sang Hong; Hiroaki Tsutsumi (Ocean Science Journal, 2016)

In-situ measured primary productivity of ice algae in Arctic sea ice floes using a new incubation method - Ho Jung Song; Jae Hyung Lee; Gawn Woo Kim; So Hyun Ahn; Houng-Min Joo; Jin Young Jeong; Eun Jin Yang; Sung-Ho Kang; Sang Heon Lee (Ocean Science Journal, 2016)

Boldness in a deep sea hermit crab to simulated tactile predator attacks is unaffected by ocean acidification - Tae Won Kim; James P. Barry (Ocean Science Journal, 2016)

Carbonic anhydrase I in a cartilaginous fish, the shortspine spurdog (Squalus mitsukurii) - Soo Cheol Kim; Kanij Rukshana Sumi; Jung Woo Kim; Myeong Rak Choi; Byung Hwa Min; Kang Hee Kho (Ocean Science Journal, 2016)

Population dynamics of the solitary ascidian Herdmania momus (Savignyi, 1816) in Jeju Island, Korea - Chang Ho Yi; Jeong Ha Kim (Ocean Science Journal, 2016)

Age and growth of filefish, Thamnaconus modestus (Günther, 1877) off the Jeju Island of Korea - AhReum Kim; HoJin Bae; Hyeong-Gi Kim; Chul-Woong Oh (Ocean Science Journal, 2016)

Growth of gametophytes and sporophytes of Grateloupia subpectinata (Rhodophyta) in culture - Ratih Ida Adharini; Hyung Geun Kim (Ocean Science Journal, 2016)

The feasibility of assessing the diets of minke whale (Balaenoptera acutorostrata) in the East Sea through fatty acid composition in blubber and stable isotopic ratio of skin - Ah-Ra Ko; Se-Jong Ju; Seok-Gwan Choi; Kyung-Hoon Shin (Ocean Science Journal, 2016)

Dracograllus trukensis sp. nov. (Draconematidae: Nematoda) from a seagrass bed (Zostera spp.) in Chuuk Islands, Micronesia, Central Western Pacific Ocean - Wongi Min; Dongsung Kim; Wilfrida Decraemer; Hyun Soo Rho (Ocean Science Journal, 2016)

Thermal effects on the growth and fatty acid composition of four harmful algal bloom species: Possible implications for ichthyotoxicity - Bonggil Hyun; Se-Jong Ju; Ah-Ra Ko; Keun-Hyung Choi; Seung Won Jung; Pung-Guk Jang; Min-Chul Jang; Chang Ho Moon; Kyoungsoon Shin (Ocean Science Journal, 2016)

Phylogenetic relationship between symbionts of tubeworm Lamellibrachia satsuma and the sediment microbial community in Kagoshima Bay - Ajit Kumar Patra; Hyun Hee Cho; Yong Min Kwon; Kae Kyoung Kwon; Takako Sato; Chiaki Kato; Sung Gyun Kang; Sang-Jin Kim (Ocean Science Journal, 2016)

Rare earth element fingerprints in Korean coastal bay sediments: Association with provenance discrimination - Jeongwon Kang; Han Jun Woo; Seok Jang; Kap-Sik Jeong; Hoi-Soo Jung; Ha Gi Hwang; Jun-Ho Lee; Jin Hyung Cho (Ocean Science Journal, 2016)

Molecular phylogeny of the families Pleuronectidae and Poecilopsettidae (PISCES, Pleuronectiformes) from Korea, with a Proposal for a new classification - Hwan-Sung Ji; Jin-Koo Kim; Byung-Jik Kim (Ocean Science Journal, 2016)

First Record of Porpita porpita (Cnidaria: Hydrozoa) from the coral reef ecosystem, Bangladesh - M. Shah Nawaz Chowdhury; S. M. Sharifuzzaman; Sayedur Rahman Chowdhury; Md. Rashed-Un-Nabi; M. Shahadat Hossain (Ocean Science Journal, 2016)

First record of massive blooming of benthic diatoms and their association with megabenthic filter feeders on the shallow seafloor of an Antarctic Fjord: Does glacier melting fuel the bloom? - In-Young Ahn; Hye-Won Moon; Misa Jeon; Sung-Ho Kang (Ocean Science Journal, 2016)

Holocene depositional patterns of the subaqueous Nakdong Delta on the Korea Strait with respect to sequence stratigraphy - Dong-Lim Choi; Yong-Kuk Lee; Dong-Hyeok Shin; Han-Jun Woo (Ocean Science Journal, 2016)

Accuracy improvement of the radar backscatter simulation from sea surface covered by oil slick using fetch-dependent waveheight spectrum: Comparison with the 2007 Heibei Spirit Case in the Yellow Sea - Tae-Ho Kim; Chan-Su Yang; Kazuo Ouchi (Ocean Science Journal, 2016)

Molecular Cloning, Characterization, and Expression of a Catalase Gene in the Japanese Scallop Mizuhopecten yessoensis Induced in the Presence of Cadmium - Jialong Gao; Shoichiro Ishizaki; Yuji Nagashima (Ocean Science Journal, 2016)

Tidal asymmetry in a tidal creek with mixed mainly semidiurnal tide, Bushehr Port, Persian Gulf - Seyed Taleb Hosseini; Vahid Chegini; Masoud Sadrinasab; Seyed Mostafa Siadatmousavi; Sadegh Yari (Ocean Science Journal, 2016)

The effect of tides on the volume of sea ice in the Arctic Ocean - Mi Ok Kwon; Ho Jin Lee (Ocean Science Journal, 2016)

Review of inorganic nitrogen transformations and effect of global climate change on inorganic nitrogen cycling in ocean ecosystems - Haryun Kim (Ocean Science Journal, 2016)

Morphological differences between three groups of Luciogobius guttatus on the Korean Peninsula - Byung-Gi Kim; Maeng-Jin Kim; Kyung-Nam Han (Ocean Science Journal, 2016)

Genetic stock identification of immature chum salmon (Oncorhynchus keta) in the western Bering Sea, 2004 - Minho Kang; Suam Kim; Loh-Lee Low (Ocean Science Journal, 2016)

Application of a partial least-squares regression model to retrieve chlorophyll-a concentrations in coastal waters using hyper-spectral data - Kimberly Ryan; Khalid Ali (Ocean Science Journal, 2016)

Monitoring trace metals in seawater using a diffusive gradient in thin film probe in Ulsan Bay, East Sea, Korea: Comparison with transplanted mussels - Mi Seon Kim; Man Sik Choi; Chan-Kook Kim (Ocean Science Journal, 2016)

Above-ground biomass estimation of tuberous bulrush (Bolboschoenus planiculmis) in mudflats using remotely sensed multispectral image - Ji Yoon Kim; Ran-Young Im; Yuno Do; Gu-Yeon Kim; Gea-Jae Joo (Ocean Science Journal, 2016)

Suspension of sediment particles over a ripple due to turbulent convection under unsteady flow conditions - Yeon S. Chang; Young-Gyu Park (Ocean Science Journal, 2016)

Evaluation of ADCP backscatter inversion to suspended sediment concentration in estuarine environments - Hyo-Bong Park; Guan-hong Lee (Ocean Science Journal, 2016)

Shifts in multi-decadal sea level trends in the East/Japan Sea over the past 60 years - Jae-Hong Moon; Joonho Lee (Ocean Science Journal, 2016)

Modeling the underwater light field fluctuations in coastal oceanic waters: Validation with experimental data - Balasubramanian Sundarabalan; Palanisamy Shanmugam; Yu-Hwan Ahn (Ocean Science Journal, 2016)

Vertical distribution of giant jellyfish, Nemopilema nomurai using acoustics and optics - Seonghun Kim; Kyounghoon Lee; Won Duk Yoon; Hyungbeen Lee; Kangseok Hwang (Ocean Science Journal, 2016)

High mortality and poor growth of green mussels, Perna viridis, in high chlorophyll-a environment - Tan Kar Soon; Delta Jenetty Denil; Julian Ransangan (Ocean Science Journal, 2016)

An assemblage of mollusks associated with the high latitude scleractinian coral Alveopora japonica (Eguchi 1968) in Jeju Island, off the south coast of Korea - Ronald G. Noseworthy; Hyun-Ki Hong; Shashank Keshavmurthy; Hee-Jung Lee; Hee-Do Jeung; Se-Jong Ju; Jong-Bin Kim; Sukgeun Jung; Kwang-Sik Choi (Ocean Science Journal, 2016)

Implication of salt marsh foraminiferal assemblages in Suncheon Bay, South Korea - Da Un Jeong; Yeon Gyu Lee; Sora Kang; Shin Kim; Jung Sick Lee (Ocean Science Journal, 2016)

Variability of sensible heat flux over the Bay of Bengal and its connection to Indian Ocean Dipole events - Ajitha Cyriac; Tarumay Ghoshal; Patel Ramkrushnbhai Shaileshbhai; Arun Chakraborty (Ocean Science Journal, 2016)

Population structure of the Korean gizzard shad, Konosirus punctatus (Clupeiformes, Clupeidae) using multivariate morphometric analysis - Se Hun Myoung; Jin-Koo Kim (Ocean Science Journal, 2016)

Morphological characteristics and distribution of Pleuronectidae (Pisces) eggs in the western margin of the East Sea - Soo Jeong Lee; Jin-Koo Kim (Ocean Science Journal, 2016)

The ecological importance of the dwarf seagrass Zostera japonica in intertidal areas on the southern coast of Korea - Sun Kyeong Choi; Sangil Kim; Kun-Seop Lee; Wen-Tao Li; Sang Rul Park (Ocean Science Journal, 2016)

Modeling the changes in the concentration of aromatic hydrocarbons from an oil-coated gravel column - Jee-Hyun Jung; Hyun-Joong Kang; Moonkoo Kim; Un Hyuk Yim; Joon Geon An; Won Joon Shim; Jung-Hwan Kwon (Ocean Science Journal, 2015)

Constraints on biotic and abiotic role in the formation of Fe-Si oxides from the PACMANUS hydrothermal field - Baoju Yang; Zhigang Zeng; Haiyan Qi; Xiaoyuan Wang; Yao Ma; Kunbo Rong (Ocean Science Journal, 2015)

Accumulation features of arsenic species in various fishes collected from coastal cities in Korea - Sung-Deuk Choi; Hee-Sik Son; Minkyu Choi; Min-Kyu Park (Ocean Science Journal, 2015)

Assessment of the governance system for the management of the East Sea-Jung dumping site, Korea through analysis of heavy metal concentrations in bottom sediments - Ki-Hoon Song; Ki-Young Choi; Chang-Joon Kim; Young-Il Kim; Chang-Soo Chung (Ocean Science Journal, 2015)

Practical considerations for the segmented-flow analysis of nitrate and ammonium in seawater and the avoidance of matrix effects - Tae Keun Rho; Stephen Coverly; Eun-Soo Kim; Dong-Jin Kang; Sung-Hyun Kahng; Tae-Hee Na; Sung-Rok Cho; Jung-Moo Lee; Cho-Rong Moon (Ocean Science Journal, 2015)

Effect of phenol on embryo development and expression of metallothionein in the sea urchin Hemicentrotus pulcherrimus - Un-Ki Hwang; Ju-Wook Lee; Hyang-Mi Ryu; Ju-Chan Kang; Han Seung Kang (Ocean Science Journal, 2015)

The simulation of a storm surge and wave due to Typhoon Sarah using an integrally coupled tide-surge-wave model of the Yellow and East China Seas - Jin-Hee Yuk; Kyeong Ok Kim; Byung Ho Choi (Ocean Science Journal, 2015)

Marine environmental impact assessment of abalone, Haliotis discus hannai, cage farm in Wan-do, Republic of Korea - Hyun-Taik Oh; Rae-Hong Jung; Yoon-Sik Cho; Dong-Woon Hwang; Yong-Min Yi (Ocean Science Journal, 2015)

First report on the occurrence of the comb pen shell, Atrina pectinata (Linnaeus, 1767) (Bivalvia: Pinnidae) in Ulleungdo Island in the East Sea: Ecology and molecular identification of the species using COI gene sequence - Hyun-Sung Yang; Hyun-Sil Kang; Heung-Sik Park; Choong Hwan Noh; Eui-Young Jeong; Kwang-Sik Choi (Ocean Science Journal, 2015)

Demersally drifting invertebrates from Kongsfjorden, Svalbård (Arctic Ocean)–a comparison of catches from drift-pump and drift-nets - Hans-Uwe Dahms; Hyoung-Min Joo; Jae Hyung Lee; Mi Sun Yun; So Hyun Ahn; Sang Heon Lee (Ocean Science Journal, 2015)

Prokaryotic community composition revealed by denaturing gradient gel electrophoresis in the East Sea - Gwang Il Jang; Dong Han Choi (Ocean Science Journal, 2015)

A review on the Holocene evolution of an inner-shelf mud deposit in the southeastern Yellow Sea: the Huksan Mud Belt - Hee Jun Lee (Ocean Science Journal, 2015)

Effect of abalone farming on sediment geochemistry in the Shallow Sea near Wando, South Korea - Jeongwon Kang; Yeon Gyu Lee; Da Un Jeong; Jung Sick Lee; Yang Ho Choi; Yun Kyung Shin (Ocean Science Journal, 2015)

Emergy evaluation of management measures for derelict fishing gears in Korea - Sunwook Hong; Jongmyoung Lee; Daeseok Kang (Ocean Science Journal, 2015)

Coastal erosion problem, modelling and protection - Nihal Yılmaz; Lale Balas; Asu İnan (Ocean Science Journal, 2015)

Rates of total oxygen uptake of sediments and benthic nutrient fluxes measured using an in situ autonomous benthic chamber in the sediment of the slope off the southwestern part of Ulleung Basin, East Sea - Jae Seong Lee; Sung-Uk An; Young-Gyu Park; Eunsoo Kim; Dongseon Kim; Jung No Kwon; Dong-Jin Kang; Jae-Hoon Noh (Ocean Science Journal, 2015)

Comparison of two cases of strong increase in the bottom temperature in the Yellow Sea in winter - Lian-Gang Lü; Guang-Bing Yang; Guansuo Wang; Zong-Wei Liu; Ying Jiang; Chunmei Yang; Chao Zhang (Ocean Science Journal, 2015)

Larval distribution pattern of Muraenesox cinereus (Anguilliformes: Muraenesocidae) leptocephali in waters adjacent to Korea - Hwan-Sung Ji; Jin-Koo Kim; Taeg Yun Oh; Kwang Ho Choi; Jung Hwa Choi; Young Il Seo; Dong Woo Lee (Ocean Science Journal, 2015)

Can the halophilic ciliate Fabrea salina be used as a bio-control of microalgae blooms in solar salterns? - Hyun Pyo Hong; Joong Ki Choi (Ocean Science Journal, 2015)

Phenology of host Chondrus ocellatus with filamentous green endophyte infection - Hang Gil Choi; Changsong Kim; Young Sik Kim; Soon Jeong Lee; Myoung Ae Park; Ki Wan Nam (Ocean Science Journal, 2015)

Potential overestimation in primary and new productions of phytoplankton from a short time incubation method - Sang Heon Lee; HuiTae Joo; Jang Han Lee; Jae Joong Kang; Jae-Hyun Lim; Mi Sun Yun; Jae Hyung Lee; Chang-Keun Kang (Ocean Science Journal, 2015)

Growth and physiological responses of a tropical toxic marine microgalga Heterosigma akashiwo (Heterokontophyta: Raphidophyceae) from Singapore waters to varying nitrogen sources and light conditions - Jerome Wai Kit Kok; Darren Chong Jinn Yeo; Sandric Chee Yew Leong (Ocean Science Journal, 2015)

Variation of flow properties during a collision event of two mesoscale eddies in the Gulf Stream region from numerical simulation - Yeon S. Chang; Young-Gyu Park (Ocean Science Journal, 2015)

Antioxidative-related genes expression following perfluorooctane sulfonate (PFOS) exposure in the intertidal mud crab, Macrophthalmus japonicus - Kiyun Park; Chamilani Nikapitiya; Tae-Soo Kwak; Ihn-Sil Kwak (Ocean Science Journal, 2015)

Evidence for ontogenetic feeding strategies in four calanoid copepods in the East Sea (Japan Sea) in summer, revealed by stable isotope analysis - Dong-Hoon Im; Jin Hee Wi; Hae-Lip Suh (Ocean Science Journal, 2015)

Effect of lower pH on settlement and development of coral, Pocillopora damicornis (Linnaeus, 1758) - Voranop Viyakarn; Wipada Lalitpattarakit; Narainrit Chinfak; Suppakarn Jandang; Pataporn Kuanui; Somkiat Khokiattiwong; Suchana Chavanich (Ocean Science Journal, 2015)

Heavy metal resistant endophytic fungi isolated from Nypa fruticans in Kuching Wetland National Park - Jenny Choo; Nuraini Binti Mohd Sabri; Daniel Tan; Aazani Mujahid; Moritz Müller (Ocean Science Journal, 2015)

Environmental changes in the Amur Bay (Japan/East Sea) during the last 150 years revealed by examination of diatoms and silicoflagellates - Ira Tsoy; Irina Prushkovskaya; Kirill Aksentov; Anatoly Astakhov (Ocean Science Journal, 2015)

Natural uranium and thorium isotopes in sediment cores off Malaysian ports - Abdul Hafidz Yusoff; Asnor Azrin Sabuti; Che Abd Rahim Mohamed (Ocean Science Journal, 2015)

Gaetice depressus (Crustacea, Varunidae): Species profile and its role in organic carbon and nitrogen flow - A’an. J. Wahyudi; Shigeki Wada; Masakazu Aoki; Takeo Hama (Ocean Science Journal, 2015)

Effects of CO2-induced ocean acidification on the growth of the larval olive flounder Paralichthys olivaceus - Kyung-Su Kim; Jeong Hee Shim; Suam Kim (Ocean Science Journal, 2015)

Introduction of geospatial perspective to the ecology of fish-habitat relationships in Indonesian coral reefs: A remote sensing approach - Shuhei Sawayama; Nurjannah Nurdin; Muhammad Akbar AS; Shingo X. Sakamoto; Teruhisa Komatsu (Ocean Science Journal, 2015)

Simulation of seagrass bed mapping by satellite images based on the radiative transfer model - Tatsuyuki Sagawa; Teruhisa Komatsu (Ocean Science Journal, 2015)

Three-dimensional mapping of red stingray (Dasyatis akajei) movement with reference to bottom topography - Takayoshi Otaki; Masahiro Hamana; Hideaki Tanoe; Nobuyuki Miyazaki; Takuro Shibuno; Teruhisa Komatsu (Ocean Science Journal, 2015)

Multisensor and multitemporal data from Landsat images to detect damage to coral reefs, small islands in the Spermonde archipelago, Indonesia - Nurjannah Nurdin; Teruhisa Komatsu; Agus; M. Akbar AS; Abdul Rasyid Djalil; Khairul Amri (Ocean Science Journal, 2015)

Abundance, composition and growth rate of coral recruits on dead corals following the 2010 bleaching event at Mu Ko Surin, the Andaman Sea - Mathinee Yucharoen; Thamasak Yeemin; Beatriz E. Casareto; Yoshimi Suzuki; Watchara Samsuvan; Kanwara Sangmanee; Wanlaya Klinthong; Sittiporn Pengsakun; Makamas Sutthacheep (Ocean Science Journal, 2015)

Marine habitat mapping at Labuan Marine Park, Federal Territory of Labuan, Malaysia - Fazliana Mustajap; Ejria Saleh; John Madin; Shahimah Abdul Hamid (Ocean Science Journal, 2015)

The potential roles of bacterial communities in coral defence: A case study at Talang-talang reef - Felicity W. I. Kuek; Li-Fang Lim; Lin-Hui Ngu; Aazani Mujahid; Po-Teen Lim; Chui-Pin Leaw; Moritz Müller (Ocean Science Journal, 2015)

Effects of temperature and salinity on survival rate of cultured corals and photosynthetic efficiency of zooxanthellae in coral tissues - Pataporn Kuanui; Suchana Chavanich; Voranop Viyakarn; Makoto Omori; Chiahsin Lin (Ocean Science Journal, 2015)

An ecosystem-based assessment of hairtail (Trichiurus lepturus) harvested by multi-gears and management implications in Korean waters - Hee Joong Kang; Chang Ik Zhang; Eun Ji Lee; Young Il Seo (Ocean Science Journal, 2015)

New records of marine algae in Vietnam - Nhu Le Hau; Bui Minh Ly; Tran Van Huynh; Vo Thanh Trung (Ocean Science Journal, 2015)

Distribution and abundance of sea urchins in Singapore reefs and their potential ecological impacts on macroalgae and coral communities - Beverly P. L. Goh; Dawn Y. F. Lim (Ocean Science Journal, 2015)

228Ra flux in the northwestern Pacific marginal seas: Implications for disproportionally large submarine groundwater discharge - Jeonghyun Kim; Hyung-Mi Cho; Guebuem Kim (Ocean Science Journal, 2015)

Generation of internal tides: An interaction of tides with variable topography and coastal geometry - Himansu K. Pradhan; A. D. Rao; Sachiko Mohanty (Ocean Science Journal, 2015)

Effects of reduced vertical mixing under sea ice on Atlantic meridional overturning circulation (AMOC) in a global ice-ocean model - Sang Yeob Kim; Ho Jin Lee; Jae-Hun Park; Young Ho Kim (Ocean Science Journal, 2015)

Population panmixia and the Pleistocene demographic expansion of spotty belly greenling Hexagrammos agrammus in the East Sea and Northwest Pacific - Kazi Ahsan Habib; Dageum Jeong; Jung-Goo Myoung; Youn-Ho Lee (Ocean Science Journal, 2015)

An overview of polybrominated diphenyl ethers (PBDEs) in the marine environment - Hyo Jin Lee; Gi Beum Kim (Ocean Science Journal, 2015)

Nutrient load estimates for Manila Bay, Philippines using population data - Lara Patricia A. Sotto; Arthur H. W. Beusen; Cesar L. Villanoy; Lex F. Bouwman; Gil S. Jacinto (Ocean Science Journal, 2015)

The sediment load and deposition by river discharge and their relation to organochlorine pesticides pollutants in the sediment bottom of Nha Trang Bay, Vietnam - Hoang Trung Du; Andreas Kunzmann (Ocean Science Journal, 2015)

Using Shoreline Video Assessment for coastal planning and restoration in the context of climate change in Kien Giang, Vietnam - Chu Van Cuong; Michael Russell; Sharon Brown; Peter Dart (Ocean Science Journal, 2015)

Low pH affects survival, growth, size distribution, and carapace quality of the postlarvae and early juveniles of the freshwater prawn Macrobrachium rosenbergii de Man - Gunzo Kawamura; Teodora Bagarinao; Annita Seok Kian Yong; Chiau Yu Chen; Siti Norasidah Mat Noor; Leong Seng Lim (Ocean Science Journal, 2015)

Development of the Operational Oceanographic System of Korea - Kwang-Soon Park; Ki-Young Heo; Kicheon Jun; Jae-Il Kwon; Jinah Kim; Jin-Yong Choi; Kyoung-Ho Cho; Byoung-Ju Choi; Seung-Nam Seo; Young Ho Kim; Sung-Dae Kim; Chan-Su Yang; et al. (Ocean Science Journal, 2015)

Distribution and abundance of octocoral (Octocorallia, alcyonacea) communities at three Southern Islands of Singapore - Jason Zhi Sheng Seah; Nicholas Wei Liang Yap; Lik Tong Tan; Beverly Pi Lee Goh (Ocean Science Journal, 2015)

Theoretical size controls of the giant Phaeocystis globosa colonies - Xiao Liu; Walker O. Smith; Kam W. Tang; Nhu Hai Doan; Ngoc Lam Nguyen (Ocean Science Journal, 2015)

Systematics of marine brown alga Sargassum from Thailand: A preliminary study based on morphological data and nuclear ribosomal internal transcribed spacer 2 (ITS2) sequences - Attachai Kantachumpoo; Shinya Uwai; Thidarat Noiraksar; Teruhisa Komatsu (Ocean Science Journal, 2015)

Genetic similarity of the Hainan medaka populations collected from hyper- and hypo-osmotic environments in northern Vietnam - Hideki Hayakawa; Quang Dung Le; Masato Kinoshita; Yusuke Takehana; Kei Sakuma; Hirohiko Takeshima; Shigeaki Kojima; Kiyoshi Naruse; Koji Inoue (Ocean Science Journal, 2015)

Proceedings of 9th WESTPAC International Scientific Symposium-A Healthy Ocean for Prosperity in the Western Pacific: Scientific Challenges and Possible Solutions, Nha Trang, Vietnam, 22–25 April 2014 - Vo Si Tuan; Youn-Ho Lee; Shuhei Nishida (Ocean Science Journal, 2015)

Bioaccumulation of heavy metals in two matrices of the Bonny/New Calabar River Estuary in Niger Delta, Nigeria - M. C. Onojake; F. D. Sikoki; B. B. Babatunde; R. U. Akpiri; D. Akpuloma; O. Omokheyeke (Ocean Science Journal, 2015)

Vertical structure and variation of currents observed in autumn in the Korea Strait - Sang-Ho Lee; Byoung-Ju Choi (Ocean Science Journal, 2015)

Long-term comparison of satellite and in-situ sea surface temperatures around the Korean Peninsula - Myeong-Taek Kwak; Gwang-Ho Seo; Yang-Ki Cho; Bong-Guk Kim; Sung Hyup You; Jang-Won Seo (Ocean Science Journal, 2015)

Under-ice measurements of suspended particulate matters using ADCP and LISST-Holo - Ho Kyung Ha; Yong Hoon Kim; Hyun Jung Lee; Byongjun Hwang; Hyoung Min Joo (Ocean Science Journal, 2015)

Phytoremediation by benthic microalgae (BMA) and light emitting diode (LED) in eutrophic coastal sediments - Hyeong Kyu Kwon; Seok Jin Oh; Han-Soeb Yang; Pyoung Joong Kim (Ocean Science Journal, 2015)

Morphology and Immune-related activities of hemocytes of the mussel Mytilus coruscus (Gould, 1861) from East Sea of Korea - Hyun-Sung Yang; Hyun-Ki Hong; Ludovic Donaghy; Choong-Hwan Noh; Heung-Sik Park; Dong-Sung Kim; Kwang-Sik Choi (Ocean Science Journal, 2015)

Molecular characterization of four genes highly expressed during megalopa stage in Chinese mitten crab, Eriocheir sinensis - Tae-Ho Yoon; Jaeyong Bae; Hye-Eun Kang; Jung Hwa Choi; Chung Il Lee; Won-gyu Park; Hyun-Woo Kim (Ocean Science Journal, 2015)

Effect of dikes on the distribution and characteristics of Phragmites australis in temperate intertidal wetlands located in the South Sea of Korea - Jiyoung Lee; Soonmo An (Ocean Science Journal, 2015)

Coupled storm surge and wave simulations for the Southern Coast of Korea - Jong-Joo Yoon; Ki-Cheon Jun (Ocean Science Journal, 2015)

Potential blue carbon from coastal ecosystems in the Republic of Korea - Calvyn F. A. Sondak; Ik Kyo Chung (Ocean Science Journal, 2015)

Evaluation of a regional ocean reanalysis system for the East Asian Marginal Seas based on the ensemble Kalman filter - Gwang-Ho Seo; Byoung-Ju Choi; Yang-Ki Cho; Young Ho Kim; Sangil Kim (Ocean Science Journal, 2015)

Reproductive characteristics of the humbug damselfish, Dascyllus aruanus, in Chuuk Lagoon, Micronesia - Young-Ung Choi; Miae Park; Kyun-Woo Lee; Chulhong Oh; Heung-Sik Park (Ocean Science Journal, 2014)

An effective seeding method for restoring the surfgrass Phyllospadix japonicus using an aartificial reef - Jung-Im Park; Min Ho Son; Jeong Bae Kim; Kun-Seop Lee (Ocean Science Journal, 2014)

Seasonal growth dynamics of the seagrass Zostera caulescens on the eastern coast of Korea - Jong-Hyeob Kim; Sang Hoon Park; Young Kyun Kim; Seung Hyeon Kim; Jung-Im Park; Kun-Seop Lee (Ocean Science Journal, 2014)

Seasonal patterns and recruitment dynamics of green tide-forming Ulva species along the intertidal rocky shores of the southern coast of Korea - Sang Rul Park (Ocean Science Journal, 2014)

Distribution of Synechococcus and its phycoerythrin pigment in relation to environmental factors in the East Sea, Korea - Defri Yona; Mi Ok Park; Seok Jin Oh; Woo Chur Shin (Ocean Science Journal, 2014)

Dynamics of strongly nonlinear internal long waves in a three-layer fluid system - Tae-Chang Jo; Young-Kwang Choi (Ocean Science Journal, 2014)

Intrusion of low-salinity water into the Yellow Sea Interior in 2012 - Kyung-Hee Oh; Joon-Ho Lee; Seok Lee; Ig-Chan Pang (Ocean Science Journal, 2014)

Fragilariopsis kerguelensis response to iron enrichment regarding its growth, uptake of nutrients and trace metals, and changes in CO2, CH4, and N2O - Young Shin Kwon; Tae Siek Rhee; Sun Young Kim; Mi Seon Kim; Man Sik Choi; Eun Jin Yang; Young-Nam Kim (Ocean Science Journal, 2014)

Sedimentary organic carbon budget of coastal sediments and the importance of benthic-pelagic coupling off Namhae Island in the South Sea of Korea - Jae Seong Lee; Jeong Hee Han; Sung-Uk An; Taehee Na; Jung No Kwon; Eun-Soo Kim (Ocean Science Journal, 2014)

Molecular cloning, over-expression and enzymatic characterization of an endo-acting β-1,3-glucanase from marine bacterium Mesoflavibacter zeaxanthinifaciens S86 in Escherichia coli - Youngdeuk Lee; Ji-Hyun Lee; Won-Bo Shim; Don Anushka Sandaruwan Elvitigala; Mahanama De Zoysa; Su-Jin Lee; Soo-Jin Heo; Jehee Lee; Do-Hyung Kang; Chulhong Oh (Ocean Science Journal, 2014)

New record of the short-tailed pipefish, Microphis brachyurus brachyurus (Teleostei: Syngnathidae), with a key to the species of the family Syngnathidae from Korea - Sang-Yun Han; Jun Mo Lee; Jin-Koo Kim (Ocean Science Journal, 2014)

Oil-suspended particulate matter aggregates: Formation mechanism and fate in the marine environment - Andrew Loh; Won Joon Shim; Sung Yong Ha; Un Hyuk Yim (Ocean Science Journal, 2014)

Threshold value of Benthic Pollution Index (BPI) for a muddy healthy benthic faunal community and its application to Jinhae Bay in the southern coast of Korea - Jin-Young Seo; Hyun-Sig Lim; Jin-Woo Choi (Ocean Science Journal, 2014)

Assessment of pollution and ecological risk of heavy metals in the surface sediments of Ulsan Bay, Korea - Kongtae Ra; Joung-Keun Kim; Sang Hee Hong; Un Hyuk Yim; Won Joon Shim; Seung-Yong Lee; Young-Ok Kim; Jaesoo Lim; Eun-Soo Kim; Kyung-Tae Kim (Ocean Science Journal, 2014)

Integrative assessment of sediment quality in terms of chemical contamination in Jinhae Bay, South Korea - Sang Hee Hong; Gi Myung Han; Un Hyuk Yim; Dhong-il Lim; Sung Yong Ha; Nam Sook Kim; Won Joon Shim (Ocean Science Journal, 2014)

Water quality assessment at Jinhae Bay and Gwangyang Bay, South Korea - Dongseon Kim; Seung Ho Baek; Dong-Young Yoon; Kyung-Hee Kim; Jin-Hyun Jeong; Pung-Guk Jang; Young-Ok Kim (Ocean Science Journal, 2014)

Marine ecosystem health assessments in Korean coastal waters - Young-Ok Kim; Fu-Liu Xu (Ocean Science Journal, 2014)

Biochemical responses of juvenile rockfish (Sebastes schlegeli) to low levels of dissolved oxygen in Gamak Bay - Jee-Hyun Jung; Ha Na Kim; Young Sun Chae; Won Joon Shim (Ocean Science Journal, 2014)

Cimetidine, acetaminophen, and 1,7-dimethylxanthine, as indicators of wastewater pollution in marine sediments from Masan Bay, Korea - Minkyu Choi; Edward T. Furlong; Stephen L. Werner; Anthony S. Pait; In-Seok Lee; Hee-Gu Choi (Ocean Science Journal, 2014)

Aragonite undersaturation in Gwangyang Bay, South Korea: Effects of fresh water input - Dongseon Kim; Eun-Jin Yang; Seung Ho Baek; Kyung-Hee Kim; Jin-Hyun Jeong; Young-Ok Kim (Ocean Science Journal, 2014)

Morphology and distribution of the three epiphytic dinoflagellate species Coolia monotis, C. tropicalis, and C. canariensis (Ostreopsidaceae, Gonyaulacales, Dinophyceae) from Vietnamese coastal waters - The V. Ho; Lam N. Nguyen (Ocean Science Journal, 2014)

Characterization of bacterial communities associated with seasonal water masses from Tongyoung in South Sea of Korea - Sung-Suk Suh; Mirye Park; Jinik Hwang; Sukchan Lee; Sang Hyun Moh; Ki Hwan Park; Taek-Kyun Lee (Ocean Science Journal, 2014)

Abundance and distribution of Nemopilema nomurai (Scyphozoa, Rhizostomeae), in Korean waters in 2005–2013 - Won Duk Yoon; Hye Eun Lee; Changhoon Han; Soo-Jung Chang; Kyunghoon Lee (Ocean Science Journal, 2014)

Seasonal variation of the neustonic zooplankton community in southern waters of Korea - Hyeon Gyeong Jeong; Hae-Lip Suh; Wonchoel Lee; Ho Young Soh (Ocean Science Journal, 2014)

Assessing the ecosystem health status of Korea Gwangyang and Jinhae bays based on a planktonic index of biotic integrity (P-IBI) - Seung Ho Baek; Moonho Son; Dongseon Kim; Hyun-Woo Choi; Young-Ok Kim (Ocean Science Journal, 2014)

Stock identification and life history interpretation using trace element signatures in salmon otoliths - Sukyung Kang; Suam Kim; Kevin Telmer; David Welch; Youn-Ho Lee (Ocean Science Journal, 2014)

Vitellogenin gene characterization and expression of Asian paddle crabs (Charybdis japonica) following endocrine disrupting chemicals - Kiyun Park; Tae-Soo Kwak; Ihn-Sil Kwak (Ocean Science Journal, 2014)

Comparison of anchovy biomass estimates measured by trawls, egg production methods and hydro-acoustics in the Chesapeake Bay and the Korea Strait - Sukgeun Jung; Edward D. Houde (Ocean Science Journal, 2014)

A review of sediment dynamical processes in the west coast of Korea, eastern Yellow Sea - Hee Jun Lee (Ocean Science Journal, 2014)

Ocean Science Journal indexed in the Science Citation Index Expanded - Won Joon Shim (Ocean Science Journal, 2014)

Rock preference of planulae of jellyfish Aurelia aurita (Linnaeus 1758) for settlement in the laboratory - Won Duk Yoon; Sung-Hwan Choi; Changhoon Han; Won Gyu Park (Ocean Science Journal, 2014)

Sources of plastic marine debris on beaches of Korea: More from the ocean than the land - Yong Chang Jang; Jongmyoung Lee; Sunwook Hong; Jong Su Lee; Won Joon Shim; Young Kyoung Song (Ocean Science Journal, 2014)

Comparison of two different passive air samplers (PUF-PAS versus SIP-PAS) to determine time-integrated average air concentration of volatile hydrophobic organic pollutants - Seung-Kyu Kim; Jong-Eun Park (Ocean Science Journal, 2014)

Distribution patterns of macrobenthic fauna communities in Deukryang Bay, one of the environment conservation areas of Korea - Jin-Young Seo; Hyun-Sig Lim; Jin-Woo Choi (Ocean Science Journal, 2014)

First record of the Thalassinid Upogebia issaeffi (Balss, 1913) (Crustacea: Decapoda: Upogebiidae) in Korean waters - Jae-Sang Hong; Chae-Lin Lee (Ocean Science Journal, 2014)

Germination rate of Phyllospadix japonicus seeds relative to storage methods and periods - Jung-Im Park; Kun-Seop Lee; Min Ho Son (Ocean Science Journal, 2014)

Trace metals (Co, Ni, Cu, Cd, and Pb) in the southern East/Japan Sea - Jeongwon Kang; Man-Sik Choi; Kap-Sik Jeong; Chang-Bok Lee (Ocean Science Journal, 2014)

Two new records of Valenciennea helsdingenii (Perciformes: Gobiidae) and Chromis margaritifer (Perciformes: Pomacentridae) from Jeju Island, Korea - Jung-Goo Myoung; Se Hun Myoung; In-Seo Hwang; Byung-il Kim; Jin-Koo Kim (Ocean Science Journal, 2014)

Enhanced photobiological H2 production by the addition of carbon monoxide and hydrogen cyanide in two unicellular N2-fixing cyanobacterial strains isolated from Korean coasts - Jong-Woo Park; Seung Won Nam; Hyung Seop Kim; Seok-Hyun Youn; Wonho Yih (Ocean Science Journal, 2014)

Variation of the southern Subtropical Countercurrent related to sea surface height and eddies in the northwest tropical pacific - Eung Kim; Dongchull Jeon; Chang Wong Shin; Dong Guk Kim (Ocean Science Journal, 2014)

Tidal oscillations in shallow bays and sediment movement - Heeyoon Park; Roger L. Hughes (Ocean Science Journal, 2014)

Asynchronous responses of fish assemblages to climate-driven ocean regime shifts between the upper and deep layer in the Ulleung basin of the East Sea from 1986 to 2010 - Sukgeun Jung (Ocean Science Journal, 2014)

Regional projection of future extreme wave heights around Korean Peninsula - Dae-Ung Lim; Kyung-Duck Suh; Nobuhito Mori (Ocean Science Journal, 2013)

Three species of Ditrichocorycaeus (Copepoda, Cyclopoida, Corycaeidae) from Korean waters, with new identification parameters - Jin Hee Wi; Dae Hwan Kim; Ho Young Soh (Ocean Science Journal, 2013)

Three species of Agetus (Copepoda, Cyclopoida, Corycaeidae) new to Korean taxa - Jin Hee Wi; Dae Hwan Kim; Ho Young Soh (Ocean Science Journal, 2013)

Ten new species of parasitic cyclopoid copepods (Crustacea) belonging to the families Bomolochidae, Philichthyidae, and Taeniacanthidae from marine fishes in Korea - Il-Hoi Kim; Seong Yong Moon (Ocean Science Journal, 2013)

LPS-induced NO inhibition and antioxidant activities of ethanol extracts and their solvent partitioned fractions from four brown seaweeds - Myoung Lae Cho; Dong-Jin Lee; Hyi-Seung Lee; Yeon-Ju Lee; Sang Guan You (Ocean Science Journal, 2013)

Induction of apoptosis by the tropical seaweed Pylaiella littoralis in HT-29 cells via the mitochondrial and MAPK pathways - Bo-Ram Ye; Junseong Kim; Min-Sun Kim; Jiyi Jang; Chulhong Oh; Do-Hyung Kang; Zhong-Ji Qian; Won-Kyo Jung; Il-Whan Choi; Soo-Jin Heo (Ocean Science Journal, 2013)

Nitrogen budget of the eelgrass, Zostera marina in a bay system on the south coast of Korea - Sang Rul Park; Young Kyun Kim; Seung Hyeon Kim; Kun-Seop Lee (Ocean Science Journal, 2013)

Oxygen penetration through invertebrate burrow walls in Korean tidal flat - Bon Joo Koo; Chul-Hwan Koh (Ocean Science Journal, 2013)

Comparative study on the fauna composition of intertidal invertebrates between natural and artificial substrata in the northeastern coast of Jeju Island - Jae-Hoon Cha; Kwang-Bae Kim; Ji-Na Song; In-Soo Kim; Jeong-Bin Seo; Chul-Hwi Kwoun (Ocean Science Journal, 2013)

An experimental transplantation to select the optimal site for restoration of the eelgrass Zostera marina in the Taehwa River estuary - Jung-Im Park; Jeong Bae Kim; Kun-Seop Lee; Min Ho Son (Ocean Science Journal, 2013)

Late quaternary paleoceanographic changes in the northeastern Ulleung Basin, East Sea, inferred from variations in biogenic components - Yeon Jee Suh; Sangmin Hyun; Chanhong Park (Ocean Science Journal, 2013)

Response of upper ocean and impact of barrier layer on Sidr cyclone induced sea surface cooling - Naresh Krishna Vissa; A. N. V. Satyanarayana; B. Prasad Kumar (Ocean Science Journal, 2013)

The occurrence of Clithon retropictus (v. Martens, 1879) (Gastropoda: Neritidae) in an unusual habitat, northern Jeju Island, Republic of Korea - Ronald G. Noseworthy; Hee-Jung Lee; Kwang-Sik Choi (Ocean Science Journal, 2013)

Assessment of coral health in the coastal areas of the Persian Gulf - Mehdi Bolouki Kourandeh; S. Mohammad Bagher Nabavi; Mahmood Sinaei (Ocean Science Journal, 2013)

Mathematical modeling of competition for ammonium among Bacteria, Archaea and cyanobacteria within cyanobacterial mats: Can ammonia-oxidizers force nitrogen fixation? - Matthew R. Boyett; Alireza Tavakkoli; Dmitri Sobolev (Ocean Science Journal, 2013)

Effects of feed restriction to enhance the profitable farming of blackhead seabream Acanthopagrus schlegelii schlegelii in sea cages - Sung-Yong Oh; Min-Suk Kim; Joon Yeong Kwon; B. A. Venmathi Maran (Ocean Science Journal, 2013)

Growth dynamics of eelgrass, Zostera marina, in the intertidal zone of Seomjin Estuary, Korea - Jeong Bae Kim; Won-Chan Lee; Kun-Seop Lee; Jung-Im Park (Ocean Science Journal, 2013)

Description of a small goby, Trimma grammistes (Perciformes: Gobiidae), from Jeju Island, Korea - Byung Jik Kim; Seung-Ho Choi; Sung Kim (Ocean Science Journal, 2013)

Distribution of small plastic debris in cross-section and high strandline on Heungnam beach, South Korea - Nak Won Heo; Sang Hee Hong; Gi Myung Han; Sunwook Hong; Jongmyoung Lee; Young Kyung Song; Mi Jang; Won Joon Shim (Ocean Science Journal, 2013)

Expression of stress response HSP70 gene in Asian paddle crabs, Charybdis japonica, exposure to endocrine disrupting chemicals, bisphenol A (BPA) and 4-nonylphenol (NP) - Kiyun Park; Ihn-Sil Kwak (Ocean Science Journal, 2013)

Changes in benthic macrofaunal assemblages in relation to bottom trawling in Cuddalore and Parangipettai coastal waters, Southeast coast of India - Samikkannu Muthuvelu; Perumal Murugesan; Muniyandi Muniasamy; Shanmugam Vijayalakshmi; Thangavel Balasubramanian (Ocean Science Journal, 2013)

Integrating Indian remote sensing multi-spectral satellite and field data to estimate seagrass cover change in the Andaman and Nicobar Islands, India - Nobi Elavumkudi Paulose; Elangovan Dilipan; Thirunavukarassu Thangaradjou (Ocean Science Journal, 2013)

Why was the 2008 Indian Ocean Dipole a short-lived event? - Iskhaq Iskandar; Muhammad Irfan; Fadli Saymsuddin (Ocean Science Journal, 2013)

Comparison of S, Se, and 210Po accumulation patterns in common squid Todarodes pacificus from the Yellow Sea and East/Japan Sea - Hannelore Waska; Guebuem Kim; Gi Beum Kim (Ocean Science Journal, 2013)

Molecular identification of anisakid nematodes third stage larvae isolated from common squid (Todarodes pacificus) in Korea - Eko Setyobudi; Chan-Hyeok Jeon; Kwangho Choi; Sung Il Lee; Chung Il Lee; Jeong-Ho Kim (Ocean Science Journal, 2013)

Analysis of horizontal and vertical ring structure based on analytical model and satellite data: Application to the North Brazil Current Rings - Raúl Cruz-Gómez; Julio Salcedo-Castro (Ocean Science Journal, 2013)

Surface current response to wind and plumes in a bay-shape estuary of the eastern Yellow Sea: Ocean radar observation - Sang-Ho Lee; Chan-Young Kang; Byoung-Ju Choi; Chang-Shik Kim (Ocean Science Journal, 2013)

A new method for estimating high-frequency radar error using data from Central San Francisco Bay - Maxwell Hubbard; Donald Barrick; Newell Garfield; Jim Pettigrew; Carter Ohlmann; Matthew Gough (Ocean Science Journal, 2013)

Temporal and spatial resolution of HF ocean radars - Malcom L. Heron; Daniel P. Atwater (Ocean Science Journal, 2013)

An overview of developments and applications of oceanographic radar networks in Asia and Oceania countries - Satoshi Fujii; Malcolm L. Heron; Kuh Kim; Jian-Wu Lai; Sang-Ho Lee; Xiangbai Wu; Xiongbin Wu; Lucy R. Wyatt; Wen-Chang Yang (Ocean Science Journal, 2013)

Copepods of Hatschekiidae (Copepoda, Siphonostomatoida) new to Korean fauna, with description of a new species - Seong Yong Moon; Il-Hoi Kim (Ocean Science Journal, 2013)

Morphology and molecular characterization of the epiphytic dinoflagellate Prorocentrum cf. rhathymum in temperate waters off Jeju Island, Korea - An Suk Lim; Hae Jin Jeong; Tae Young Jang; Nam Seon Kang; Sung Yeon Lee; Yeong Du Yoo; Hyung Seop Kim (Ocean Science Journal, 2013)

Preliminary results of the Japan-Taiwan joint survey on combining ocean radar data in the Kuroshio upstream region - Kaoru Ichikawa; Wen Chang Yang; Akihiko Morimoto; Yutaka Yoshikawa; Shigeo Sugitani; Wen-Shan Chiang; Jian-Wu Lai; En Yu Liang; Cho-Teng Liu; Chang-Wei Lee; Kei Yufu; Moeto Kyushima; et al. (Ocean Science Journal, 2013)

Development of oceanographic radar networks, data management and applications in Asia and Oceania countries - Sang-Ho Lee; Malcolm L. Heron (Ocean Science Journal, 2013)

Right-lateral strike-slip movement of the South Korea Plateau associated with the opening of the East Sea (Sea of Japan) - Dong-Lim Choi; Han-Joon Kim; Hyeong-Tae Jou; Seom-Kyu Jeong; Yong-Kuk Lee; Tae-Hee Lee (Ocean Science Journal, 2013)

Upwelling variability along the southern coast of Bali and in Nusa Tenggara waters - Nining Sari Ningsih; Noviani Rakhmaputeri; Agung B. Harto (Ocean Science Journal, 2013)

Seasonal variations in the low-salinity intermediate water in the region south of sub-polar front of the East Sea (Sea of Japan) - Chang-Woong Shin; Sang-Kyung Byun; Cheolsoo Kim; Jae Hak Lee; Bong-Chae Kim; Sang-Chull Hwang; Young Ho Seung; Hong-Ryeol Shin (Ocean Science Journal, 2013)

Influence of Environmental Variables on the Distribution of Macrobenthos in the Han River Estuary, Korea - Ok Hwan Yu; Hyung-Gon Lee; Jae-Hac Lee (Ocean Science Journal, 2012)

Temporal changes of diatoms in marine biofilm developed on acrylic panels submerged in a tropical coast - Sathianeson Satheesh; Samuel Godwin Wesley (Ocean Science Journal, 2012)

Development and application of a novel miniature in situ microprofiler (NAFRI BelpI) - Jae Seong Lee; Eun-Soo Kim; Sung-Hyun Kahng; Seok-Hyun Yoon; Jin-Hyung Cho; Kyung-Soo Bahk; Dong-Jin Kang (Ocean Science Journal, 2012)

Comparison of primary productivity algorithms for Korean waters - Joo-Eun Yoon; Jisoo Park; Sinjae Yoo (Ocean Science Journal, 2012)

First retrieval of data regarding spatial distribution of Asian dust aerosol from the Geostationary Ocean Color Imager - Kwon Ho Lee; Joo Hyung Ryu; Jae Hyun Ahn; Young Joon Kim (Ocean Science Journal, 2012)

Tidal dynamics in the strong tidal current environment of the Uldolmok waterway, southwestern tip off the Korean peninsula - Sok Kuh Kang; Kyung Tae Jung; Ki-Dai Yum; Kwang-Soo Lee; Jin-Soon Park; Eun Jin Kim (Ocean Science Journal, 2012)

Quantitative analysis of fish schooling behavior with different numbers of medaka (Oryzias latipes) and goldfish (Carassius auratus) - Joo-Baek Leem; Wonju Jeon; Chi-Young Yun; Sang-Hee Lee (Ocean Science Journal, 2012)

Biology, fishery, conservation and management of Indian Ocean tuna fisheries - N. Gopalakrishna Pillai; Palanisamy Satheeshkumar (Ocean Science Journal, 2012)

Paleomagnetic records and mineral-magnetic properties of deep-sea sediments in the NW pacific: Paleoenvironmental implication - Cheong Kee Park; Wonnyon Kim; Youngtak Ko; Hyun-Bok Lee; Jai-Woon Moon; Seong-Jae Doh (Ocean Science Journal, 2012)

Assessment of potential biomarkers, metallothionein and vitellogenin mRNA expressions in various chemically exposed benthic Chironomus riparius larvae - Kiyun Park; Inn-Sil Kwak (Ocean Science Journal, 2012)

Geological consequences of the Saemangeum Dyke, mid-west coast of korea: A review - Hee Jun Lee; Soo Hwan Lee (Ocean Science Journal, 2012)

Spatial scales of mesoscale eddies from GOCI Chlorophyll-a concentration images in the East/Japan Sea - Kyung-Ae Park; Hye-Jin Woo; Joo-Hyung Ryu (Ocean Science Journal, 2012)

Variability of suspended particulate matter in the Bohai Sea from the geostationary Ocean Color Imager (GOCI) - Kevin Ruddick; Quinten Vanhellemont; Jing Yan; Griet Neukermans; Guomei Wei; Shaoling Shang (Ocean Science Journal, 2012)

Impact of multiple satellite ocean color samplings in a day on assessing phytoplankton dynamics - ZhongPing Lee; Mingshun Jiang; Curtiss Davis; Nima Pahlevan; Yu-Hwan Ahn; Ronghua Ma (Ocean Science Journal, 2012)

Assessment of GOCI radiometric products using MERIS, MODIS and field measurements - Nicolas Lamquin; Constant Mazeran; David Doxaran; Joo-Hyung Ryu; Young-Je Park (Ocean Science Journal, 2012)

GOCI data processing and ocean applications - Joo-Hyung Ryu; Joji Ishizaka (Ocean Science Journal, 2012)

A solution for the correct interpolation of data across regions with abrupt changes in tidal phase-lag - Se-Young Park; Do-Seong Byun; Deirdre E. Hart (Ocean Science Journal, 2012)

Spatial variability of biochemical responses in resident fish after the M/V Hebei Spirit Oil Spill (Taean, Korea) - Jee-Hyun Jung; Young Sun Chae; Ha Na Kim; Moonkoo Kim; Un Hyuk Yim; Sung Yong Ha; Gi Myung Han; Joon Geon An; Eunsic Kim; Won Joon Shim (Ocean Science Journal, 2012)

Relationship between polymetallic nodule genesis and sediment distribution in the KODOS (Korea Deep Ocean Study) Area, Northeastern Pacific - Jonguk Kim; Kiseong Hyeong; Hyun-Bok Lee; Young-Tak Ko (Ocean Science Journal, 2012)

Metallothionein-like proteins induced by cadmium stress in the scallop Mizuhopecten yessoensis - Avianna F. Zhukovskaya; Nina N. Belcheva; Valentina S. Slobodskova; Viktor P. Chelomin (Ocean Science Journal, 2012)

Laboratory experiment to measure 5-MHz volume backscattering strengths from Red-tide causing microalgae Chattonella antiqua - Junghun Kim; Jee Woong Choi; Donhyug Kang (Ocean Science Journal, 2012)

Surveillance of waste disposal activity at sea using satellite ocean color imagers: GOCI and MODIS - Gi Hoon Hong; Dong Beom Yang; Hyun-Mi Lee; Sung Ryull Yang; Hee Woon Chung; Chang Joon Kim; Young-Il Kim; Chang Soo Chung; Yu-Hwan Ahn; Young-Je Park; Jeong-Eon Moon (Ocean Science Journal, 2012)

Enhanced biological activity by an anticyclonic warm eddy during early spring in the East Sea (Japan Sea) detected by the geostationary ocean color satellite - Jae-Hyun Lim; Seunghyun Son; Jung-Woo Park; Jung Hyun Kwak; Chang-Keun Kang; Young Baek Son; Jung-No Kwon; Sang Heon Lee (Ocean Science Journal, 2012)

Detecting massive green algae (Ulva prolifera) blooms in the Yellow Sea and East China Sea using Geostationary Ocean Color Imager (GOCI) data - Young Baek Son; Jee-Eun Min; Joo-Hyung Ryu (Ocean Science Journal, 2012)

Estimating photosynthetically available radiation at the ocean surface from GOCI data - Robert Frouin; John McPherson (Ocean Science Journal, 2012)

Evaluation of GOCI sensitivity for At-Sensor radiance and GDPS-Retrieved chlorophyll-a products - Chuanmin Hu; Lian Feng; ZhongPing Lee (Ocean Science Journal, 2012)

Initial validation of GOCI water products against in situ data collected around Korean peninsula for 2010–2011 - Jeong-Eon Moon; Young-Je Park; Joo-Hyung Ryu; Jong-Kuk Choi; Jae-Hyun Ahn; Jee-Eun Min; Young-Baek Son; Sun-Ju Lee; Hee-Jeong Han; Yu-Hwan Ahn (Ocean Science Journal, 2012)

Development of atmospheric correction algorithm for Geostationary Ocean Color Imager (GOCI) - Jae-Hyun Ahn; Young-Je Park; Joo-Hyung Ryu; Boram Lee; Im Sang Oh (Ocean Science Journal, 2012)

Geometric performance evaluation of the Geostationary Ocean Color Imager - Chan-Su Yang; Jung-Hwan Song (Ocean Science Journal, 2012)

Overview of geostationary ocean color imager (GOCI) and GOCI data processing system (GDPS) - Joo-Hyung Ryu; Hee-Jeong Han; Seongick Cho; Young-Je Park; Yu-Hwan Ahn (Ocean Science Journal, 2012)

Seasonal occurrence and microhabitat of the hyperparasitic monogenean Udonella fugu on the caligid Copepod Pseudocaligus fugu infecting the grass puffer Takifugu niphobles in the Seto Inland Sea, Japan - Hiroko Okawachi; Susumu Ohtsuka; Norshida Binti Ismail; B. A. Venmathi Maran; Kazuo Ogawa (Ocean Science Journal, 2012)

Tintinnid species as biological indicators for monitoring intrusion of the warm oceanic waters into Korean coastal waters - Young-Ok Kim; Kyoungsoon Shin; Pung-Guk Jang; Hyun-Woo Choi; Jae-Hoon Noh; Eun-Jin Yang; Eung Kim; Dongchull Jeon (Ocean Science Journal, 2012)

Morphometric and molecular data on two mitochondrial genes of a newly discovered chimaeran fish (Hydrolagus melanophasma, Chondrichthyes) - José De La Cruz-Agüero; Francisco Javier García-Rodríguez; Víctor Manuel Cota-Gómez; Felipe Neri Melo-Barrera; Rogelio González-Armas (Ocean Science Journal, 2012)

Modelling the effect of climate change on the wave climate of the world’s oceans - Erik Vanem; Bent Natvig; Arne Bang Huseby (Ocean Science Journal, 2012)

Spatial distribution and biodiversity of macrofauna in the southeast of the Caspian Sea, Gorgan Bay in relation to environmental conditions - Mehrshad Taheri; Maryam Yazdani Foshtomi; Majid Noranian; Seyed Sahab Mira (Ocean Science Journal, 2012)

DNA damage in the gill cells of the marine scallop Mizuhopecten yessoensis during anoxic stress and aerobic recovery - Valentina V. Slobodskova; Avianna F. Zhukovskaya; Victor P. Chelomin (Ocean Science Journal, 2012)

The study on highly expressed proteins as a function of an elevated ultraviolet radiation in the copepod, Tigriopus japonicus - Igor Z. Zubrzycki; Seunghan Lee; Kanghyun Lee; Magdalena Wiacek; Wonchoel Lee (Ocean Science Journal, 2012)

Dear readers of and contributors to Ocean Science Journal - Won Joon Shim (Ocean Science Journal, 2012)

Estimation of the minimum food requirement using the respiration rate of medusa of Aurelia aurita in Sihwa Lake - Chang-hoon Han; Jinho Chae; Jonghyeok Jin; Wonduk Yoon (Ocean Science Journal, 2012)

Taxonomic studies on Korean marine benthic diatoms — LM and SEM observations of the diatom genus Amphora (Bacillariophyceae) from Korean tidal flats with the first recordings of A. arenicola, A. beaufortiana and A. maletractata var. constricta - Jinsoon Park; Chul-Hwan Koh (Ocean Science Journal, 2012)

Decadal changes in fish assemblages in waters near the Ieodo ocean research station (East China Sea) in relation to climate change from 1984 to 2010 - Kangseok Hwang; Sukgeun Jung (Ocean Science Journal, 2012)

Seasonal variation of freshwater budget in the Yellow and East China Seas simulated from an ocean general circulation model - Taewook Park; Chan Joo Jang (Ocean Science Journal, 2012)

Structural changes in macrozoobenthic communities due to summer hypoxia in Gamak Bay, Korea - Jin-Young Seo; So-Hyun Park; Jung-Ho Lee; Jin-Woo Choi (Ocean Science Journal, 2012)

Molecular characterization and morphology of the photosynthetic dinoflagellate Bysmatrum caponii from two solar saltons in western Korea - Hae Jin Jeong; Se Hyeon Jang; Nam Seon Kang; Yeong Du Yoo; Min Jeong Kim; Kyung Ha Lee; Eun Young Yoon; Éric Potvin; Yeong Jong Hwang; Jong Im Kim; Kyeong Ah Seong (Ocean Science Journal, 2012)

Influence of environmental parameters on the distribution and diversity of molluscan composition in pondicherry mangroves, southeast coast of India - Palanisamy Satheeshkumar; Anisa Basheer Khan (Ocean Science Journal, 2012)

Effect of Taiwan Strait Current on the onshore intrusion of Kuroshio: A geostrophic adjustment model - Young Ho Seung (Ocean Science Journal, 2012)

Assessment of immune parameters of manila clam Ruditapes philippinarum in different physiological conditions using flow cytometry - Kyung-Il Park; Ludovic Donaghy; Hyun-Sil Kang; Hyun-Ki Hong; Young-Ok Kim; Kwang-Sik Choi (Ocean Science Journal, 2012)

New polychaete records from seagrass beds at Minicoy Island, Lakshadweep, India - V. Dalia Susan; N. G. K. Pillai; P. Satheeshkumar (Ocean Science Journal, 2011)

Temporal occurrence patterns and habitat use of fish in the Mangyeong estuary on the western coast of Korea in 2003, before dike enclosure - Sun Wan Hwang; Tae Won Lee; Hak Bin Hwang; Sun Do Hwang (Ocean Science Journal, 2011)

Investigating the effectiveness of the surfactant dioctyl sodium sulfosuccinate to disperse oil in a changing marine environment - David A. Steffy; Alfred C. Nichols; George Kiplagat (Ocean Science Journal, 2011)

Contents and stable isotopic compositions of organic carbon and total nitrogen in the surface sediment of two coastal bays in Korea - Sangmin Hyun; Taehee Lee; Seom-Kyu Jung (Ocean Science Journal, 2011)

Tidal transport through the Tsugaru Strait — part I: Characteristics of the major tidal flow and its residual current - Quang-Hung Luu; Kosuke Ito; Yoichi Ishikawa; Toshiyuki Awaji (Ocean Science Journal, 2011)

Picocyanobacterial abundances and diversity in surface water of the northwestern Pacific Ocean - Dong Han Choi; Jae Hoon Noh; Mi-Seon Hahm; Charity Mijin Lee (Ocean Science Journal, 2011)

Cochlodinium polykrikoides red tide detection in the South Sea of Korea using spectral classification of MODIS data - Young Baek Son; Joji Ishizaka; Jong-Chul Jeong; Hyun-Choel Kim; Taehee Lee (Ocean Science Journal, 2011)

The occurrence of Acartia species and their environmental characteristics at three ports in Korea - Jung-Hoon Kang (Ocean Science Journal, 2011)

Abundance of epiphytic dinoflagellates from coastal waters off Jeju Island, Korea During Autumn 2009 - Hyung Seop Kim; Wonho Yih; Jong Hyeok Kim; Geumog Myung; Hae Jin Jeong (Ocean Science Journal, 2011)

Five new species of lichomolgid copepods associated with ascidians from Korea, with proposal of two new genera (Crustacea, Copepoda, Lichomolgidae) - Seong Yong Moon; Il-Hoi Kim (Ocean Science Journal, 2011)

Secondary production of the eusirid amphipod Pontogeneia rostrata Gurjanova, 1938 (Crustacea: Peracarida) on a sandy shore in Korea - Ok Hwan Yu; Hae-Lip Suh (Ocean Science Journal, 2011)

Improving the description of the suspended particulate matter concentrations in the southern North Sea through assimilating remotely sensed data - Ghada Y. El Serafy; Marieke A. Eleveld; Meinte Blaas; Thijs van Kessel; Sandra Gaytan Aguilar; Hendrik J. Van der Woerd (Ocean Science Journal, 2011)

Reproductive traits of sandbird octopus, Amphioctopus aegina (Gray, 1849) from Mandapam coastal waters (Palk Bay), Southeast Coast of India - Boby Ignatius; Muthukumarasamy Srinivasan; Srinivasan Balakrishnan (Ocean Science Journal, 2011)

Egg production rate of the copepod Calanus sinicus off the Korean coast of the Yellow Sea during spring - Hyung-Ku Kang; Chang-Rae Lee; Keun-Hyung Choi (Ocean Science Journal, 2011)

Interactions between the pathogenic bacterium Vibrio parahaemolyticus and red-tide dinoflagellates - Kyeong Ah Seong; Hae Jin Jeong (Ocean Science Journal, 2011)

Anthropogenic pollution stimulates oxidative stress in soft tissues of mussel Crenomytilus grayanus (Dunker1853) - Nina N. Belcheva; Maxim V. Zakhartsev; Nadezhda V. Dovzhenko; Avianna F. Zhukovskaya; Victor Ya. Kavun; Victor P. Chelomin (Ocean Science Journal, 2011)

Vertical structure of the M2 tidal current in the Yellow Sea - Seok Lee; Heung-Jae Lie; Cheol-Ho Cho; Sok Kuh Kang; William J. Teague; Kyung-Il Chang; Kyu-Min Song; Kyung-Hee Oh (Ocean Science Journal, 2011)

Benthic meiofaunal composition and community structure in the Sethukuda mangrove area and adjacent open sea, East coast of India - Balasubramanaian Thilagavathi; Bandana Das; Ayyappan Saravanakumar; Kuzhanthaivel Raja (Ocean Science Journal, 2011)

Concentrations of trace metals in the tissues of long-beaked common dolphins (Delphinus capensis) in the East Sea, Korea - Seong-Gil Kim; Seong-Soo Kim; Hee-Gu Choi; Yong-Rock An (Ocean Science Journal, 2011)

Taxonomy and zoogeography of euchaetid copepods (Calanoida, Clausocalanoidea) from Korean waters, with notes on their female genital structure - Man-Ki Jeong; Hae-Lip Suh; Ho Young Soh (Ocean Science Journal, 2011)

Tracing origins of sewage and organic matter using dissolved sterols in Masan and Haengam Bay, Korea - Hyo Jin Lee; Sang Hee Hong; Moonkoo Kim; Sung Yong Ha; Soon Mo An; Won Joon Shim (Ocean Science Journal, 2011)

Experimental restoration of a salt marsh with some comments on ecological restoration of coastal vegetated ecosystems in Korea - Bon Joo Koo; Jong Geel Je; Han Jun Woo (Ocean Science Journal, 2011)

Eight new species of ascidicolous copepods from the eastern coast of Korea (Crustacea, Copepoda, Cyclopoida) - Il-Hoi Kim; Seong Yong Moon (Ocean Science Journal, 2011)

The spatial distribution of surface fCO2 in the Southwestern East Sea/Japan sea during summer 2005 - Sang-Hwa Choi; Dongseon Kim; JeongHee Shim; Hong Sik Min (Ocean Science Journal, 2011)

Intertidal meiofauna of Jeju Island, Korea - Olga N. Pavlyuk; Yulia A. Trebukhova (Ocean Science Journal, 2011)

Time series changes in sea-surface temperature, chlorophyll a, nutrients, and sea-wind in the East/Japan Sea on the left- and right-hand sides of typhoon shanshan’s track - Chung Il Lee; Mi-Ok Park (Ocean Science Journal, 2010)

Tidal front and its relation to the biological process in coastal water - Youn-Jong Sun; Yang-Ki Cho (Ocean Science Journal, 2010)

Meiobenthos assemblages in the mekong estuarine system with special focus on free-living marine nematodes - Ngo Xuan Quang; Ann Vanreusel; Nic Smol; Nguyen Ngoc Chau (Ocean Science Journal, 2010)

High organic carbon deposition in the northern margin of the Aleutian Basin (Bering Sea) before the last deglaciation - Boo-Keun Khim; Sunghan Kim; Masao Uchida; Takuya Itaki (Ocean Science Journal, 2010)

Assimilation of sea surface temperature in the Northwest Pacific Ocean and its marginal seas using the ensemble Kalman filter - Gwang-Ho Seo; Byoung-Ju Choi; Yang-Ki Cho; Young Ho Kim; Sangil Kim (Ocean Science Journal, 2010)

Measurement of temporal and horizontal variations in 222Rn activity in estuarine waters for tracing groundwater inputs - Jong-Sun Kim; Michael J. Lee; Jihyuk Kim; Guebuem Kim (Ocean Science Journal, 2010)

Nutrient input from submarine groundwater discharge versus intermittent river-water discharge through an artificial dam in the Yeongsan River estuary, Korea - Jihyuk Kim; Jong-Sun Kim; Guebuem Kim (Ocean Science Journal, 2010)

Dissolved organic phosphorus utilization and alkaline phosphatase activity of the dinoflagellate Gymnodinium impudicum isolated from the South Sea of Korea - Seok Jin Oh; Hyeong Kyu Kwon; Il Hyeon Noh; Han-Soeb Yang (Ocean Science Journal, 2010)

Blooms of Trichodesmium erythraeum in the South Eastern Arabian Sea during the onset of 2009 summer monsoon - K. B. Padmakumar; B. R. Smitha; Lathika Cicily Thomas; C. L. Fanimol; G. SreeRenjima; N. R. Menon; V. N. Sanjeevan (Ocean Science Journal, 2010)

Preliminary results on suspended sediment transport by tidal currents in Gomso Bay, Korea - Hee Jun Lee (Ocean Science Journal, 2010)

Satellite-derived SST validation based on in-situ data during summer in the East China Sea and western North Pacific - Eun Jin Kim; Sok Kuh Kang; Sung-Tae Jang; Jae Hak Lee; Young Ho Kim; Hyoun-Woo Kang; Yeong Yeon Kwon; Young Ho Seung (Ocean Science Journal, 2010)

Reproduction of the giant jellyfish, Nemopilema nomurai (Scyphozoa: Rhizostomeae), in 2006–2008 as peripherally-transported populations - Naoki Iguchi; Hye Eun Lee; Won Duk Yoon; Suam Kim (Ocean Science Journal, 2010)

Pathologic survey on the Manila clam Ruditapes philippinarum (Adams and Reeve 1850) from Haeju off the western coastal Yellow Sea - Hyun-Sung Yang; Kwang-Jae Park; Kwang-Sik Choi (Ocean Science Journal, 2010)

Dear readers of and contributors to Ocean Science Journal - Hae Jin Jeong (Ocean Science Journal, 2010)

Reconstruction of regular time series from bi-monthly temperature data in the Yellow Sea and the northwestern East China Sea - Heung-Jae Lie; Seok Lee (Ocean Science Journal, 2010)

Conjunction of 2D and 3D modified flow solvers for simulating spatio-temporal wind induced hydrodynamics in the Caspian Sea - Mohammad Zounemat-Kermani; Saeed-Reza Sabbagh-Yazdi (Ocean Science Journal, 2010)

Feeding selectivity of calanoid copepods on phytoplankton in Jangmok Bay, south coast of Korea - Min-Chul Jang; Kyoungsoon Shin; Tongsup Lee; Il Noh (Ocean Science Journal, 2010)

Growth, feeding and ecological roles of the mixotrophic and heterotrophic dinoflagellates in marine planktonic food webs - Hae Jin Jeong; Yeong Du Yoo; Jae Seong Kim; Kyeong Ah Seong; Nam Seon Kang; Tae Hoon Kim (Ocean Science Journal, 2010)